Dopamine triggers TOR signaling cascade to drive biomass and astaxanthin hyperaccumulation in Haematococcus lacustris under coordinated salinity and gradient light stress - Shiyu Lin; Qingwei Wang; Raoqiong Che; Qingqing Li; Chunli Yu; Min Yang; Lifang Li; Penghua Gao; Ying Qi; Feiyan Huang; Xiang Wang; Yongteng Zhao; et al. (Bioresource Technology, 2026)

Chemical constituents from Gerbera delavayi and their chemotaxonomic significance - Ming-yue Chen; Li Jiang; Yu-shuang Wen; Ying-jie Xu; Lin Tian; Jia Sun; Yong-jun Li (Biochemical Systematics and Ecology, 2026)

Electric field optimizes bacterium-phage interactions to enhance biofilm adaptation and microbial function in constructed wetlands - Xiaohui Liu; Fengling Zhang; Zijun Lin; Tianci Tang; Jing Xu; Pingfeng Yu; Ying Liu; Fengchang Wu (Water Research, 2026)

Interaction of ARA54 with androgen receptor in mediating testosterone-dependent regulation of caput epididymal GPX5 expression in mice - Dong-li Liu; Xin Gao; Yi-ying Wang; Yu-qing Lin; Si-han Yu; Zhao-jin Luan (Theriogenology, 2026)

Chronic exposure to chlorate at regulatory safety limits induces p21/p16-mediated neuronal senescence and Parkinsonian-like decline - Cai-Jhen Wu; Chien-Tai Hong; Jiun-Lin Horng; Hung-Shao Lai; Hao-Yu Tsai; Tsorng-Harn Fong; Chen-Yuan Hsiao; Cheng-Ying Chu; Yvonne Jing Mei Liew; Tien-Chun Yang (Environmental Pollution, 2026)

Precursor rigidity engineering enables synergistic regulation of closed pores and graphitic domains for balancing energy and power densities in hard carbon anodes - Qiaofeng Huang; Yiwen Sun; Haoliang Lin; Yuhai Wang; Yifan Sha; Weizhen Fan; Litao Shi; Yu Ying; Xianjian Duan; Chunlei Wu; Guang Shi (Chemical Engineering Journal, 2026)

pH-Controlled co-adsorption and selective separation for Cs+ and Sr2+ by an ultra-stable layered titanoniobate - Zhi-Hua Chen; Hao-Wei Lin; Bu-Bu Gao; Hai-Yan Sun; Tian-Yu Pan; Mei-Ling Feng; Xiao-Ying Huang (Chemical Engineering Journal, 2026)

Progressive fluorescence amplification of molecular rotors via G-run-length engineering of G-rich DNA scaffolds - Ruo-Yao Cui; Yu-Chao Cao; Yi-Xuan Gu; Ling-Li Zhao; Xu-Yang Shen; Ying Liu; Ying-Lin Zhou; Xin-Xiang Zhang (Analytica Chimica Acta, 2026)

Cover Image - Chia‐Yu Hsieh; Shang‐Ting Wu; Chun‐Ying Lin (Journal of Fish Diseases, 2026)

Rapid adaptation and enrichment of salt-tolerant anammox via dosing of chemical enhancers in packed-bed biofilm reactor - Ying-yu Li; Lin Lin; Lei Wen; Xiao-yan Li (Water Research, 2026)

Integrated transcriptomic and metabolomic analyses reveal the involvement of AtGASA1 and AtGASA4 in salicylic acid pathway-associated immune responses in Arabidopsis - Jian-Bo Song; Ya-Ru Li; Zi-Xin Zhao; Xian-Zhi Zuo; Cai-Feng Wang; Min Huang; Shu-Fan Liu; Yu-Fan Chen; Wen-Qian Song; Lin Wang; Ying-Juan Wang; Xuan Huang (Plant Science, 2026)

Carbon dot-based catalytic materials: From photo/electrocatalysis to nanozyme activity - Pei-De Zhu; Chang Liu; Hui Wang; Rong-Yu Yao; Ling-Rui Sun; Xin-Ru Xu; Jing-Wen Jiang; Ying-Sheng Xu; Kun-Peng Lin; Jia-Xing Wu (Journal of Environmental Chemical Engineering, 2026)

Recoverable millimeter-sized poly(ether-ether-ketone)-based adsorbent beads with multisite complexation for Co2+/Ni2+ removal from radioactive wastewater - Peng-De Yu; Yan-Lin Ren; Wen-Juan Wang; Ya-Juan Cai; Ting Yue; Ke-Xiao Sang; Yi-Xing Sun; Dan Wu; Zi-Hao Yang; Chuan-Zhe Zhao; Ying-Kang Li; Ya-Ge Wu; et al. (Journal of Environmental Chemical Engineering, 2026)

Structural and functional characterization of whey protein isolate-polyphenol covalent conjugates prepared via electrochemical oxidation, alkaline treatment, and free radical grafting - Jinshun Ye; Ying Xu; Yuting Li; Wenxue Cheng; Xiaozhen Liu; Xiangying Yu; Jingkun Yan; Lin Li (Food Research International, 2026)

Immune response as a modifier linking phthalate exposure to lung function decline: Results from a longitudinal study - Wei-Chi Wang; Yuan-Ting C. Lo; Hsiu-Ying Ku; Hsu-Kai Huang; You-Zhen Chen; Wei-Yu Lin; Han-Bin Huang (Environmental Pollution, 2026)

Epitaxial high-entropy relaxor ferroelectric films for flexible piezoelectric sensors and MEMS - Yu-En Pan; Yu-Hao Tu; Li-Hui Tsao; Yu-Ju Lin; Sheng-Yao Hung; Yi-Chun Chen; Mengyao Xiao; Qibin Zeng; Huajun Liu; Chengkuo Lee; Ying-Hao Chu (Chemical Engineering Journal, 2026)

Crosslinking-regulated dual-network carboxymethyl chitosan/gelatin hydrogel for pH-responsive oral curcumin delivery - Yujing Zhong; Ying Yu; Yonggang Peng; Zhongwen Su; Yangfan Mao; Lin Wang; Meihua Xin; Mingchun Li (Carbohydrate Polymers, 2026)

Coumarin constituents from Gerbera delavayi: Anti-inflammatory and anti-tumor activities with chemotaxonomic significance - Yan Zhong; Yu-Shuang Wen; Ying-Jie Xu; Chun-Hua Liu; Xue Ma; Yong-Lin Wang; Yong-Jun Li; Li Jiang (Biochemical Systematics and Ecology, 2026)

Exposure to a porcine appeasing pheromone in periparturient sows: Effects on behavior, health status, and reproductive performance - Shuang Liu; Liang Wang; Xu-Kai Nie; Chun-Yu Song; Ying-Han Chen; Lin Wang; Cai-Yu Lian (Applied Animal Behaviour Science, 2026)

Single-cell multi-omics dissects transcript isoform and immune repertoire dynamics in human immunosenescence - Yuhui Zheng; Ze-Hui Ren; Yafei Yang; Wenteng Liu; Fupeng Li; Yajun Zuo; Tao Zeng; Xue Wang; Xiumei Lin; Xinyue Zhu; Baibing Guan; Wenwen Zhou; et al. (Science China Life Sciences, 2026)

Membrane-regulated seawater electrolysis for sustainable hydrogen production - Zhongting Liu; Jingfen Yuan; Sunpeng Shan; Guangpu Li; Song Gu; Cheng Chen; Wei Yu; Mingzhu Zhou; Saleem Raza; Ying Liu; Hongjun Lin; Yang Jiao; et al. (Water Research, 2026)

Artificial intelligence-related technologies for municipal solid waste management: A review and new insights from smart cities - Tachin Chin; Ying Fan; Chien-Liang Lin; Yu-Cheng Lin; Kuo-Ti Liao (Sustainable Cities and Society, 2026)

Arbuscular mycorrhizal fungi as soil biota improve soybean nutrient acquisition and yield formation: a global meta-analysis - Ying-chun Du; Qiong Hou; Yu-qi Song; Lin Wang (Rhizosphere, 2026)

Photo-assisted catalytic oxidation using PBA-derived ZnCo oxides in a H₂O₂ system for organic pollutant removal - Jia-Yin Lin; Yun-Ju Lai; Ying-hua Lai; Ta Cong Khiem; Nai-Wen Tsao; Yu-Chih Tsai (Journal of Water Process Engineering, 2026)

Glucose-derived carbon-confined cu nanoparticles for selective nitrate reduction to ammonia under acidic conditions and biofouling-resistant wastewater treatment - Tsung-Ying Yang; Ko-Shan Ho; Kan-Yen Hsieh; Yu-Lin Hsiao; Sheng-Ci Jhong; Hsiu-Chung Tu (Journal of Water Process Engineering, 2026)

Neurotoxicological Concerns: Azole Fungicides as Mixed/Noncompetitive Inhibitors of Human and Rat 5α-Reductase 1 - Jiachen Lin; Yinghao Huang; Yilin Xu; Zhiqiang Yu; Chentao Ding; Mengru Li; Yingfen Ying; Ren-shan Ge; Yiluan Wang (Journal of Hazardous Materials, 2026)

Construction of MOF-decorated 3D printed membrane with hierarchical surface functionalization for oil-water separation: Role of interfacial energy barrier - Jingtao Hu; Zhiyu Zhao; Hua Li; Saleem Raza; Ying Liu; Cheng Chen; Wei Yu; Yanchao Xu; Hongjun Lin; Guanhua Jin; Liguo Shen (Journal of Hazardous Materials, 2026)

Wendan decoction ameliorates chronic obstructive pulmonary disease via regulating pulmonary microbiota homeostasis and inhibiting NOD-like receptor pyrin domain-containing 3-Caspase1 pathway: Integrating chemical profiling, efficacy validation and molecular mechanism elucidation - Song Lin; Qi Yu; Guoan Zhao; Xuanyu Fu; Yuyang Chen; Shutong Chen; Ying Lyu; Weiwei Jia; Yuran Sun; Wenbao Wang; Tianyang Wang; Yan Lin (Food Bioscience, 2026)

Genome-wide association analysis for resistance against iridovirus disease in large yellow croaker (Larimichthys crocea) from a natural outbreak population - Ying Pan; Hongshu Chi; Nengfeng Lin; Junjia Zeng; Xiaodong Liu; Xiuxia Chen; Zaiyu Zheng; Qiuhuan Jiang; Xunkai Yu; Hui Gong (Fish & Shellfish Immunology, 2026)

ROS-responsive “Trojan Horse” nanoplatform via homotypic fibroblast-membrane camouflage for precision reprogramming of pathogenic synoviocytes in rheumatoid arthritis - Hua-Zhong Ying; Zhen-Hua Ying; Zhi-Min Rao; Song-Lin Jiang; Song-Zhao Zhang; Ying-Jun Lou; Karim Malik; Arman Chowdhury; Chen-Huan Yu (Chemical Engineering Journal, 2026)

A chitosan-based cinnamaldehyde–raspberry ketone integrated carrier architecture for oral delivery toward mild metabolic regulation - Yu-Chi Wang; Sin-Huei Chuang; Chien-Fu Lin; Yan-Ting Lin; You-Song Cheng; Chih-Chen Lin; Chi-Chen Ting; Wei-Han Chen; Ting-Yu Chen; Shen-Ho Kuo; Fu-I Tung; Tse-Ying Liu (Carbohydrate Polymers, 2026)

Exposure-informed ventilation control for nanoparticle pollutants in an enclosed industrial built environment: A laser metal deposition case study - Ying-Fang Wang; Thi-Cuc Le; Jing Wang; Yu-Tung Dai; Phuong-Uyen Tran; Van-Nghia Tran; Guo-Ping Chang-Chien; Lin-Chi Wang (Building and Environment, 2026)

Efficient extraction of low phospholipid Moringa oleifera seed oil via enzyme synergistic low-melting eutectic mixture solvents based three-phase partitioning - Jiabo Cheng; Xiaofei Xie; Kungang Li; Xuanyi Yu; Jirui Sui; Quanyu Lin; Ying Yang; Chunying Li; Chunjian Zhao (Biomass and Bioenergy, 2026)

Decoupling of mass-based and oxidative-potential-based source contributions to PM2.5 in Nanjing: Random forest combined with PMF analysis - Yan-Yu Chen; Fang Cao; Chang-Liu Wu; Xiao-Ying Yang; Yu-Ting Mei; Yuan Dai; Meng-Ying Bao; Wen-Huai Song; Yan-Lin Zhang (Atmospheric Environment, 2026)

Weather source heterogeneity affects disease forecasting: A case study of rice bacterial leaf blight in Taiwan - Jie-Hao Ou; Guo-Cih Lin; Yea-Fang Wu; Chi-Yu Chen; Guan-Ying Huang; Hau-Ping Chou; Chien-Chih Kuo; Hsin-Yuh Wu; Qiao-Juan Lai; Chih-Wei Wang; Yi-Chen Tsai; Chang-Hsin Kuo; et al. (Agricultural and Forest Meteorology, 2026)

Investigating the Antiviral Mechanism of Kaempferol Against Grouper Iridovirus: Combined Evaluation of In Vitro Activity and In Vivo Efficacy - Nijia Xue; Lin Huang; Jieying Yu; Jia Cai; Zhengzhao Liu; Yibing Wang; Shu Cheng; Junxiang Lai; Ying Pan; Qing Yu; Wenhong Li; Pengfei Li (Journal of Fish Diseases, 2026)
Singapore grouper iridovirus (SGIV) is one of the major pathogens that pose significant threats to the aquaculture industry. Kaempferol is a flavonoid compound extracted from Illicium verum Hook.f. (star anise), a material that is both edible and used in traditional medicine. In this study, we evaluated the antiviral effects of kaempferol against SGIV in vitro and in vivo, and elucidated the antiviral mechanism. Our study found that kaempferol could effectively resist SGIV infection in vitro and in vivo. Kaempferol might destroy the SGIV envelope and interfere with the attachment, invasion, and replication stages of SGIV infection. Transcriptomic analysis showed that differentially expressed genes regulated by kaempferol were enriched in ribosome, NF‐κB, and phospholipase D signalling pathways. Further screening of immunity‐related genes and pathway analysis revealed that antiviral immune responses were mainly governed by the JAK–STAT, PI3K‐Akt, and TNF signalling pathways. This study demonstrated that kaempferol exhibited significant antiviral effects against SGIV through multiple mechanisms and had the potential to become an anti‐SGIV fishery drug. These findings provide a theoretical basis for the development of effective drugs for the prevention and treatment of SGIV.

Context-dependent coupling between rhizosphere biochemical activation and SOC enrichment in croplands: a global meta-analysis - Ya-Jun Cheng; Jie-Yu-Xin Kang; Chun-Yan Li; Bai-Jian Lin; Yun Zhang; Jian-Ying Qi (Plant and Soil, 2026)

The JAK/STAT pathway: a pivotal therapeutic target in disease and advances in natural product modulation - Ming-Yue Li; Yu-Yang Lin; Chun-Ying Wang; Yu-Shan Qi; Jun-Sheng Zhang; Di Ge; Hai-Na Yu; Hua Zhang; Jie Bao (Molecular Diversity, 2026)

Exosomal miR-21-5p from ectopic endometrial stromal cells drives fibrosis progression in endometriosis through direct VHL targeting - Jia-Hao Chen; Yi-Hong Lei; Dian-Chao Lin; Hua-Ying Zhang; Zhi-Xiong Huang; Ruo-Fan Huang; Pei-Tong Wei; Meng-Jie Yang; Xin-Yu Ding; Wei-Dong Zhou; Qiong-Hua Chen (Human Cell, 2026)

Construction and validation of plant configuration methods for coastal wetland parks under the close-to-nature concept - Ying Lin; Xiaoli Song; Qingyun Yu; Yunjia Kang; Yanchuan Yang; Peiyan Guo; Xiaolei Jiang (Landscape and Ecological Engineering, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Sedimentation rate changes revealing the evolution of circum–Arctic ice sheets since the Last Interglacial - Song Zhao; Dong Wu; Yu-Ying Zhang; Chao Cui; Sen Shan; Peng Ren; Lin-Sen Dong; Wei-Bin Zhang; Shu-Wei Sun; Yan-Guang Liu (Global and Planetary Change, 2026)

Invisible plastic release from overlooked usage practices in microwaved food packaging - Pei-Ying Lin; Shu-Ling Hsieh; I-Hsuan Wu; Yu-Chi Hsieh; Shuchen Hsieh (Food Chemistry, 2026)

The TFAM-OGG1 axis mediates T-2 toxin-induced chondrocyte mitochondrial dysfunction and cartilage degeneration - Jiaxin Li; Chenxi Wang; Buyi Lin; Jiayuan Li; Fang Qi; Ying Liu; Haoyu Du; Yue Zhao; Jun Yu (Food and Chemical Toxicology, 2026)

Layer-by-layer assembly of polycationic electrolytes onto cation exchange membranes for enhanced Li+/Mg2+ selectivity: A comparative study of polyethyleneimine and chitosan - Jiadi Ying; Zhen Cui; Xiaoxiang Xi; Junwei Zhu; Tiancun Liu; Song Lu; Qi Shen; Min Guo; Yeqing Wang; Zhen Yang; Yaochun Chen; Minfeng Zeng; et al. (Desalination, 2026)

Cl−-repelling Mn3O4/Co(OH)2 heterojunction on self-supporting N-doped CNTs for high-stability seawater zinc-air batteries - Lin Mu; Yuxin Yao; Haibo Zhao; Shifang Yang; Ying Wang; Peng Yu (Chemical Engineering Journal, 2026)

Design, preparation and performance study of DAP-1 based conductive energetic composite - Wan-Jun Wei; Rui Pu; Yu-Ruizhi Lin; Ying-Qi Mao; Qi-Long Yan; Shao-Li Chen (Chemical Engineering Journal, 2026)

Intracranial Mitochondrial Microparticles Promote Cerebral Edema via Endothelial Injury in Stroke - Xiaoyan Du; Xintong Yu; Mengfei Wang; Ying Fu; Kunxin Lin; Jiaying Wu; Qianqian Lin; Wenlong Zhao; Yi Lin (Translational Stroke Research, 2026)

Structure-based classification for differential tyrosine kinase inhibitors efficacy of EGFR exon 19 deletions in non-small cell lung cancer - Wei Zhuang; Hua Bai; Jie Zhao; Weihua Li; Jiaojiao Yu; Zhijie Wang; Jianchun Duan; Xuezhi Hao; Yan Wang; Yutao Liu; Lin Wang; Lin Lin; et al. (Science China Life Sciences, 2026)

End-to-end deep learning quadrature phase shift keying demodulation with channel and receiver impairments - Guan-Lin Liu; Chung-Yu Shih; Cissi Ying-tsen Lin (Advances in Space Research, 2026)

The Antiviral Activity and Underlying Mechanisms of Quercetin in Combating Largemouth Bass Virus Infection - Lin Huang; Wenyu Liao; Mingquan Peng; Jieying Yu; Mingzhu Liu; Junxiang Lai; Ermeng Yu; Ying Pan; Fei Ling; Shuyu Han; Qing Yu; Pengfei Li (Journal of Fish Diseases, 2026)
Largemouth bass virus (LMBV), a member of the Ranavirus genus within the Iridoviridae family, is a significant pathogen causing high mortality and substantial economic losses in largemouth bass aquaculture. Therefore, developing effective antiviral agents against this viral infection is crucial for the largemouth bass aquaculture industry. Quercetin, a widely utilised flavonoid known for its therapeutic and prophylactic properties, was investigated for its antiviral efficacy against LMBV and underlying mechanisms in this study. The results demonstrated that quercetin significantly inhibited LMBV propagation in vitro and in vivo, and was effective in both prevention and treatment stages. Specifically, quercetin at 6.25 μg/mL suppressed LMBV (major capsid protein) MCP gene transcription by up to 92.09%, with the post‐infection treatment achieving 99.33% inhibition in vitro. Mechanistic studies revealed that quercetin reduces LMBV infectivity by disrupting viral internalisation and replication, while also potentiating cellular immune responses mediated by the IFN system. In vivo experiments further confirmed that quercetin treatment reduced viral transcription in the liver, spleen and kidney by 97.49%, 47.45% and 98.42%, respectively, at 48 h post‐infection and significantly enhanced the survival rate of infected juveniles. In conclusion, quercetin demonstrated potent antiviral activity against LMBV and might serve as a promising, eco‐friendly antiviral agent.

Taxonomy of Neostagonosporella on Chimonobambusa with descriptions of two new taxa - Xiu-Lan Xu; Yu Deng; Li-Ping Gao; Qian-Ying Huang; Wei Liu; Li Zhuang; Fei Chen; Qian-Gang Xiao; Zhen Zeng; Feng Liu; Qi-Rong Sun; Ying-Gao Liu; et al. (Mycological Progress, 2026)

PROMETHEUS clinical trial protocol: tailoring healthy ageing with lifestyle and nutraceuticals - Ajla Hodzic Kuerec; Lihuan Guan; Weilan Wang; Duarte Barros; Wejdan M. Alenezi; Jozo Grgic; Vanessa K. Wazny; Jordi Morwani-Mangnani; Mazzarine Dotou; Dingding Zhang; Tong Chen; Jiaqiu Wang; et al. (GeroScience, 2026)
The d emographic shift toward an older population is accelerating the prevalence of age-related diseases. Precision geromedicine represents a paradigm shift in targeting the biological processes of ageing to optimise health and healthspan, which likely requires multimodal tailored interventions. PROMETHEUS, as part of the XPRIZE healthspan semi-finalist competition, is an 8-week feasibility and exploratory study including 20 middle-aged-to-older participants who received a multimodal intervention comprising fundamental and augmented interventions. The fundamental interventions include sleep and dietary recommendations; supplementation with whey protein, creatine, and fucoidan; supervised exercise with an exergaming component (dual-task cognitive-physical training); motivational interviewing; and cognitive behavioural therapy. The augmented intervention is further personalised based on predefined gerotypes, reflecting individual ageing patterns beyond chronological age. At baseline, urolithin A, nicotinamide mononucleotide, and/or multivitamin-multimineral were prescribed to participants based on their muscle mass, VO 2 peak, and cognitive performance. At mid-intervention, interventions were adjusted based on individual response, including dose escalation and/or the addition of ergothioneine for inadequate improvement in cognition. Primary outcomes include measures of muscle strength and mass, immune function and cognitive performance, and feasibility indicators such as adherence and trial completion. Secondary outcomes include assessments of other biological, clinical, and digital biomarkers of ageing, as well as qualitative indicators of motivation and personal values. This study is aimed at investigating the recruitment feasibility, safety, adherence, and exploratory outcome trajectories of a multimodal, personalised precision geromedicine intervention protocol based on individual participant’s baseline characteristics and interim responses. These findings will also inform the design of a subsequent 12-month, randomised controlled trial evaluating personalised lifestyle and nutraceutical strategies with the potential to incorporate repurposed pharmacological agents to optimise age-related health outcomes.

Co-exposure to polystyrene microplastics and Di-(2-ethylhexyl) phthalate exacerbates food allergy in mice associated with gut barrier dysfunction - Xuanpei Wang; Wenfeng Liang; Shiyun Chen; Ying Liu; Jiaxin Yu; Jianing Cui; Lin Xu; Min Fang; Zhiyong Gong; Xin Liu; Qing Yang (Food Bioscience, 2026)

Ultrasound-driven structural and functional modifications of grape seed protein revealed by power- and duration-dependent experiments - Ying-Yang Liu; Da-Rui Tang; Shi-Ling Wang; Wei-Wei Li; Jun-Wei Xu; Lian-Bing Lin; Yu-Hang Jiang; Qi-Lin Zhang (Food Hydrocolloids, 2026)

In vitro and in vivo evaluation of Bacillus amyloliquefaciens E35 as prophylactic agents against Singapore grouper iridovirus - Yanxia Gao; Lingling Deng; Yibing Wang; Lin Huang; Jieying Yu; Xiangmou Qin; Junxiang Lai; Ermeng Yu; Shuyuan Zhang; Ying Pan; Jiwei Xu; Qing Yu; et al. (Fish & Shellfish Immunology, 2026)

Pollutant-specific pathways linking gaseous air pollution to adolescent depressive symptoms: Direct and sleep-mediated effects in a population-based retrospective cohort study - Chun-Ji Lin; Po-Ya Chang; Yu-Ling Li; Chih-Da Wu; Chao-Ying Tu; Chih-Yi Wu; Szu-Ying Chen; Hung-Yi Chiou (Environmental Research, 2026)

Erratum to “Plant growth–promoting bacteria reshape rhizosphere microecology to regulate Cd, Pb, and Zn mobilization at root–soil interface” [Bioresour. Technol. 451 (2026) 134559] - Caixing Lai; Kaiyang Ying; Xusheng Jiang; Xuehong Zhang; Hongwei Yu; Huachun Lan; Gang Liu; Geoffrey I. Sunahara; Jie Liu; Hua Lin; Yi Li; Guo Yu (Bioresource Technology, 2026)

Plant growth–promoting bacteria reshape rhizosphere microecology to regulate Cd, Pb, and Zn mobilization at root–soil interface - Caixing Lai; Kaiyang Ying; Xusheng Jiang; Xuehong Zhang; Hongwei Yu; Huachun Lan; Gang Liu; Geoffrey I. Sunahara; Jie Liu; Hua Lin; Yi Li; Guo Yu (Bioresource Technology, 2026)

StrokeDiffNet: quantifying DWI-FLAIR mismatch via a common feature space for time since stroke classification - Jianing Li; Zhihao Lin; Yu Xin; Junjie Ying; Chaochao Wang (Medical & Biological Engineering & Computing, 2026)

Lactate acts as a metabolic brake on inflammation by repressing NLRP3 transcription via NF-κB inhibition - Hsin-An Lin; Hsin-Chung Lin; Chih-Yung Chiou; Hao-Hsuan Peng; Yu-Jen Chen; Bo-Ying Bao; Kuen-Jou Tsai; Chao-Feng Lin; Chieh-Tien Shih; Sheng-I. Hu; Kuo-Yang Huang; Lih-Chyang Chen (Inflammation Research, 2026)

A chimeric PRRSV vaccine with dual Nsp2 deletions elicits cross-lineage protection against heterologous challenge - Zhuo-ran Miao; Bo Han; Ling-zhai Meng; Zhen-hui Ren; Yi-han Lu; Jing Li; Wen Sun; Shi-qin Zhang; Jia Wang; Jin-jin Ma; Jia-Lu Li; Yu-tong Zhu; et al. (The Veterinary Journal, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Application of a next generation risk assessment framework, integrated testing strategy defined approaches and read-across for evaluating the skin sensitization potency: Case studies with 5-hydroxymethylfurfural and 5,5′-oxydimethylenebis (2-furfural) - Ni Lin; Jianing Zhang; Ying Liu; Fenglan Zhang; Gangli Wang; Zhenxi Yu; Hongtao Jin; Yong Lu (Regulatory Toxicology and Pharmacology, 2026)

Mechanically engineered multi-oxide heterojunctions for bifunctional antibacterial and photocatalytic environmental remediation - Juan Pei; Jialan Mi; Shuhan Yao; Mingxing Guo; Ye Zhang; Xiaoling Wan; Wei Wu; Ying Hong; Pei Hu; Ping Chen; Lin Chen; Haichun Zeng; et al. (Journal of Environmental Chemical Engineering, 2026)

Enhancing environmental stress tolerance of Saccharomyces cerevisiae by deletion of NTH1 and FKS3: Implications for beer brewing - Chih-Yuan Tan; Huan-Yu Lin; Tsung-Tang Chen; Ying-Ta Shih; Yun-Chin Chung (International Journal of Food Microbiology, 2026)

Multifunctional Cu2O@Ag probe for ultra-sensitive SERS detection and inhibition of Escherichia coli O157: H7 - Hao Jiang; Yu-Qing Wang; Huan Cheng; Shi-Ying Fu; Hongmei Li; Jia-Sheng Lin; Yue-Jiao Zhang; Jian-Feng Li (Food Chemistry, 2026)

Virus-host metabolic interaction: SGIV-induced protein lactylation suppresses viral propagation - Mingming Zhao; Jiaxi Li; Mingzhu Liu; Ying Pan; Sining Su; Xiangmou Qin; Yanxia Gao; Lin Huang; Junxiang Lai; Jia Cai; Huapu Chen; Qing Yu; et al. (Fish & Shellfish Immunology, 2026)

Biodegradable mulch film-enriched with biochar, chicken feather, and oyster shell powder for improved soil quality and crop productivity - Kesinee Iamsaard; Girma Sisay Wolde; Chih-Huang Weng; Ying-Chen Chen; Han-Yu Hsueh; Jenn-Wen Huang; Yao-Tung Lin (Environmental Research, 2026)

Tailored self-assembled molecule for efficient charge extraction and enhanced crystallization in wide-bandgap perovskite solar cells - Haojun Hu; Xianglang Sun; Xuke Yang; Zongbao Li; Peiyan Zhang; Xinyu Yu; Shi'ang Li; Zifan Lin; Dayu Liu; Ziyang He; Chuyun Deng; Longhui Zeng; et al. (Chemical Engineering Journal, 2026)

Amorphous/crystalline heterophase induced S2− migration and oxidation for enhanced oxygen evolution reaction - Yue Huang; Jiejie Li; Yu Liu; Ying-Jie Ma; Lin Zhu; Fu-Rui Teng; Ziqi Tian; Ai-Dong Li (Chemical Engineering Journal, 2026)

Synergistic interfacial engineering in MXene/NiCoSe2/NCS heterostructure for rapid charge transfer in supercapacitors - Wenhao Chen; Lin Sun; Bin He; Muhammad Usman; Yulong Ying; Longhua Li; Yu Liu (Chemical Engineering Journal, 2026)

Benzotriazole ultraviolet stabilizers impair trophoblast function at nanomolar concentrations via GPER signaling: implications for placental health - Ze-Pei Zhao; Shi-Ye Zhu; Ying-Huang Hu; Yu-Ke Wan; Shang-Jun Xu; Jie-Zhi Ma; Deng-Ni Lai; An-Wei Chen; Yuan Yang; Lin Luo; Lin-Ying Cao (Chemico-Biological Interactions, 2026)

In Situ Hybridization and RT ‐ PCR Detection of Nervous Necrosis Virus in Fourfinger Threadfin, Eleutheronema tetradactylum , in Taiwan - Chia‐Yu Hsieh; Shang‐Ting Wu; Chun‐Ying Lin (Journal of Fish Diseases, 2026)
Between April and July 2020, suspected outbreaks of nervous necrosis virus (NNV) infection were observed in fourfinger threadfin ( Eleutheronema tetradactylum ) fingerling hatcheries in Pingtung County, southern Taiwan. Affected fish exhibited spiral swimming behaviour and abdominal distension, resulting in mortality rates between 50% and 100%. Histopathological examination showed severe vacuolation in the brain and ocular tissues, with large oval and/or irregular basophilic cytoplasmic inclusion bodies in the brain. Phylogenetic analysis of the viral replicase (RNA1) and capsid protein (RNA2) genes revealed high nucleotide sequence identities among the isolates in this study, with sequence similarity rates of 96.9%–99% for RNA1 and 98.2%–99.0% for RNA2 compared to RGNNV reference strains available in the NCBI GenBank database. This is the first detection of betanodavirus in fourfinger threadfin in Taiwan, using RT‐PCR and ISH. A positive correlation between elevated water temperatures and disease severity indicates the need for year‐round surveillance and genomic analysis to clarify the epidemiology of FTNNV. The data suggest that infected eggs may facilitate the vertical transmission of Betanodavirus. Crucially, utilising virus‐free broodstock, alongside routine health screening and environmental control, is essential for mitigating NNV risks in fourfinger threadfin aquaculture.

Impacts of urban hierarchy, mobility, and built environment on transport carbon emissions - Yu-Sheng Shen; Ying-Chen Lin; Jianyi Lin; Lilai Xu; Chaofan Xian (Sustainable Cities and Society, 2026)

From air to water: Regulation-induced pollution substitution across media - Lin Xiang; Ying Fan; Xueying Yu (Resources, Conservation and Recycling, 2026)

Viral communities as mirrors and vectors: Tracing antibiotic resistome distribution and dissemination across diverse habitats in Macao - Yu-Qiu Ye; Da Lin; Luo-Qin Shen; Di Wu; Ying Li; Yi-Fei Wang; Dong Zhu (Journal of Hazardous Materials, 2026)

A transformer-reinforcement learning framework integrating acoustic thermometry for multi-pollutant prediction and control in a full-scale WtE plant in China - Yuxuan Ying; Linyi Chen; Hanqing Yang; Tianyi Zhu; Weiwei Cao; Zhenwei Yang; Hongyu Sun; Jinghao Ye; Yu Liu; Yunhua Zhao; Weiya Jin; Mi Yan; et al. (Journal of Cleaner Production, 2026)

Formaldehyde activates the RUNX1–ISX axis to promote leukemic reprogramming, a pathway associated with poor prognosis in pediatric B-ALL - Pei-Chin Lin; Li-Ting Wang; Li-Heng Ye; Pin-Ying Tseng; Pei-Hsien Huang; Wan-Yi Hsu; Yu-Mei Liao; Shyh-Shin Chiou; Shih-Hsien Hsu (Environmental Pollution, 2026)

Building a yeast cell factory for green biomanufacturing of (R)-(+)-γ-decalactone: A natural peach-like aroma compound - Yizi Yu; Kaifeng Wang; Tao Sun; Shushu Li; Ying Zhou; Mei-Li Sun; Lu Lin; Rodrigo Ledesma-Amaro; Xiao-Jun Ji (Chemical Engineering Journal, 2026)

Risk evaluation associated with high-temperature disasters in citrus-producing regions of China - Swe Zin Phyo; Siliang Shuai; Lin Zhao; R. M. Dinesh Madhushanka Karunarathna; Ying Yu; Abu Reza Md. Towfiqul Islam; Qi Li; Zhenghua Hu (Theoretical and Applied Climatology, 2026)

Deletion of the SHORT Syndrome Gene Prkce Results in Brain Atrophy and Cognitive and Motor Behavior Deficits in Mice - Yu-Long Bao; Wei-Peng Duan; Yan Yang; Zhijie Lin; Ying Shen; Rui Zheng; Xin-Tai Wang (Neuroscience Bulletin, 2026)

Sinomenine ameliorates experimental autoimmune neuritis by suppressing pro-inflammatory immune components and restoring immune balance - Yan-Mei Gong; Zhen-Lin Liu; Si-Miao Li; Yi-Fan Wei; Guo-Hui Gao; Rui-Qi Xu; Xue-Min Li; Yu-Dong Liu; Rui-Sheng Duan; Ying Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Pre-cultivation of nitrifying biofilms for rapid start-up of biofilm reactors: Manipulation by the biocarrier packing mode and fluid conditions - Ying-yu Li; Pei Wang; Guiyun Chen; Lin Lin; Xiao-yan Li (Journal of Cleaner Production, 2026)

Robigenin in combating largemouth bass ranavirus: Investigating the antiviral potency and underlying mechanisms - Wenyu Liao; Lin Huang; Jieying Yu; Mingzhu Liu; Nijia Xue; Junxiang Lai; Ermeng Yu; Fei Ling; Shuyu Han; Ying Pan; Pengfei Li; Qing Yu (Fish & Shellfish Immunology, 2026)

REAL208, a Liposome-based Formulation of Phosphodiesterase Inhibitor, Protects Acute Kidney Deficiency in Mice - Jui-Chi Tsai; Yi-Wen Lin; Chun-Yao Huang; Chun-Ming Shih; Yu-Tse Wu; Toshio Kurosaki; Yuki Inoue; Ying-Chi Du; Feng-Yen Lin (Pharmaceutical Research, 2026)

Zebrafish Model Reveals Early Electrocardiographic and Molecular Signatures of Doxorubicin-Induced Cardiotoxicity - Zih-Yin Lai; Chi-Ying Lee; Yu-Ching Chiu; Chia-Hung Lin; Chung-Chi Yang; Chia-Chia Ho; Lawrence Yu-Min Liu; Yung-Jen Chuang (Cardiovascular Toxicology, 2026)

Phosphorus-driven enhancement of microalgal growth, lipid biosynthesis, and nutrient removal efficiency in Monoraphidium sp. QLZ-3: Implications for biofuel production and high‑phosphorus wastewater treatment - Shiyu Lin; Jinkun You; Yongteng Zhao; Qingwei Wang; Ying Qi; Feiyan Huang; Xuya Yu; Lei Yu (Algal Research, 2026)

Integrated LC-Orbitrap-MS and network pharmacology decipher the pharmacological basis of Eucommiae folium in treating rheumatoid arthritis - Yasi Deng; Ling Liang; Haokai Lin; Xinyang Shen; Hao Zheng; Ying Deng; Xing Tian; Juan Huang; Ye Zhang; Bin Li; Huanghe Yu; Wei Wang (Molecular Diversity, 2026)

Pharmacotranscriptomics-based discovery and hydrogel-mediated delivery of drug combinations for potentiated cancer immunotherapy - Rong Liu; Hui-Han Yu; Wei-Rong Li; Jia-Si Wu; Jing-Yang Zhang; Jia-Qi Luo; Yu Pang; Ying Chen; Yan-Dan Yao; Run Lin; Ling Wang; Jin-Zhi Du; et al. (Science Bulletin, 2026)

Posttranslational regulation of TOR kinase activity controls resource allocation between plant growth and immunity in Arabidopsis - Jianwei Li; Ran Wang; Chenying Li; Xijie Guo; Qinghong Li; Zhixuan Wu; Shanshan Zeng; Fan Qi; Yuchen Wang; Zhiyi Jia; Weiwei Yu; Zeming Huang; et al. (Molecular Plant, 2026)

Sex-specific associations between exposure to metal mixtures and mitochondrial DNA copy number: A repeated-measures study - Junxiu He; Xiaoting Ge; Sencai Lin; Yu Bao; Hong Cheng; Sihan Hu; Xiuming Feng; Qinghua Fan; Ying Yang; Xiaobo Yang (Journal of Environmental Sciences, 2026)

Coated ferrous sulfate requirement for alleviating hypoxia-induced hepatopancreatic inflammation in sub-adult grass carp (Ctenopharyngodon idella) - Yu-Juan Yang; Pei Wu; Wei-Dan Jiang; Yao-Bin Ma; Hong-Yun Zhang; Yang Liu; Xiao-Wan Jin; Hong-Mei Ren; Ying-Gu Kuang; Xiao-Qiu Zhou; Lin Feng (Fish & Shellfish Immunology, 2026)

Corrigendum to “Construction of ultrathin PANI nanostructure on cation-exchange membranes for selective lithium extraction” [Desalination, 619 (2026) 119555] - Jiadi Ying; Zhen Cui; Tiancun Liu; Song Lu; Qi Shen; Min Guo; Yeqing Wang; Zhen Yang; Minfeng Zeng; Zhixin Yu; Yuqing Lin (Desalination, 2026)

Contrasting size responses of loricate ciliates to long-term warming: agglutinated forms decrease while hyaline forms increase - Yunfan Zhang; Wenhua Bian; Hanyue Chen; Wuchang Zhang; Chaofeng Wang; Jichen Qiu; Xiaoxia Sun; Jun Lin; Ying Yu; Meiping Feng; Bingzhang Chen (Marine Biology, 2026)

Rapid microfluidic sample preparation for mass spectrometric analysis of wild-type and mutant BRAF protein - Yen-Heng Lin; Heng-Yun Chang; Chia-Chun Wu; Yung-Chin Hsiao; Ying-Hao Wen; Jau-Song Yu (Analytica Chimica Acta, 2026)

Mechanisms for enhanced antibiotic removal and lipid production by a cyanobacteria-bacteria consortium in an optimized baffled photobioreactor - Ziqi Yu; Guannan Lin; Yawen Qi; Ying Liu; Jian Zhang (Algal Research, 2026)

Mitigation of antibiotic resistance genes and pathogens via black soldier fly-mediated bioconversion of chicken manure - Yun-Ying Wu; Yuan-Yu Lin (Science of The Total Environment, 2026)

Histone H3.3 phosphorylation facilitates H3K9me3-heterochromatin formation during retrotransposon silencing and X-chromosome inactivation via H3.3K27me3–CBX7–KAP1 axis - Jun Chen; Jiyu Chen; Zhouliang Yu; Liwei Zhang; Yanchao Liu; Xuan Ouyang; Juan Yu; Menghan Wang; Shangqiang Xie; Ming Wang; Tiantian Zhang; Zhaohui Jin; et al. (Science Bulletin, 2026)

Exploring different modification methods of biochar for Se(IV) removal from water: Synergistic effect of adsorption and reduction - Yu-Ying Wang; Juan Yu; Rong-Ting Jiao; Li-Li He; Yao Su; Yun-Long Wang; Hui Lin; Yan Shi; Hao-Hao Lyu (Journal of Contaminant Hydrology, 2026)

Mechanism and dynamic evolution of LED irradiation on volatile metabolites: A novel strategy for optimizing aroma quality in innovative black tea - Jihang He; Xinru Yu; Yunzhi Hao; Qiuming Li; Qingyang Wu; Xiaoxi Ou; Ying Xu; Hongzheng Lin; Ziwei Zhou; Yun Sun (Food Chemistry, 2026)

Design and synthesis of multifunctional polyaspartic acid derivatives as green water treatment agents: Calcium scale inhibition, antibacterial activity, and fluorescence properties - Ying Zhang; Lin-Lin Zhao; Yu Han; Yu-Xia Wang; Zhong-Yan Cao; Ya-Min Cheng; Ying Xu (Desalination, 2026)

Construction of ultrathin PANI nanostructure on cation-exchange membranes for selective lithium extraction - Jiadi Ying; Zhen Cui; Tiancun Liu; Song Lu; Qi Shen; Min Guo; Yeqing Wang; Zhen Yang; Minfeng Zeng; Zhixin Yu; Yuqing Lin (Desalination, 2026)

Pivotal effect of oxygen vacancies on S-scheme BiVO4/g-C3N4: Novel dual activation mechanistic studies in photocatalytic selective ethylbenzene oxidation under LED irradiation - Wen-Yu Luo; Ze-Lin Wang; Peng-Jiang Chao; Ying-Ying Xu; Yanfei Xu; Zhuo Li; Lin-Yu Jiao; Mingyue Ding (Chemical Engineering Journal, 2026)

Triatomic-doped MXene based catalyst with sodium alginate encapsulation their molecular and DFT calculation study for efficient photocatalytic removal of disinfected by-product from drinking water - Saleem Raza; Ata Ur Rehman; Zhiyu Zhao; Hua Li; Cheng Chen; Wei Yu; Ying Liu; Yanchao Xu; Liguo Shen; Hongjun Lin (Chemical Engineering Journal, 2026)

A new fucosylated glucuronoxylomannan from the fruit bodies of Tremella aurantia: structural characterization and immunoenhancing activity on seasonal influenza mRNA vaccine - Jing Chen; Yuan Ma; Zhi-Min Rao; Song-Lin Jiang; Ying-Jun Lou; Karim Malik; Arman Chowdhury; Hua-Zhong Ying; Chen-Huan Yu (Carbohydrate Polymers, 2026)

Effects of dietary selenium supplementation on physiological parameters, tissue fatty acid composition, and fatty acid-metabolism relative gene expression of grouper (Epinephelus coioides) fed high plant protein diets - Yen-Chun Lee; Ying-Chieh Lin; Yu-Sheng Huang; Yu-Hung Lin (Fish Physiology and Biochemistry, 2026)

Novel insights into cyanobacterial (microcystins) neurotoxicity in rats: hepatic encephalopathy - Wen-Li Xu; Liang Chen; Hui-Hui Fan; Geoffrey A. Codd; John P. Giesy; Yu-Ming Guo; Elizabeth D. Hilborn; Daniela Sedan; Darío Andrinolo; Saurabh Chatterjee; Hai-Jun Wang; Ying Liu; et al. (Archives of Toxicology, 2026)

Skin Ulceration in Farmed Leopard Coral Grouper (Plectropomus leopardus) Was Associated with Vibrio spp. and Photobacterium damselae in China - Yunji Xiu; Xiaowan Lin; Lirong Jiang; Zemin Bai; Jinlong Dong; Jinjing Cao; Xiuxiu Tian; Yu Zhang; Wei Wang; Ying Huang; Bo Zhou; Lei Wang; et al. (Fishes, 2026)
The leopard coral grouper (Plectropomus leopardus), an economically important marine fish, is widely farmed in Hainan Province, China. However, intensive farming has led to frequent disease outbreaks, including viral nervous necrosis, vibriosis, and enteritis, with skin ulceration a widespread and significant concern. To identify the pathogen causing skin ulceration, we collected diseased fish from Hainan and conducted histopathological and ultrastructural analyses, parasite examination, viral metagenomic sequencing, and bacterial isolation and identification. The histopathological analysis and ultrastructural observation showed that the diseased P. leopardus displayed marked pathological alterations, with significant hepatic degeneration and necrosis and splenic structural disorganization. Parasites and viruses were both excluded from being the primary pathogen. A total of 79 bacterial strains were isolated from diseased P. leopardus liver tissue, including Vibrio harveyi (38 strains, 48.1%), Vibrio owensii (17 strains, 21.5%), Vibrio rotiferianus (16 strains, 20.3%), and Photobacterium damselae subsp. damselae (8 strains, 10.1%). Infection experiments suggested that all four bacterial species could induce skin ulceration. This study demonstrates that skin ulceration in P. leopardus is associated with multiple bacterial pathogens, refining the previous view that attributed the disease solely to V. harveyi. These findings provide a foundation for developing vaccines and disease-resistant breeding strategies.

Two new clerodane diterpenoids and their anti-inflammatory activity from Callicarpa integerrima - Muhammad Aurang Zeb; Xiao-Ying Ruan; Xing-Jie Zhang; Yu-Tong Xing; Meng-Ru Wang; Yuan-Lin Kong; Xiao-Li Li; Kai Jiang; Wei-Lie Xiao (Natural Product Research, 2026)

A novel single-cell communication framework combining multi-omics reveals neuro-viral pathogenesis in fish - Yi-Fan Liu; Teng-Fei He; Zhi-Wen Zhao; Bao-Sheng Wu; Ying Liang; Lin-Miao Li; Jin-Ping Chen; Ye-Pin Yu (Marine Life Science & Technology, 2026)

ER stress disrupts MFN2-related mitophagy via HRD1-PINK1/ parkin axis in bovine embryos - Shu-Ming Shi; Li-Ying Liu; Zhi-Chao Chi; Lin-Yi Qu; Jing-Hang Li; Guan-Lin Jia; Yu-Yan He; Yong-Xun Jin; Ming-Jun Zhang; Xian-Feng Yu (Theriogenology, 2026)

Dicyanoisophorone-based near-infrared fluorescent probe with a large Stokes shift for the detection and bioimaging of hydrazine - Hong-Cheng Xia; Yu-Hang Zhang; Li-Ming Lv; Di Han; Hong-Kun Yang; Hui-Juan Yan; Jie-Li Lv; Jun-Tang Lin; Ying-Ying Kong (Journal of Hazardous Materials, 2026)

Modified QuEChERS coupled with hybrid mass spectrometry for 322 target pesticides and suspect screening of emerging organic contaminants in agricultural soils - Yu-Hui Chang; Chi-Chieh Hu; Chinn-Yuan Fu; Sichao Wang; Yu-Min Tzou; Shiou-Ruei Lin; Hsiao-Ying Yang; Jerry J. Wu; Cheng-Hua Liu; Ya-Hui Chuang (Journal of Hazardous Materials, 2026)

Dibifree, a dietary phytomix, improves glycemic control and adiposity via modulation of the gut–pancreas–adipose–immune axis in type 2 diabetes - Tzu-Yi Huang; Niann-Tzyy Dai; Hsiu-Jung Liao; Ly Hien Doan; Tai-Shan Cheng; Wen-Yu Hsieh; I-Hsuan Lin; Yu-Tang Huang; Chia-Ching Liaw; Hsiao-Sheng Liu; Wei-Ming Cheng; Chun-Li Su; et al. (Food Research International, 2026)

Pulsed electric fields as a green alternative to chemical treatment: Toward enhanced molecular interactions and performance in biodegradable preservation films - Rui Wang; Pei-Feng Guo; Ying Xu; Xing-Chan Xie; Dan-Dan Lin; Yu-Wei Wu; Dong-Yang Xu; Lang-Hong Wang; Xin-An Zeng (Chemical Engineering Journal, 2026)

Enhancing capacitive energy storage in Na0.5Bi0.5TiO3-based relaxor ferroelectric ceramics by tuning polymorphic polar nanoregions - Binglong Zheng; Ying Lin; Fei Yan; Qibin Yuan; Yongzhen Ma; Yanlong Ma; Yu Zhang; Da Li; Haibo Yang (Chemical Engineering Journal, 2026)

Statistical characteristics of storm cells and centroid-based probability nowcasts by tracking error - Kao-Shen Chung; Tsai-Jung Lee; Li-Pen Wang; Bing-Zhang Wang; Chieh-Ying Ke; Yi-Hao Tsou; Shin-Gan Chen; Ping-Yu Lin; Treng-Shi Huang (Atmospheric Research, 2026)

Hippocampal Neuronal Ferroptosis Driven by Lipocalin-2 Mediates Comorbid Visceral Pain and Anxiety in Irritable Bowel Syndrome - Ying Tang; Zhengqing He; Qianli Zhang; Yiqian Liu; Lu Li; Yu Chen; Aiqin Chen; Chun Lin (Molecular Neurobiology, 2026)

Emerging trends and clinical challenges in AI-enhanced emotion diagnosis using physiological data - Ying-Ying Tsai; Guan-Lin Wu; Yu-Jie Chen; Yen-Feng Lin; Ju-Yu Wu; Ching-Han Hsu; Lun-De Liao (Medical & Biological Engineering & Computing, 2026)

QTL analysis of single-segment substitution lines dissected from a rice CSSL-Z668 and fine-mapping of qGL3.4 for grain length - Si-Qian Xiang; Yu-Zhu Tao; Zhao-Peng Yu; Zhuo-Wen Zhao; Han Zhang; Qiao-Long Li; Lu Li; Ao-Ni Xiang; Jing-Hong Xu; Fan Zhang; Xu Yan; Zheng-Lin Yang; et al. (Euphytica, 2026)

Correction: Isolation and functional identification of Jasmonate resistant 1, a jasmonic acid isoleucine-conjugating enzyme in catharanthus roseus - Aikun Pan; Haiqiao Gao; Ying Lin; Bingrun Yang; Chunhao Chang; Zhiwen Liu; Yanyan Wang; Zhaoxia Jin; Fang Yu (Journal of Plant Research, 2026)

Integrating structural equation modeling and machine learning to unravel the drivers of fine-grained urban thermal patterns - Ying Ding; Chen Huang; Jue-Yu Lin; De-Shun Xu; Yang-Zi Che; Ying Sun; Wei-Lin Liao (Urban Climate, 2025)

Fluoride removal by MgO-based adsorbents synthesized via distinct routes: Comparative evaluation of adsorption efficiency and column-scale stability - Yee-Rui Chan; Wei-Han Lin; Wei-Zhe Lin; Rao Y. Surampalli; Ying-Liang Yu; Chih-Ming Kao (Journal of Water Process Engineering, 2025)

Integrating stream storage and lagging effects in analytical models for stream depletion prediction - Ying-Fan Lin; Bwalya Malama; Meng-Yu Lin (Journal of Hydrology, 2025)

Sponge-like mesostructured perovskite catalysts with enhanced redox properties for efficient toluene oxidation - Jia-Yin Lin; Yu-Lun Wu; Guan-Jie Wang; Chia-Jou Liu; Chih-Ying Wang; Wen-Ta Yang (Journal of Environmental Chemical Engineering, 2025)

Photocatalytic activation of peroxyacetic acid by MnFe₂O₄ for efficient caffeine degradation: Efficacy, mechanisms and reusability - Ying Yu; Gengwei Lin; Huilin Dai; Qingsong Li; Chao Huang; Yunbo Song (Journal of Environmental Chemical Engineering, 2025)

Rapid and sensitive on-site detection of peach (Prunus persica) species in fruit juices using a RAA-CRISPR/Cas12a approach - Lin Wang; Ran-Ran Xing; Xiao-Ke Liang; Yao-Xian Yu; Qiu-Ju Yi; Si-Yuan Lu; Ting-Ting Deng; Jiu-Kai Zhang; Xu Wang; Ying Chen (Food Control, 2025)

Dietary prebiotics combined with iron supplementation: A two-pronged approach to reduce rice cadmium bioavailability - Rong-Yue Xue; Yao-Sheng Zhang; Jin-Feng Xi; Lei Zhou; Xin-Ying Lin; Tian-Wen Ye; Yu-Hang Bao; Dongmei Zhou; Hong-Bo Li (Food and Chemical Toxicology, 2025)

Galla Chinensis as an antiviral agent: Targeting Micropterus salmoides rhabdovirus infection - Jieying Yu; Mingzhu Liu; Qing Yu; Xiangmou Qin; Mingming Zhao; Ying Pan; Nijia Xue; Hao Wang; Songlin Li; Fei Ling; Gaoxue Wang; Shuyu Han; et al. (Fish & Shellfish Immunology, 2025)

Development of a three-directional isolation system for LNG storage tanks subjected to near-fault earthquakes - Jie-Ying Wu; Qian-Qian Yu; Xiang-Lin Gu; Tianhua Deng (Engineering Structures, 2025)

Cobalt-doped sunflower plate-derived porous carbon as a dual-functional cathode host for high-performance Li S batteries via synergistic confinement-catalysis - Ying Fang; Bin Yue; Lin Li; Yuqi Wang; Xinyu Yan; Jinxian Wang; Yang Su; Guixia Liu; Wensheng Yu; Xiangting Dong (Chemical Engineering Journal, 2025)

Effects of gum incorporation on the properties of sodium alginate-based composite hydrogel beads for encapsulating lactic acid bacteria - Ying-Ying Jing; Yun-Cheng Li; Yong-Qi Luo; Long-Hua Zou; Yuan-Mou Tang; Yu-Xi Lin; Fan-Bing Meng (Carbohydrate Polymers, 2025)

Pluvial flood warnings in a tidally influenced basin enhanced by rainfall–tide compound indicators: Taipei case study - Mei-Ying Lin; Wen-Yih Sun; Huei-Syuan Fu; Chih-Hsin Chang; Wei-Bo Chen; Chieh-Ju Wang; Hsuan-Wei Wang; Yi-Chiang Yu; Yen-Wei Li (Stochastic Environmental Research and Risk Assessment, 2025)

Histone H3K18 lactylation-dependent epigenetic activation of RUNX2 orchestrates PI3K/AKT oncogenic signaling in laryngeal squamous cell carcinoma - Daidi Fu; Xin Huang; Ying Lin; Feng Yu; Haiwei Wu (Journal of Molecular Histology, 2025)

Identification, characterization, and expression profiling of rice MADS-box transcription factor genes associated with fluroxypyr-meptyl and oxyfluorfen metabolism - Zhi Zhong Zhou; Nian Hua Teng; Jia Lin Liang; Ying Yu Zeng; Yi Zhuo Wang; Li Qing Zeng; Xiao Liang Liu; Xi Ran Cheng; Zhao Jie Chen (Genetica, 2025)

Simplified theoretical analyses of lagging Darcy flow and land subsidence in a groundwater pumping system of three horizontal layers: An elastic thin plate approach - Jun-Hong Lin; Chih-Yu Liu; Chien-Chung Ke; Ying-Fan Lin (Advances in Water Resources, 2025)

Impacts of Global Warming on Severe Drought in Northern Taiwan: A Future Projection Based on the Year 2021 - Shih‐Ming Huang; Tsung‐Yu Lee; Chuan‐Yao Lin; Yi‐Ying Lin; Huang‐Hsiung Hsu (International Journal of Climatology, 2025)
In 2021, Taiwan experienced its most severe drought in 56 years, resulting in substantial crop losses, estimated to be approximately NT$1.65 billion due to insufficient water in reservoirs. This study employed the pseudo‐global‐warming method to project changes in seasonal rainfall during future droughts in northern Taiwan using a high‐resolution (1 km) regional mesoscale model. The simulation was based on the severe drought event of 2021 and employed the Weather Research and Forecasting model driven by the global High‐Resolution Atmospheric Model under the Representative Concentration Pathway 8.5 scenario for the mid‐21st century (2040–2059). The modelling projections revealed significant variations in seasonal rainfall in northern Taiwan, exhibiting a pattern described as “dry season gets drier, wet season gets wetter.” Notably, a more than 40% decrease (increase) in spring (Mei‐yu season) rainfall was observed. During the dry season, rainfall intensity was expected to decrease significantly due to a reduction in heavy rain and an increase in light rain (±5%) in the rainfall intensity range, whereas the opposite trend was anticipated for the wet season. These findings indicate that changes in rainfall due to global warming will worsen drought conditions in northern Taiwan if a severe drought reoccurs, particularly affecting major reservoir watersheds such as the Feitsui Reservoir, which was projected to experience 13% annual and 50% spring rainfall reductions.

Real-world emissions and total output from fishing vessels in Taiwan - Po-Yen Chien; Chia-Hsiang Lai; Wu-Xing Chen; Chia-Hung Chen; Chia C. Wang; Amila Kasun Abeysinghe; Yi-Ching Lin; Tsai-Jung Yen; Hsiang-Ying Wu; Yu-Lun Tseng; Pei-Shih Chen; Yen-Ping Peng (Transportation Research Part D: Transport and Environment, 2025)

Salidroside improves bovine embryo quality by mitigating oxidative stress and regulating mitochondrial lipid metabolism - Li-Ying Liu; Xian-Feng Yu; Zhi-Chao Chi; Shu-Ming Shi; Tian Lan; Jia-Hui Leng; Jing-hang Li; Yu-Yan He; Lin-Yi Qu; Guan-Lin Jia; Ilkeun Kong; Ming-Jun Zhang; et al. (Theriogenology, 2025)

The influence of trees shade level on human thermal comfort and the development of applied assessment tools - Yu-Ying Wei; Ching-Yin Cheng; Tzu-Ping Lin (Landscape and Urban Planning, 2025)

Application of a thiophene-based conjugated polymer in the photocatalytic eradication of multidrug-resistant bacteria: Synergistic inactivation of MRSA via carboxyl capture and multi-pathway regulation - Ying Xu; Simiao Wang; Xinyu Yu; Yuncong Wang; Lin Han; Yu Wang; Haiyong Guo; Juan Du (Journal of Hazardous Materials, 2025)

Linking source-to-sink processes, organic matter composition, and oxygen consumption on a shallow passive margin shelf sustained by small mountainous rivers - Yu-Shih Lin; Chih-Lin Wei; Yuan-Pin Chang; Jih-Terng Wang; Shu-Ying Chuang; Liang-Chi Wang; James T. Liu; Hong-Chun Li; Chieh-Wei Hsu (Geochimica et Cosmochimica Acta, 2025)

Effects of ice-binding protein from Leucosporidium sp. AY30 (LeIBP) on physicochemical quality, myofibrillar protein and ice crystal morphology of largemouth bass during air freezing - Junde Ren; Feifei Hu; Farooq Muhammad; Lihui Hu; Tao Song; Maninder Meenu; Jie Lin; Ying Liu; Hosahalli S. Ramaswamy; Yong Yu (Food Research International, 2025)

Structure-function modulation of sodium caseinate: Insights from non-covalent reuterin binding - Mao-Cheng Sun; Jie-Ting Wang; Ying-Di Wang; Lin-Yu Hu; Shi-Qi Yu; Tiehua Zhang; Changhui Zhao (Food Chemistry, 2025)

Cobalt-embedded carbon nanotube-bridged hollow carbon cubes enabling electron/ion co-transport and catalytic conversion in lithium-sulfur batteries - Xinyu Yan; Bin Yue; Lin Li; Yuqi Wang; Ying Fang; Ye Li; Yang Su; Jinxian Wang; Wensheng Yu; Xiangting Dong (Chemical Engineering Journal, 2025)

Corrigendum to “Bromide-intercalated poly (triazine imide) as a dual-functional adsorbent for Sr(II) and Co(II) removal from aqueous solution: Contrasting mechanisms of ion exchange and coordination-driven immobilization” [Chem. Eng. J. 520 (2025) 166316] - Miaoling Chen; Yu Chen; Zhengyuan Zhou; Purui Lin; Minhua Su; Jiacheng Min; Kaimin Shih; Ying Zhou (Chemical Engineering Journal, 2025)

Mechanochemical synthesis of ZnO@TiO2 II heterojunction material: Photocatalytic degradation and antibacterial synergistic effect - Juan Pei; Xiaoling Wan; Mingxing Guo; Jialan Mi; Wei Wu; Ying Hong; Pei Hu; Ping Chen; Lin Chen; Siwei Xiang; Qianyu Zhang; Haichun Zeng; et al. (Chemical Engineering Journal, 2025)

Targeting cuproptosis by FDX1 in acetaminophen-induced liver injury - Yan Liu; Ying Yang; Baizhao Peng; Zhongyue Ou; Anna Zuo; Zihao Jiang; Chuanghai Wu; Hiu Yee Kwan; Ke Ma; Lin Yu; Xiaoshan Zhao (Chemico-Biological Interactions, 2025)

Two new withanolides from Physalis minima L - Li-Jie Zhang; Mei-Lin Peng; Shi-Ying Xu; Fu-Rui Wang; Lin-Lin Yu; Qin-Feng Zhu; Shang-Gao Liao; Guo-Bo Xu (Natural Product Research, 2025)

Ribociclib derivative Rib-CA suppresses breast cancer progression via p53-dependent apoptosis - Mengwei Song; Ying Zhou; Xudong Yu; Boyu Zhang; Sen Wang; Kadirya Asan; Zihao Yang; Haiyan Lin; Jian Wang; Xiaoxue Song; Yongyuan Jiang; Si Chen; et al. (Toxicology and Applied Pharmacology, 2025)

Chemical constituents isolated from leaves of seashore plant Aglaia rimosa - Jing-Ru Weng; Jui-Hsin Su; Ping-Jyun Sung; Wei-Yu Lin; Zhen-Hong Han; You-Ying Chen; Chun-Lin Chen (Phytochemistry Letters, 2025)

Discovery of a new 1-monoglyceride from Streptomyces albogriseolus JM128 symbiotic with Lendenfeldia sponge - Yun-Ting Zeng; Chia-Ching Liaw; Yu-Chi Lin; Su-Ying Chien; You-Ying Chen; Li-Guo Zheng; Chih-Yin Huang; Hsi-Wen Sun; Ping-Jyun Sung (Phytochemistry Letters, 2025)

Carbon-nitrogen-phosphorus level regulation of potentially toxic elements and enzyme activities in paddy soil aggregates: Straw and organic fertilizer effects - Keqi Zhao; Wenbo Xiao; Nanyi Wang; Xiaobing Zhang; Ying Wang; Hua Peng; Jiachao Zhang; Anwei Chen; Renli Qi; Fangying Yu; Dan Wan; Lin Luo; et al. (Journal of Environmental Chemical Engineering, 2025)

Waste valorization into K-doped alumina catalysts via Al-MOF templates for efficient COS hydrolysis - Jia-Yin Lin; Jia-Yu Lee; Pei-Tzu Chang; Chih-Ying Wang (Journal of Environmental Chemical Engineering, 2025)

Surface oxygen vacancies-engineered spherical bismuth molybdate: Enhanced visible-light-driven photocatalytic activity for selective oxidation of benzyl alcohol under ambient conditions - Ying-Ying Xu; Wen-Yu Luo; Fei Wen; Yanfei Xu; Zhuo Li; Shanshan Liu; Ze-Long Sun; Xiaoxun Ma; Mingyue Ding; Lin-Yu Jiao (Chemical Engineering Journal, 2025)

Corrigendum to “Bromide-intercalated poly (triazine imide) as a dual-functional adsorbent for Sr(II) and Co(II) removal from aqueous solution: Contrasting mechanisms of ion exchange and coordination-driven immobilization” [Chemical Engineering Journal 520 (2025) 166316] - Miaoling Chen; Yu Chen; Zhengyuan Zhou; Purui Lin; Minhua Su; Jiacheng Min; Kaimin Shih; Ying Zhou (Chemical Engineering Journal, 2025)

Halogen-sulfur synergy in benzodithiophene-benzodithienedione conjugated polymers: Molecular design of high-performance photoelectrodes for metal anti-corrosion - Rui Ding; Jin-ying Li; Yi-wen Zhang; Hao-han Cao; Xiao Liu; Yu-han Wang; Ming-di Lei; Yu-lin Zhang; An-lan Ji; Yu-chen Zhang; Jie Liu; Tai-jiang Gui; et al. (Chemical Engineering Journal, 2025)

Waste cotton thread-derived SnO2 microfibres for enhanced sensing to trace triethylamine and application in meat freshness detection - Jing-Han Wang; Xiao-Na Zhang; Kuo Lin; Wen-Xiao Li; Bao-Yu Song; Fei Ye; Ying Fu; Ying-Ming Xu (Chemical Engineering Journal, 2025)

Dual-regulation of high-valence metals and oxygen vacancy enabled direct electrocatalytic amines oxidation via constructing a M6+-OV-Ni/Co3+ active pocket - Guosheng Wang; Jingzhou Wang; Wenyue Lin; Huilin Li; Haiyang Yu; Xiaohui Liu; Wenjie Zhang; Ying Cao; Xiantai Zhou; Can Xue (Chemical Engineering Journal, 2025)

Dopant alliance: K/Cu cooperative bonds lock structural stability in P2-type sodium cathodes - Yu Duan; Jia-xuan He; Zi-han Ma; Shu-wen Chen; Ying-ying Huang; Shuo Bao; Jin-lin Lu (Chemical Engineering Journal, 2025)

Association between air pollution and obstructive sleep apnea in terms of respiratory event frequency and lung-to-finger circulation time - Rachel Chien; Zhihe Chen; Peizheng Wang; Wen-Te Liu; Ying-Ying Chen; Yen-Ling Chen; Arnab Majumdar; Jiunn-Horng Kang; Kang-Yun Lee; Wun-Hao Cheng; Yi-Chih Lin; Cheng-Jung Wu; et al. (Atmospheric Pollution Research, 2025)

The Antimicrobial Peptide Tilapia Piscidin 4 Induced the Apoptosis of Bladder Cancer Through ERK/SIRT1/PGC-1α Signaling Pathway - Chun-Feng Chang; Po-Chih Chang; Yi-Chen Lee; Chieh-Yu Pan; Hui-Min Chang; Wan-Ju Wu; Mei-Ying Lin; Chung-Yi Chen; Zhi-Hong Wen; Chien-Hsing Lee (Probiotics and Antimicrobial Proteins, 2025)

Novel L-type chiral metal(II) complexes inhibit breast cancer growth through synergistic effects of anti-angiogenesis, anti-inflammatory, apoptosis induction and cuproptosis - Nan Jin; Bing-Bing Xu; Hong-Yu Lin; Bing-Li Jiang; Qiao-Ying Yang; Xiu-Ying Qin (Apoptosis, 2025)

Altererythrobacter guangdongensis sp. nov. and Tsuneonella sediminis sp. nov., two novel carotenoid-producing species isolated from tidal flat sediment - Huan-Huan He; Ying Wang; Bing-Yu Li; Chun-Yan Lu; Shuai Li; Zhuo-Huan Zheng; Liang Zhang; Wen-Hui Lian; Xin-Tao Luo; Hai-Wei Lin; Lei Dong; Wen-Jun Li (Systematic and Applied Microbiology, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Genomic analysis of Pseudoalteromonas sp. SD03 reveals its potential in chitin hydrolysis - Yu-Xuan Jiang; Wen-Yue Xu; Hui Liu; Si-Qi Lin; Sha-Sha Liu; Xi-Ying Zhang; Yan-Ru Dang (Marine Genomics, 2025)

Quantitative prediction and mechanistic insights into Cu(II) transport in kaolinite-coated sand columns affected by ferrihydrite nanoparticles - Lijuan Zeng; Guining Lu; Feng Jiang; Ying-Jie Zhang; Xiaohu Jin; Weilin Huang; Yu-Jung Lin; Jyh-Fu Lee; Xiaoyun Yi; Zhi Dang (Journal of Hazardous Materials, 2025)

Fundamental study of horizontal wind velocity effect on PM2.5 and PM10 sampling accuracy of low-Cost sensors - Yi-Ming Lee; Thi-Cuc Le; Ying-Chang Chen; Gung-Hwa Hong; Guan-Yu Lin; Chuen-Jinn Tsai (Journal of Aerosol Science, 2025)

Bromide-intercalated poly (triazine imide) as a dual-functional adsorbent for Sr(II) and Co(II) removal from aqueous solution: Contrasting mechanisms of ion exchange and coordination-driven immobilization - Miaoling Chen; Yu Chen; Zhengyuan Zhou; Purui Lin; Minhua Su; Jiacheng Min; Kaimin Shih; Ying Zhou (Chemical Engineering Journal, 2025)

Membrane technology for microplastic removal: Microplastic occurrence, challenges, and innovations of process and materials - Zhuoran Lin; Xingyu Hu; Hongjun Lin; Genying Yu; Liguo Shen; Wei Yu; Bisheng Li; Leihong Zhao; Mingyi Ying (Chemical Engineering Journal, 2025)

Synergistic treatment of respiratory syncytial virus induced pneumonia by multifunctional Baicalin-Resveratrol self-assembled nanomedicine - Chenqi Chang; Yu Zheng; Chang Lu; Ying Ma; Liang Wu; Yunyu Zhang; Lili Lin; Liang Guo; XiuZhen Chen; Linwei Chen; Jianming Cheng; Rui Chen (Chemical Engineering Journal, 2025)

Full-scale studies are closer to reality than lab-scale ones: Tertiary treatment constructed wetlands maintain robust removal capability for pharmaceuticals and personal care products in cold weather conditions - Jiaxi Wang; Beibei Ye; Xia Yu; Ruiqi Yan; Hui Lin; Ying Man; Qian Sui (Bioresource Technology, 2025)

Isolation and functional identification of Jasmonate resistant 1, a Jasmonic acid isoleucine-conjugating enzyme in Catharanthus roseus - Aikun Pan; Haiqiao Gao; Ying Lin; Bingrun Yang; Chunhao Chang; Zhiwen Liu; Yanyan Wang; Zhaoxia Jin; Fang Yu (Journal of Plant Research, 2025)

Butenolide synergises with vancomycin to eradicate pre-formed biofilm of Staphylococcus aureus by interfering with energy-associated metabolism - Dai-Xin Hu; Jinyou Liang; Jing Yan; Zhi-Wen Ma; Hai-Lin Li; Ying Xu; Yu Zhang; Qi Yin (Biofouling, 2025)

Whole-genome resequencing-based assessment of genomic diversity and selection signatures in Rhipicephalus microplus from Shaanxi, China - Yi-yao Mou; FU-wen Wang; YU-kun Kang; Ya-qing Li; YU-ying Yang; Tian-yuan Liu; Chu-zhao Lei; Qing Lin (Veterinary Parasitology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Impact of sodium dithionite salinity stress on hydrolysis of urea and total nitrogen removal in textile printing wastewater: Insights from anoxic-oxic-anoxic process - Faheem Ahmed Ghori; Ying Wu; Xumeng Lin; Jintao Yu; Hong Chen; Abdul Khalique Jhatial; Qifan Zhou; Mohmadarslan Kutubuddin Sadannavar; Gang Xue (Process Safety and Environmental Protection, 2025)

Adaptive fluoride removal across concentration scales: Potential roles of microbial and acicular gypsum interactions in nitrogen and phosphate cycling - Ying-Liang Yu; Wei-Han Lin; Rao Y. Surampalli; Ssu-Ching Chen; Chih-Ming Kao (Journal of Hazardous Materials, 2025)

A critical need to control thallium contamination in aquatic ecosystem for the age of low carbon - Juan Liu; Wenhuan Yuan; Yu Shi; Yanyi Liu; Pei Li; Wanpeng Chen; Xuan Zeng; Ying Li; Ke Lin; Yinyin Lu; Haiyao Hu; Jin Wang (Journal of Hazardous Materials, 2025)

Fate, transport, and plant uptake of ricinine in soils amended with castor cake organic fertilizer - Ya-Hui Chuang; Kai-Xuan Zheng; Siu Chun Wong; Yu-Min Tzou; Sichao Wang; Shiou-Ruei Lin; Hsiao-Ying Yang; Chinn-Yuan Fu; Jerry J. Wu; Cheng-Hua Liu (Journal of Hazardous Materials, 2025)

Dual-emission fluorescent probe with sequential two-step ESIPT activation mechanism for selective hydrazine detection and multifunctional applications - Hanxun Zou; Guoming Lin; Yuxuan Bao; Jie Liang; Yunyun Li; Lifeng Cai; Han-Ying Wu; Fan Yang; Hang Chen; Xiuchun Lin; Yi-Hong Xiao; Lei Yang; et al. (Journal of Hazardous Materials, 2025)

Sustainable remediation of butyl xanthate-contaminated mine wastewater by combining emergent macrophyte Cyperus alternifolius with a versatile bacterial isolate - Qi Liu; Yao-Yao Ye; Sha Yang; Cheng-Yu Cui; Huan Du; Jin-Cheng Ye; Ji-Liang Cheng; Rui-Wen Hu; Lei Xiang; Bai-Lin Liu; Yan-Wen Li; Quan-Ying Cai; et al. (Journal of Hazardous Materials, 2025)

Thick polyethylene films lessen pollution footprint while highlighting environmental merit and maize yielding in drylands - Xiao-Bin Xiong; Peng-Yang Wang; Ze-Ying Zhao; Zi-Yu Han; Yuan Song; Ying Zhu; Yi-Bo Wang; Jin-Lin Zhang; Xu-Sheng Guo; Xiao-Feng Zhang; Xiao-Yu Lu; You-Cai Xiong (Journal of Environmental Management, 2025)

CCN1 Is a Therapeutic Target for Reperfused Ischemic Brain Injury - Gilbert Aaron Lee; Yu-Wei Chang; Jing-Huei Lai; Tzu-Hao Chang; Shiu-Wen Huang; Chih‑Hao Yang; Ting-An Shen; Wan-Li Lin; Ying-Chieh Wu; Li-Wen Tseng; Sung-Hui Tseng; Yung-Chieh Chen; et al. (Translational Stroke Research, 2025)

Astrocytic P2X7 receptor in retrosplenial cortex drives electroacupuncture analgesia - Wei Zhao; Si-Le Liu; Si-Si Lin; Ying Zhang; Chang Yu (Purinergic Signalling, 2025)

Enhanced Hair Growth Through Transdermal Delivery of Bacopa Monnieri Extract Using a Needle-Free Supersonic Atomizer - Yu-Chiuan Wu; Yi-Ping Lin; Ching-Yi Chang; Hsia-Ying Cheng; Tien-Huei Chu; Chien-Chih Chen; Shyh-Ming Kuo (Journal of Medical and Biological Engineering, 2025)

Associations of Metal Mixtures with Lipid Profiles: Exploring the Mediating Role of Testosterone in a Cross-Sectional Study - Sencai Lin; Ying Yang; Junxiu He; Sihan Hu; Yu Bao; Xiaoting Ge; Xiaobo Yang (Biological Trace Element Research, 2025)

Exploring possible ancient applications of perilla: evidence from 3 million fruit remains from Han Dynasty tombs in China - Yun-Jun Bai; Ming Jiang; Xue-Ping Wei; Zhi-Jun Zhao; Xin-Ying Zhou; Hong-En Jiang; Tao Xie; Xiao-Lin Li; Yu-Yang Zhao; Xue Yan; Meng Cheng; Lu-Qi Huang; et al. (Science Bulletin, 2025)

Correlation of ferritin autophagy mediated by NCOA4 in type 2 diabetes with nonalcoholic fatty liver: Thermal radiation biomedical imaging testing - Wen-Yu Xue; Lei Xue; Jin-Suo Xue; Ying Jin; Lin-Jing Fan (Journal of Thermal Biology, 2025)

Tetraphenylethene-based covalent organic polymers with tunable Electrochemiluminescence for ultrasensitive detection of tetracycline - Ziqi Lian; Zhoumei Lin; Yu Wang; Li Tan; Wenjing Gao; Yuchan Liu; Huizhen Ma; Junqiang Luo; Chenyao Chen; Wanzhen Chen; Rongkai Ye; Ying Ma; et al. (Food Chemistry, 2025)

Infrared Laser Stimulation of Purkinje Cells Primarily Depends on TRP Channel Activation - Bin-Bin Dong; Chen Wang; Wan-Qi Huang; Yu-Peng Bian; Jun Liu; Wei Chen; Lin Zhou; Ying Shen; Luxi Wang (Neuroscience Bulletin, 2025)

Reversing Neuronal Klotho Dysfunction–Mediated Diabetic Neuropathy Through 16:8 Intermittent Fasting - Ying-Shuang Chang; Yu-Yu Kan; Tzu-Ning Chao; Yi-Hsuan Chen; Yu-Lin Hsieh (Molecular Neurobiology, 2025)

Image-well solution for island aquifers with pumping, recharge, and complex coastlines - Ying-Fan Lin; Barret L. Kurylyk; Adrian D. Werner; Chih-Yu Liu; Cristina Solórzano-Rivas; Jun-Hong Lin (Advances in Water Resources, 2025)

Whole-genome sequences revealed genomic diversity and selection signatures of Dermacentor silvarum in Shaanxi, China - Yi-yao Mou; Meng-ke Lin; Yu-ying Yang; Yu-kun Kang; Ya-qing Li; Tian-yuan Liu; Chu-zhao Lei; Qing Lin (Veterinary Parasitology, 2025)

Searching for neutrinoless double-beta decay of 136 Xe with PandaX-4T - Shu Zhang; Zihao Bo; Wei Chen; Xun Chen; Yunhua Chen; Zhaokan Cheng; Xiangyi Cui; Yingjie Fan; Deqing Fang; Zhixing Gao; Lisheng Geng; Karl Giboni; et al. (Science Bulletin, 2025)

Three new sesquiterpenes with cytotoxic activity from Croton tiglium - Wen-Ying Zhou; Xiao-Xiao Zheng; Yang-Mei Ou; Yang-Lin Ou; Hong-Yu Jang; Yu-Xin Peng; Yi-Yi Wang; Bi-Qing Zhao; Li Li (Phytochemistry Letters, 2025)

Assembly processes of rare and abundant microbial taxa are closely related to bacterial and fungal functionality during desert vegetation reestablishment - Zhouchang YU; Wei ZHANG; Pian DUO; Ying ZHANG; Xingfang TIAN; Lin SUN; Yuzheng GU; Junhong ZHANG; Jiaxing SONG; Ahejiang SAILIKE; Yujie LIANG; Rong FU; et al. (Pedosphere, 2025)

Upcycling electroplating sludge into nanoflower-structured Cu-MOFs for efficient Fenton-like degradation of organic dyes - Jia-Yin Lin; Si-Han Yu; Jun-Ren Shih; Tsai-Hsuan Hsieh; Chih-Ying Wang; Jen-Yu Huang; Nai-Wen Tsao (Journal of Water Process Engineering, 2025)

Tuning pH to motivate chain reaction of iron release with extracellular polymeric substances formation for long lasting Fe0-driven autotrophic denitrification - Ling Xiong; Binxue Song; Xumeng Lin; Ying Wu; Jintao Yu; Xiaonuan Wang; Huahan Huang; Yimei Cheng; Qifan Zhou; Gang Xue (Journal of Environmental Management, 2025)

Treatment of sulfamethoxazole-polluted wastewater coupled to lipid production by cyanobacteria-bacteria consortium in baffled photobioreactor - Ziqi YU; Guannan LIN; Ying LIU; Jian ZHANG (Journal of Environmental Chemical Engineering, 2025)

Spatial patterns of essential fish habitats in the western Taiwan coast - Yu-Jia Lin; Chien-Cheng Lai; Hsu-Sen Chen; Tsu-Chun Chen; Kuo-Shu Chen; Norhafiz Hanafi; Pei-Jie Meng; Ying-Chin Fang; Chiee-Young Chen; Hsin-Ming Yen; Meng-Hsien Chen (Estuarine, Coastal and Shelf Science, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Long-term characteristics of formaldehyde concentrations in four Chinese residences and estimation of annual average - Jin Ye; Zhiyuan Wang; Tao Yu; Wenbin Zhuang; Wenqing Lai; Lei Tian; Wenjun Leng; Ying Song; Shaodan Huang; Yinping Zhang; Cong Liu; Bencheng Lin (Building and Environment, 2025)

Chemical constituents from the aerial parts of Clematis peterae - Pan-Pan Yu; Meng-Ya Chen; Ya-Ru Wu; Yong-Qi Guo; Ying-Zhen Tang; Zi-Han Zhu; Yang-Yang Ma; Shi-Hui Qian; Nan Yao; Zhen-Lin Li (Biochemical Systematics and Ecology, 2025)

Degradable microplastics induce more soil organic carbon loss via priming effects: a viewpoint - Zhenyu Yang; Ying Sha; Amit Kumar; Zhiguo Yu; Junjie Lin; Yan Lei (Plant and Soil, 2025)

An EXPAR-CRISPR/Cas12a Assay for Rapid Detection of Salmonella - Wensen Lin; Mintao Huang; Hongjian Fu; Luxin Yu; Ying Chen; Lingwei Chen; Yanzhen Lin; Ting Wen; Xiaomin Luo; Yanguang Cong (Current Microbiology, 2025)

The underlying mechanism of Porcine Teschovirus 2 3Cpro antagonizing the NLRP3 inflammasome - Xin-yu Zhang; Yu-ying Li; Wei Chen; Yi-min Zhou; Lin Zhou; Lu-lu Xie; Yan-Qing Hu; Hai-xin Huang; Chen-chen Zhao; Yan Qin; Tian Lan; Wen-chao Sun (Veterinary Microbiology, 2025)

Newly isolated bacterium and arbuscular mycorrhizal fungus effectively reduce the root cadmium concentration and increase the root biomass of Ophiopogon japonicus - Lin Lin; Jin Li; Obey Kudakwashe Zveushe; Ying Han; Hengxing Zhang; Yu Qin; Victor Resco de Dios; Lei Zhou; Xiangyu Xi; Wei Zhang; Yulian Zhao; Amal Mohamed Omer; et al. (Journal of Hazardous Materials, 2025)

Single-step pyrolytic synthesis of ultra-microporous ammonialized biochar for carbon dioxide capture - Che-Jung Hsu; I-Lin Kuo; Hsing-Cheng Hsi; Su Shiung Lam; Ying-Pin Huang; Yu-Chieh Ting (Journal of Environmental Management, 2025)

Molecular mechanisms based on peripheral level of vanillin recognition in Orthaga achatina (Lepidoptera: Pyralidae) - Ting-Ting Yang; Yu Ma; Zheng Dai; Ying Li; Ji-Xiang Wang; Teng-Fei Bai; Merid Negash Getahun; George F.O. Obiero; Shuang-Lin Dong; Jin Zhang; Qi Yan (Insect Biochemistry and Molecular Biology, 2025)

Ratiometric fluorescence analysis of tetracycline by dual-ligand europium-based metal-organic framework - Yating Zhong; Keying Zhang; Xinru Wang; Haibo Liang; Ying Yu; Manli Guo; Yujuan Cao; Bixia Lin (Food Chemistry, 2025)

Low-frequency ultrasound-driven piezoelectric films repair neuro-immune circuits in diabetic wound healing - Chenyan Yu; Ying Hu; Xin Zhang; Kaixu Yu; Lang Chen; Wenqian Zhang; Shengming Zhang; Zhenhe Zhang; Ruiyin Zeng; Yuheng Liao; Yanzhi Zhao; Lin Gan; et al. (Chemical Engineering Journal, 2025)

Synergistic modulation of electronic structure in high entropy perovskite oxide for enhanced bifuntional oxygen evolution/reduction reactions and its mechanistic insights via in-situ analyses and density functional theory calculation - Thi Xuyen Nguyen; Chih-Heng Lee; Jun-Hong Sun; Chun-Kuo Peng; Wen-Hui Chu; Hamed Pourzolfaghar; Yu-Ru Lin; Muhammad Ghufron; Yuan-Yao Li; Yu-Hao Chang; Yan-Gu Lin; Hsin-Yi Tiffany Chen; et al. (Chemical Engineering Journal, 2025)

Effects of iron/aluminum mineral phases on soil organic carbon storage in different clay soils of subtropical acidic forests - Yi Li; Chen-chen Wang; Cui Zou; Yang Zhao; Pei Wei; Yu-ying Liu; Xiao-jun Zhao; Dun-mei Lin; Xian-jin He; Jun-long Huang; Jin-song Guo; Guang-yu Zhu (CATENA, 2025)

Enhancing occupant-centric ventilation control in airport terminals: A predictive optimization framework integrating agent-based simulation - Hao Tang; Juan Yu; Yang Geng; Xue Liu; Zujian Huang; Yuren Yang; Zhe Wang; Ying Chen; Borong Lin (Building and Environment, 2025)

Impact of Faba Bean (Vicia faba L.) Diet and Subsequent Withdrawal on GIFT Tilapia (Oreochromis niloticus) Muscle Quality - Guanling Xu; Wei Xing; Tieliang Li; Shibo Wei; Ying Zhang; Tingting Song; Huanhuan Yu; Lin Luo (Fishes, 2025)
To systematically evaluate FB’s effects on tilapia muscle quality, two distinct experimental phases are designed, the crispy texture development phase (0–16 weeks) and the crispy texture retention phase (17–24 weeks), which can determine the minimum faba bean (FB) feeding duration required to achieve optimal textural modification and can assess the persistence of improved textural properties following FB withdrawal, respectively. The results demonstrated that a 60% FB inclusion diet administered for 16 weeks did not adversely affect tilapia growth performance. Significant improvements in textural parameters, including hardness, springiness, chewiness, and shear force, were observed in FB-fed tilapia as early as 8 weeks, with these enhancements being maintained throughout the 16-week feeding period. These superior textural characteristics persisted during the subsequent retention phase following FB withdrawal. Microstructural analysis revealed that the 60% FB diet significantly enhanced muscle-fiber density while reducing fiber diameter in tilapia during the 8–16 week feeding period. These microstructural modifications persisted throughout the texture retention phase, maintaining significant differences compared to the control group. Serological analysis demonstrated the FB group elevated Superoxide dismutase (SOD) activity and reduced malondialdehyde (MDA) levels at 4 weeks, though these differences normalized thereafter. qRT-PCR showed the 60% FB clearly increased the expression of mstn at 8 weeks, while col1a-2 and myog expressions also obviously improved at 12 weeks. In summary, dietary 60% FB improved tilapia muscle crispiness by altering texture and microstructure via gene-expression regulation. The minimum duration was 8 weeks to achieve crispiness in tilapia by the 60% FB diet without adverse effects on growth, immunity, and hepatopancreas function. Furthermore, the crispy texture of tilapia fillets was maintained for at least 2 months following withdrawal of the 60% FB diet after 16 weeks of continuous feeding.

Surveillance and genetic diversity of bovine viral diarrhea virus in dairy herds across Taiwan - Fong-Yuan Lin; Hau-You Tzeng; Ching-Yu Tseng; Ruei-Sheng Tsai; Mami Oba; Tetsuya Mizutani; Yumiko Yamada; Hue-Ying Chiou; Shih-Te Chuang; Wei-Li Hsu (The Veterinary Journal, 2025)

Junceellolide Q, a new polyacetoxybriarane from the delicate sea whip octocoral Junceella fragilis - Yih-Gang Goan; Mingzi M. Zhang; Lun Kelvin Tsou; Zhi-Hong Wen; Chia-Ching Liaw; Yu-Chi Lin; Su-Ying Chien; Yu-Jen Wu; Jih-Jung Chen; Hai Nhat Do; Pei-Luen Jiang; Ping-Jyun Sung (Phytochemistry Letters, 2025)

Kuenenia-enriched hydroxyapatite granules enable stable high-rate nitrogen removal of high-strength food waste permeate in an EGSB-anammox system: Insights into granule performance and process scalability - Lan Lin; Wenzhao Zhao; Shen Cui; Ying Song; Yuanfan Zhang; Yu-You Li (Journal of Water Process Engineering, 2025)

The combination of metagenomics and metabolomics reveals the effect of nitrogen fertilizer application driving the remobilization of immobilization remediation cadmium and rhizosphere microbial succession in rice - Huan-Zhan Zhou; Bu-Qing Wang; Yong-Hong Ma; Yu-Ying Sun; Huan-Lin Zhou; Zhen Song; Yuan Zhao; Wei Chen; Jie Min; Jing-Wen Li; Tao He (Journal of Hazardous Materials, 2025)

Green solvent engineering of quasi-two-dimensional Dion-Jacobson perovskite films for efficient solar cells - Jiamin Xie; Haotian Wu; Lin Zhang; Jinyang Yu; Guofeng You; Ying Zhou; Gang Wu; Hongzheng Chen (Chemical Engineering Journal, 2025)

Regulation mechanisms of tea residue-based carbon dots in water-induced full-color emission and applications of visual ratio water sensors in organic solvents and WLEDs - Chao Yong; Ying Lei; Jian Du; Yinghui Liu; Yu Li; Fan Ye; Lin Xu; Guobin Ni; Shaowu Zhang (Analytica Chimica Acta, 2025)

The effect of ice-binding protein from Leucosporidium sp. AY30 (LeIBP) on physicochemical quality and microstructure of largemouth bass during frozen storage - Junde Ren; Feifei Hu; Maninder Meenu; Lihui Hu; Yuxiao Mao; Tao Song; Jie Lin; Ying Liu; Hosahalli S. Ramaswamy; Yong Yu (Innovative Food Science & Emerging Technologies, 2025)

Investigation on neutronics changes in tungsten granular blockage accident on VENUS-II light water reactor - Liang Chen; Wei Jiang; Zhao-Dong Xia; Fei Ma; Rui Yu; Hai-Yan Meng; Qi Zhou; Hong-Lin Ge; Yan-Bin Zhang; Xue-Ying Zhang (Annals of Nuclear Energy, 2025)

AI integration into wavelength-based SPR biosensing: Advancements in spectroscopic analysis and detection - Ying-Feng Chang; Yu-Chung Wang; Tsung-Yu Huang; Meng-Chi Li; Sin-You Chen; Yu-Xen Lin; Li-Chen Su; Kwei-Jay Lin (Analytica Chimica Acta, 2025)

Social conditions alter the growth, metabolic rate, behavioral traits, and food-shelter preferences in the juvenile qingbo Spinibarbus sinensis - Yu-Lin Zhang; Wen-Qian Zhou; Shi-Jian Fu; Lauren E. Nadler; Shaun S. Killen; Ke-Ying Zhou; Shi-Long Zheng; Cheng Fu (Behavioral Ecology and Sociobiology, 2025)

Late Quaternary slip rate of the Northern Margin Fault of the Huaizhuo Basin in the North China Block and its seismological implications - Lu-wei Li; Zhong-yuan Yu; Chun-miao Qiu; Wen-xuan Wang; Qian Zhao; Rong-ying Zheng; Yan-Lin Yang (Applied Geophysics, 2025)

Long-term exposure to ambient air pollution and the incidence of systemic lupus erythematosus - Lihong Ye; Ding Ye; Yu Qian; Jiayu Li; Bin Liu; Jiacheng Ying; Manli Wang; Hao Lin; Jing Guo; Xiaohui Sun; Zhixing He; Chengping Wen; et al. (Chemosphere, 2025)

LncRNAs: expanding horizons in drug development and disease treatment - Zhizhuo Wang; Junfeng Wang; Wenfei Wu; Chengyu Shi; Ying Wang; Yu Chen; Fangzhou Liu; Shanshan Xie; Aifu Lin (Science Bulletin, 2025)

GRACE/ML-based analysis of the spatiotemporal variations of groundwater storage in Africa - Kuiyuan Ding; Xiaowei Zhao; Jianmei Cheng; Ying Yu; Yiming Luo; Joaquin Couchot; Kun Zheng; Yihang Lin; Yanxin Wang (Journal of Hydrology, 2025)

Inheritance of Cry2Ab2 resistance in two Helicoverpa zea (Lepidoptera: Noctuidae) populations resistant to single- and dual-Bacillus thuringiensis proteins - Fangneng Huang; Wenbo Yu; Graham P. Head; Ying Niu; Caroline Sakuno; Shucong Lin; Tiago Silva; Bhavana Patla (Journal of Invertebrate Pathology, 2025)

Microplastics-exposure experience aggravates the accumulation of diarrhetic shellfish toxins (DSTs) in thick-shell mussel Mytilus coruscus through impairing detoxification processes - Kuan-Kuan Yuan; Ying-Ying Yu; Yu-Jie Liu; Xiu-Lin Yang; Yan-Hang Mo; Wei Shi; Guang-Xu Liu; Hong-Ye Li; Wei-Dong Yang (Journal of Hazardous Materials, 2025)

High performance catalyst CoNP for efficient electrochemical production of hydrogen peroxide - Ko-Shan Ho; Kuan-Ying Hung; Yu-Lin Hsiao; Hsiu-Chung Tu (Journal of Environmental Chemical Engineering, 2025)

Gelation improvement of low-salt Chinese shrimp (Fenneropenaeus chinensis) surimi gel by L-arginine - Yue Liu; Lin-Da Zhang; Ying-Rui Wang; Tian-Qi Zhou; Yu-Qiao Wang; Jia-Nan Yan; Bin Lai; Ce Wang; Hai-Tao Wu (Food Chemistry, 2025)

Insight into volatile metabolites and key odorants in black teas processed from Jianghua Kucha tea germplasm (Camellia sinensis var. assamica cv. Jianghua) - Ying-Lin Zhu; Wei-Xuan Li; Yu-Hui Zhang; Han Yan; Long-Yu Guo; Yue Zhang; Hai-Peng Lv; Ling-Hong Zhou; Zhi Lin; Wen-Liang Wu; Yin Zhu (Food Chemistry, 2025)

An efficient fungi-biochar-based system for advancing sustainable management of combined pollution - Ying Xia; Minghui Deng; Tao Zhang; Junjun Yu; Xinda Lin (Environmental Pollution, 2025)

Research landmarks on the 60th anniversary of Epstein-Barr virus - Lan-Yi Zhong; Chu Xie; Le-Le Zhang; Yan-Lin Yang; Yuan-Tao Liu; Ge-Xin Zhao; Guo-Long Bu; Xian-Shu Tian; Zi-Ying Jiang; Bo-Yu Yuan; Peng-Lin Li; Pei-Huang Wu; et al. (Science China Life Sciences, 2025)

RGS22 maintains the physiological function of ependymal cells to prevent hydrocephalus - Xue Pang; Lin Gu; Qiu-Ying Han; Jia-Qing Xing; Ming Zhao; Shao-Yi Huang; Jun-Xi Yi; Jie Pan; Hao Hong; Wen Xue; Xue-Qing Zhou; Zhi-Hui Su; et al. (Science China Life Sciences, 2025)

Digital transformation of mental health therapy by integrating digitalized cognitive behavioral therapy and eye movement desensitization and reprocessing - Ju-Yu Wu; Ying-Ying Tsai; Yu-Jie Chen; Fan-Chi Hsiao; Ching-Han Hsu; Yen-Feng Lin; Lun-De Liao (Medical & Biological Engineering & Computing, 2025)

Role of MFN2 in bovine embryonic development and the mitigation of ER stress - Shu-Ming Shi; Bing Hu; Zhi-Chao Chi; Lin-Yi Qu; Li-Ying Liu; Yu-Yan He; Guan-Lin Jia; Jing-Hang Li; Ilkeun Kong; Yong-Xun Jin; Xian-Feng Yu (Animal Reproduction Science, 2025)

Knocking Down HN1 Blocks Helicobacter pylori-Induced Malignant Phenotypes in Gastric Mucosal Cells and Inhibits Gastric Cancer Cell Proliferation, Cytoskeleton Remodeling, and Migration - Ying Huang; Xiaofei Wang; Hao Liu; Xiangkun Meng; Hua Yin; Ruirui Hou; Wan Lin; Xu Zhang; Jun Ma; Xiaoxu Zhang; Feixiong Zhang; Yu Miao (Biochemical Genetics, 2025)

Recent progress on triterpenoid derivatives and their anticancer potential - Zi-Xuan Zhao; Qiong-Yu Zou; Ying-Hong Ma; Susan L. Morris‐Natschke; Xiang-Yuan Li; Lin-Chun Shi; Guo-Xu Ma; Xu‐Dong Xu; Mei‐Hua Yang; Zi-Jian Zhao; Yuan-Xiang Li; Jing Xue; et al. (Phytochemistry, 2025)

Fates of bioactive compounds and antioxidant activities of red pitaya pulp upon in vitro gastrointestinal digestion - Xian Lin; Xiangyu Li; Ying Huang; Jing Wen; Yuanshan Yu; Daobang Tang; Baojun Xu; Yujuan Xu (Food Research International, 2025)

Research progress of electrospinning in food field: A review - Fa-Lin Sun; Ming-Yue Zhao; Yue Li; Zhi-Ying Li; Xiu-Jun Li; Nuo Wang; Bo-Wen Hu; Hao-Yu Xue; Min Zhao; Jin-Long Tian (Food Hydrocolloids, 2025)

Flexural behavior of reinforced concrete beams at low temperatures - Gu Xiang-Lin; Wu Jie-Ying; Yu Qian-Qian; Liu Shuang; Huang Qing-Hua (Engineering Structures, 2025)

Mitochondria-targeted delivery of zinc-coordinated resveratrol nanoparticles rescues the osteogenic potential of periodontal ligament stem cells compromised by inflammation for periodontal wound healing - Yu-Jie Tan; Xuan Li; Wen-Jie Zhang; Yu-Meng Cao; Jie-Kang Zou; Lin Jing; Dian Gan; Yu-Zhe Chen; Mei Xu; Ying An; Fa-Ming Chen; Xiao-Tao He; et al. (Chemical Engineering Journal, 2025)

Three-dimensional Heterogeneity and Intrinsic Plasticity of the Projection from the Cerebellar Interposed Nucleus to the Ventral Tegmental Area - Chen Wang; Si-Yu Wang; Kuang-Yi Ma; Zhao-Xiang Wang; Fang-Xiao Xu; Zhi-Ying Wu; Yan Gu; Wei Chen; Ying Shen; Li-Da Su; Lin Zhou (Neuroscience Bulletin, 2025)

CircHAT1 regulates the proliferation and phenotype switch of vascular smooth muscle cells in lower extremity arteriosclerosis obliterans through targeting SFRS1 - Xian-ying Huang; Fang-yong Fu; Kai Qian; Qiao-li Feng; Sai Cao; Wei-yu Wu; Yuan-lin Luo; Wei-jie Chen; Zhi Zhang; Shui-chuan Huang (Molecular and Cellular Biochemistry, 2025)

The link between eye movements and cognitive function in mild to moderate Alzheimer’s disease - Xiao-ting Ma; Lin-lin Yao; Shan-wen Liu; Xiao-fen Weng; Run-ying Bao; Yi-fan Yang; Yi-feng Li; Yan-yun Sun; Dan Xu; Zhen-yu Jia; Hua Hu (Experimental Brain Research, 2025)

Construction of Zinc-based metal-organic frameworks for visual ratiometric fluorescence detection of tetracycline - Yating Zhong; Haocheng Gao; Jingqi Yang; Xinru Wang; Ying Yu; Yujuan Cao; Manli Guo; Bixia Lin (Analytica Chimica Acta, 2025)

New insights into the stages of cadmium remediation in ryegrass enhanced by kitchen compost-derived dissolved organic matter: Activation, absorption, and storage - Bing Kou; Lin Huo; Minyi Cao; Kunlong Hui; Wenbing Tan; Ying Yuan; Yu Jiang (Science of The Total Environment, 2024)

Environmental contamination and risks of organic UV filters: Source, discharge, analytical methods and implications for ecological and human health - Yue-hong Sun; Heng-Yu Wu; Feng-Qi Xie; Jia-Ru Ma; Qin-Lin Tang; Yan-Fen Chen; Hao Li; You-Sheng Liu; Guang-Guo Ying (Science of The Total Environment, 2024)

Community prevention and standardized clinical treatment jointly improve cancer outcome: Real-world evidence from an esophageal cancer patient cohort study - Ji Ke; Fangfang Liu; Wei Yang; Ruiping Xu; Lei Chen; Wenlei Yang; Yu He; Zhen Liu; Bolin Hou; Liqun Zhang; Miaoping Lin; Lixin Zhang; et al. (Science Bulletin, 2024)

A TT1–SCE1 module integrates ubiquitination and SUMOylation to regulate heat tolerance in rice - Hong-Xiao Yu; Ying-Jie Cao; Yi-Bing Yang; Jun-Xiang Shan; Wang-Wei Ye; Nai-Qian Dong; Yi Kan; Huai-Yu Zhao; Zi-Qi Lu; Shuang-Qin Guo; Jie-Jie Lei; Ben Liao; et al. (Molecular Plant, 2024)

Identification of BpEXP family genes and functional characterization of the BpEXPA1 gene in the stems development of Betula platyphylla - Yao Chi; Zihan Wang; Shizhong Chen; Lin Feng; Meiqi Zhou; Yang Li; Ying Yu; Caiqiu Gao; Chao Wang (Journal of Plant Physiology, 2024)

Interactions between microplastics and heavy metals in leachate: Implications for landfill stabilization process - Jiabao Chen; Lin Huo; Ying Yuan; Yu Jiang; Hui Wang; Kunlong Hui; Yanjiao Li; Zekai Huang; Beidou Xi (Journal of Hazardous Materials, 2024)

Synthesis of cholesterol analogues and comparison on their effect on plasma cholesterol with β-Sitosterol - Hanyue Zhu; Longjian Chen; Zi-Xing Chen; Huiqi Lin; Jianhui Liu; Erika Kwek; Ka Ying Ma; Wensen He; Guoxin Wang; Zhen-Yu Chen (Food Chemistry, 2024)

Deep insights into the assembly mechanisms, co-occurrence patterns, and functional roles of microbial community in wastewater treatment plants - Zi-Yan Wei; Min Feng; Ding-Xi Zhang; Cheng-Ying Jiang; Ye Deng; Zhu-Jun Wang; Kai Feng; Yang Song; Nan Zhou; Yu-Lin Wang; Shuang-Jiang Liu (Environmental Research, 2024)

The effect of paeoniflorin on the rewarding effect of methamphetamine and the associated cognitive impairment in mice - Xin-shuang Gong; Hai-xing Wang; Xiang-dong Yang; Zhao-ying Yu; Shu-jun Lin; Zhi-ting Zou; Jia-nan Lv; Li-yin Qian; Yu-er Ruan; Zi-zhen Si; Yi Zhou; Yu Liu (Metabolic Brain Disease, 2024)

Unveiling the common laws of extracellular polymeric substances (EPS) properties on short-chain fatty acids production from sludge by EPS disintegration pretreatment - Xi-qi Li; Zhe Yu; Zhen Lin; Ying-ke Fang; Qi Sun; Kan Chen; Ai-jie Wang; Wen-zong Liu (Science of The Total Environment, 2024)

Operando-reconstructed polyatomic ion layers boost the activity and stability of industrial current–density water splitting - Yingxia Zhao; Ying Wu; Qunlei Wen; Danji Huang; Ruoou Yang; Haozhi Wang; Yingying Xu; Ming Sun; Youwen Liu; Jiakun Fang; Tianyou Zhai; Lin Yu (Science Bulletin, 2024)

Mirids secrete a TOPLESS targeting protein to enhance JA-mediated defense and gossypol accumulation for antagonizing cotton bollworms on cotton plants - Yu-Pei Mu; Dian-Yang Chen; Yu-Jie Liu; Ming-Yu Zhu; Xian Zhang; Yin Tang; Jia-Ling Lin; Mu-Yang Wang; Xiao-Xia Shangguan; Xiao-Ya Chen; Chengshu Wang; Ying-Bo Mao (Molecular Plant, 2024)

Impacts of shellfish and macroalgae mariculture on the seawater carbonate system and air-sea CO 2 flux in Haizhou Bay, China - Jia-Hui Zhou; Ying-Zi Guo; Xu Zhao; Jin-Chen Yu; Jin Zhou; Jun Lin; Hong Huang (Marine Environmental Research, 2024)

Impact of photoaging on the chemical and cytotoxic properties of nanoscale zeolitic imidazolate framework-8 - Yi-Chun Chen; Kun-Yi Andrew Lin; Ying-Chu Chen; Yan-Yu Hong; Yu-Fang Hsu; Chia-Hua Lin (Journal of Hazardous Materials, 2024)

Tracing potentially toxic elements in button mushroom cultivation and environmental implications: Insights via stable lead (Pb) isotope analysis - Xun Liu; Junjie Yu; Xueping Lu; Manli Yang; Yazhou Liu; Hui Sun; Ying Ni; Guo Lin; Chuansheng Wu; Jun Tang (Journal of Cleaner Production, 2024)

Applying kitchen compost promoted soil chrysene degradation by optimizing microbial community structure - Bing Kou; Lin Huo; Minyi Cao; Tingqiao Yu; Yuman Wu; Kunlong Hui; Wenbing Tan; Ying Yuan; Xiaoli Zhu (Journal of Environmental Management, 2024)

Insight into simultaneous urea hydrolysis and total nitrogen removal in textile printing wastewater: Focus on the impact of sodium sulfate salinity - Faheem Ahmed Ghori; Ying Wu; Xumeng Lin; Yueling He; Qianjiang Yu; Hong Chen; Gang Xue (Journal of Environmental Management, 2024)

Multi-omics integration analysis: Tools and applications in environmental toxicology - Chengcheng Shi; Lin Cheng; Ying Yu; Shuangshuang Chen; Yubing Dai; Jiajia Yang; Haijun Zhang; Jiping Chen; Ningbo Geng (Environmental Pollution, 2024)

High-contrast electrochromic coatings and devices for health assurance, visual comfort and energy-saving in buildings - Chung-Wen Kuo; Han-Yu Chen; Chen-Hao Yeh; Yuan-Chung Lin; Jeng-Kuei Chang; Pei-Ying Lee; Tzi-Yi Wu (Energy and Buildings, 2024)

An unsaturated chain carbonate additive contributing to high-performance LiFePO4//graphite battery at broad temperature range - Xin-Lin Zhang; Bin Dong; Yi Jin; Jia-Shun Song; Li Li; Jia-Yu Wang; Yu-Ying Zhu; Yan-Yun Sun (Chemical Engineering Journal, 2024)

Electronic effect in bromide-modified noble metal catalysts promotes highly stable and selective hydrogenation - Xintai Chen; Mengqi Yang; Qiying Liu; Xiaoling Mou; Linbin Ying; Yu Meng; Ronghe Lin; Yunjie Ding (Chemical Engineering Journal, 2024)

A wearable exhaled breath condensate (EBC) collector with controllable condensation microfluidics and a branched hydrophilic film - Chun-Hao Chang; Ying-Hsuan Yu; Hsiu-Pen Lin; Ping-Hsien Tsou; Yaw-Kuen Li; Bor-Ran Li (Chemical Engineering Journal, 2024)

Differential response of soil bacteria and fungi to carbon and respiration components in abandoned grasslands on the Loess Plateau, China - Xingfang Tian; Ying Zhang; Yujie Liang; Rong Fu; Lin Sun; Zhouchang Yu; Jiayi Shi; Ahejiang Sailike; Hongjian Hao; Wei Zhang (Plant and Soil, 2024)

Ultrasensitive mass spectrometric quantitation of apurinic/apyrimidinic sites in genomic DNA of mammalian cell lines exposed to genotoxic reagents - Chen-Yu Xue; Ya-Hong Liu; Yue Yu; Ying Liu; Ying-Lin Zhou; Xin-Xiang Zhang (Analytica Chimica Acta, 2024)

Rational design of stable Cu and AuCu nanoparticles for investigations of size-enhanced SERS applications - Kuan-Wen Liu; Pei-Yu Sie; Jing-Yin Huang; Hsi-Ying Chen; Yi-Lun Chen; Yu-Ching Lin; Mei-Yi Liao (Analytica Chimica Acta, 2024)

Soluble Epoxide Hydrolase Inhibitor Ameliorates Olfactory Dysfunction, Modulates Microglia Polarization, and Attenuates Neuroinflammation after Ischemic Brain Injury - Chien-Fu Yeh; Tung-Yueh Chuang; Ming-Ying Lan; Yung-Yang Lin; Wei-Hao Huang; Yu-Wen Hung (Journal of Neuroimmune Pharmacology, 2024)

Visible-light-prompted photoelectrochemical sensors fabricated using Er3NbO7/P@g-C3N4/SnS2 nanocomposite for detecting mercury ion in environmental water samples - Abishek Jayapaul; Yu-Chien Lin; Ying-Chu Chen; Ting-Yu Liu; Ren-Jei Chung (Chemosphere, 2024)

An extended investigation on allele frequency of resistance to Bt maize in the southwestern corn borer and sugarcane borer (Lepidoptera: Crambidae) in the mid-south region of the United States - Fangneng Huang; Ying Niu; Qisheng Song; Scott Stewart; Blake Wilson; Graham Head; Sebe Brown; Wenbo Yu; Tiago Silva; Caroline Sakuno; Shucong Lin (Crop Protection, 2024)

A preliminary study of T-2 toxin that cause liver injury in rats via the NF-kB and NLRP3-mediated pyroptosis pathway - Shicong Zheng; Haonan Li; Hexuan Dong; Fang Qi; Bing Zhang; Qian Yu; Buyi Lin; Hong Jiang; Haoyu Du; Ying Liu; Jun Yu (Toxicon, 2024)

Quantifying city freight mobility segregation associated with truck multi-tours behavior - Yitao Yang; Yan Chen; Ying-Yue Lv; Xiang-Yu Jia; Xu-Jie Lin; Xiao-Yong Yan; Bin Jia; Ed Manley (Sustainable Cities and Society, 2024)

Combined effects of thermal environment and gene regulation on metabolic enzyme activities of major metabolic tissues in a winter-breeding amphibian - Chi-Ying Zhang; Hua-Li Hu; Yu Wang; Lin Zhang; Guo-Hua Ding (Journal of Thermal Biology, 2024)

Long-term ambient ozone exposure and childhood asthma, rhinitis, eczema, and conjunctivitis: A multi-city study in China - Zhao-Huan Gui; Zhan-Yu Guo; Yang Zhou; Shyamali Dharmage; Lidia Morawska; Joachim Heinrich; Zhang-Kai Cheng; Hui Gan; Zhi-Wei Lin; Dong-Ying Zhang; Jing-Wen Huang; Li-Zi Lin; et al. (Journal of Hazardous Materials, 2024)

Unraveling the mechanism of selective dissolution in anthracite coal for enhanced permeability through sodium hypochlorite oxidation treatment - Yu Lu; Yili Kang; Zhigang Li; Ming Yue; Teng Zhang; Feng He; Chong Lin; Yue Hu; Ying Li; Zhenjiang You (Fuel, 2024)

The role of aroA and ppk1 in Aeromonas veronii pathogenicity and the efficacy evaluation of mutant strain AV-ΔaroA/ppk1 as a live attenuated vaccine - Jiahui Lu; Wan'e Ding; Jinming Wei; Hua Ye; Hui Luo; Yun Li; Ying Lin; Yongyao Yu; Jiayun Yao; Ronghua Wu (Fish & Shellfish Immunology, 2024)

Synergistic enhancement of UASB reactor for leachate treatment using Fe2O3 nanomodified pumice and ozone oxidation - Yu-Zhou Yang; Yong Zhang; Yu Zhan; Jia-Qi Liu; Chuan-Chuan Yan; Ying Zhang; Hua-Lin Zhang (Chemical Engineering Journal, 2024)

Sex-Specific Associations of Five Serum Essential Metal Elements with Thyroid Nodules in Euthyroid Adults: a Cross‑sectional Study - Qintao Ma; Ying Li; Genfeng Yu; Siyang Liu; Yuqi Jiang; Hualin Duan; Dongmei Wang; Yajun He; Xingying Chen; Nanfang Yao; Xu Lin; Heng Wan; et al. (Biological Trace Element Research, 2024)

Verification of Seasonal Prediction by the Upgraded China Multi-Model Ensemble Prediction System (CMMEv2.0) - Jie Wu; Hong-Li Ren; Jianghua Wan; Jingpeng Liu; Jinqing Zuo; Changzheng Liu; Ying Liu; Yu Nie; Chongbo Zhao; Li Guo; Bo Lu; Lijuan Chen; et al. (Journal of Meteorological Research, 2024)

Application of Multiple Geophysical Exploration Methods in the Exploration of Marine Sand Resources in the Northern Offshore Waters of the South China Sea - Gang Yu; Xichong Hu; Jie Fang; Ying Yang; Yongcong Zhang; Jinhui Lin; Jingyi Liu; Libing Qian (Journal of Marine Science and Engineering, 2024)
Marine sand, in addition to oil and gas resources, is the second-largest marine mineral resource. The rational development and utilization of marine sand resources are conducive to the growth of the marine economy. In the process of marketing marine sand in China, local authorities are required to delineate auctioned sand mining areas after a general survey, commonly referred to as preliminary exploration. Marine sand can be categorized into surface marine sand and buried marine sand. Buried marine sand deposits are buried beneath the sea floor, making it challenging to locate them due to their thin thickness. Consequently, there exist numerous technical difficulties associated with marine sand exploration. We conducted the preliminary research work in the waters off Guangdong Province of the South China Sea, employing a reduced drilling and identifying a potentially extensive deposit of marine sand ore. In this study, various geophysical methods such as sub-bottom profile survey, single-channel seismic survey, and drilling engineering were employed in the northern offshore waters of the South China Sea. As a result, two distinct marine sand bodies were delineated within the study area. Additionally, five reflective interfaces (R1, R2, R3, R4, and R5) were identified from top to bottom. These interfaces can be divided into five seismic sequences: A1, B1, C1, D1, and E1, respectively. Three sets of strata were recognized: the Holocene Marine facies sediment layer (Q4m), the Pleistocene alluvial and pluvial facies sediment layer (Q3al+pl), as well as the Pleistocene Marine facies sedimentary layer (Q3m). In total, two placers containing marine sand have been discovered during this study. We estimated the volume of marine sand and achieved highly favorable results of the concept that we are proposing a geologic exploration approach that does not involve any previous outcropping analogue study.

Benzo(a)pyrene promotes the malignant progression of malignant-transformed BEAS-2B cells by regulating YTH N6-methyladenosine RNA binding protein 1 to inhibit ferroptosis - Na Wang; Hong-qiang Chen; Yong Zeng; Yu Shi; Zhe Zhang; Jiang-ying Li; Shi-meng Zhou; Ya-wen Li; Shuang-wu Deng; Xue Han; Zi-yuan Zhou; Mao-lin Yao; et al. (Toxicology, 2024)

Ozone sensitivity regimes vary at different heights in the planetary boundary layer - Xin Li; Wenjie Wang; Suding Yang; Yafang Cheng; Limin Zeng; Xuena Yu; Sihua Lu; Ying Liu; Min Hu; Shaodong Xie; Xiaofeng Huang; Jun Zhou; et al. (Science of The Total Environment, 2024)

Diterpenoid alkaloids from Delphinium trichophorum - Shuai Huang; Jian-Zhu Wang; Yang-Li Pu; Yu-Yan Liu; Ying Chen; Lin Chen; Xian-Li Zhou (Phytochemistry, 2024)

Transitioning weathered oil fields towards new energy: A review on utilizing hydrogenotrophic methanogens for petroleum hydrocarbons remediation - Jiaping Zhou; Wei-Han Lin; Ying-Liang Yu; Cheng-Di Dong; Haibing Zhang; Zhongtao Hu; Chih-Ming Kao (Journal of Hazardous Materials, 2024)

Fe(II)-mediated Fe–N–P metabolism in an anammox-dominated system for enhanced nitrogen removal and Fe–P crystals (FePs) production - Biru Zhou; Lan Lin; Qian Zhang; Ying Wang; Zikun Zhang; Xiaoqing Xie; Wenzhi Cao; Yu-You Li; Yanlong Zhang (Journal of Cleaner Production, 2024)

Macrophage-Targeted multifunctional nanoparticles for detection and treatment of intraplaque hemorrhage - Haiyang Wang; Min Zheng; Yushi Chen; Long Cheng; Xiaotong Qi; Huilin Yu; Jianming Sun; Junjie Liu; Ruoyao Wang; Yaqin Hu; Tao Lin; Ying Zhang; et al. (Chemical Engineering Journal, 2024)

Synergistic structure engineering and electrochemical activation modulating vanadium oxide cathode toward superior zinc-ion storage - Kan Fang; Heng Zhang; Peng Chen; Hua-Yu Zhang; Zhan Wei; Ling Ding; Xiao-Ai Ye; Jiawang Liu; Yi-Lin Liu; Gui-Gen Wang; Hui Ying Yang (Chemical Engineering Journal, 2024)

Three-dimensional mixed-valence polyoxovanadates@polyaniline architecture towards high-performance rechargeable aqueous zinc-ion batteries cathode - Xue-Wei Liang; Yu-Ying Yang; Wen-Fei Di; Si-Yu Chen; Rui Zhang; Jisong Hu; Dunmin Lin; Yu Huo (Chemical Engineering Journal, 2024)

Convergent Neuroimaging and Molecular Signatures in Mild Cognitive Impairment and Alzheimer’s Disease: A Data-Driven Meta-Analysis with N = 3,118 - Xiaopeng Kang; Dawei Wang; Jiaji Lin; Hongxiang Yao; Kun Zhao; Chengyuan Song; Pindong Chen; Yida Qu; Hongwei Yang; Zengqiang Zhang; Bo Zhou; Tong Han; et al. (Neuroscience Bulletin, 2024)
The current study aimed to evaluate the susceptibility to regional brain atrophy and its biological mechanism in Alzheimer’s disease (AD). We conducted data-driven meta-analyses to combine 3,118 structural magnetic resonance images from three datasets to obtain robust atrophy patterns. Then we introduced a set of radiogenomic analyses to investigate the biological basis of the atrophy patterns in AD. Our results showed that the hippocampus and amygdala exhibit the most severe atrophy, followed by the temporal, frontal, and occipital lobes in mild cognitive impairment (MCI) and AD. The extent of atrophy in MCI was less severe than that in AD. A series of biological processes related to the glutamate signaling pathway, cellular stress response, and synapse structure and function were investigated through gene set enrichment analysis. Our study contributes to understanding the manifestations of atrophy and a deeper understanding of the pathophysiological processes that contribute to atrophy, providing new insight for further clinical research on AD.

Hinokione: an abietene diterpene with pancreatic β cells regeneration and hypoglycemic activity, and other derivatives with novel structures from the woods of Agathis dammara - Zheng Wang; Zhe-Wei Yu; Yi Zhang; Wen-Hui Wang; Xin-Yi Wu; Shun-Zhi Liu; Yan-Lin Bin; Bang-Ping Cai; Shi-Yan Huang; Mei-Juan Fang; Rong Qi; Ming-Yu Li; et al. (Journal of Natural Medicines, 2024)

Associations among global long interspersed nuclear element-1 DNA methylation, metal exposure, and chronic kidney disease - Yu-Mei Hsueh; Mei-Chieh Chen; Ying-Chin Lin; Chih-Yin Wu; Horng-Sheng Shiue; Sheng-Lun Hsu; Hsi-Hsien Chen; Ya-Li Huang (Archives of Toxicology, 2024)

Age-related alterations in vortex veins on indocyanine green angiography - Chen-Xi Cai; Shan-Shan Yu; Xiao-Mei Xiong; Bing-Qian Liu; Zhen-Qiang Lin; Qiang Wang; Jin-Li Cui; Ze-Hao Liu; Tao Li; Lin Lu; Ying Lin (GeroScience, 2024)
To determine age-related alterations in vortex veins in healthy subjects. A total of 228 healthy subjects (aged 4 to 86 years) were recruited and divided into four groups (G1, <21 years; G2, 21–40 years; G3, 41–60 years; and G4, 61–86 years). The clinical characteristics of the participants were recorded, and parameters including the number of vortex vein roots (NVVR), the central vortex vein diameter (CVVD), the mean root area of the vortex vein (MRAVV), and the weighted mean of the thickest branch diameter (WMTBD) were obtained by marking the vortex veins on indocyanine green angiography (ICGA). The NVVR in the age group over 60 years old was significantly lower than that in other age groups ( P < 0.05). The CVVD, MRAVV, and WMTBD of all age groups increased with increasing age ( P < 0.05). The NVVR was unevenly distributed among the quadrants ( P < 0.001). The proportions of type four vortex veins (complete systems including ampulla) and anastomotic branches of the vortex veins were significantly increased in elderly participants over 50 years of age ( P < 0.05). Subfoveal choroidal thickness was significantly correlated with age, NVVR, CVVD and MRAVV ( P < 0.05). This is the first study to reveal age-related alterations in vortex veins on ICGA in a healthy population. Aging may lead to partial vortex occlusion and residual vortex dilation. As age increases, anastomotic branches increasingly appear between the originally independent vortex veins. Translational relevance: Aging may lead to partial vortex occlusion and residual vortex dilation.

Three new chemical constituents of Senecio raphanifolius - Shu-Wen Huang; Huan He; Zhi-Qiang Li; Yu-Wei Wang; Yuan-Ying Fang; Yu-Lin Feng; Zhi-Feng Li; Qi Wang (Phytochemistry Letters, 2024)

Dimeric piperidinoquinoline alkaloids from the seeds of Chimonanthus salicifolius - Zhan-Peng Yu; Yu-Xia Wang; Li-Hong Hong; Ya-Lin Li; Jian-Fei Zhang; Mu Li; Ping Ying; Qiang Zheng; Ling-Yi Kong; Jian-Guang Luo (Phytochemistry Letters, 2024)

Construction and characterization of a novel Myr-OSADS-CIn micelle for enhanced stability and bioavailability of myricetin - Zhi-Yuan Nie; Xue-Ying Li; Ying-Ying Chen; Yuan-Yuan Deng; Dan-Dan Kuang; Yu-Lin Sun; Huan-Huan Xiao; Qiang-Ming Li; Jian-Ping Luo; Xue-Qiang Zha (Food Bioscience, 2024)

Enhanced sludge granulation and stable performance of an anammox expanded granular sludge bed (EGSB) reactor through the utilization of hydroxyapatite (HAP) particles - Lan Lin; Ying Song; Yanlong Zhang; Zibin Luo; Qian Li; Wenzhi Cao; Yu-You Li (Bioresource Technology, 2024)

Human Amniotic Epithelial Stem Cells Alleviate Autoimmune Premature Ovarian Insufficiency in Mice by Targeting Granulosa Cells via AKT/ERK Pathways - Xiaohang Ye; Yifeng Lin; Yanyun Ying; Xuezhi Shen; Feida Ni; Feixia Wang; Jianpeng Chen; Wei Zhao; Xiaoming Yu; Dan Zhang; Yifeng Liu (Stem Cell Reviews and Reports, 2024)
Autoimmune factors play an important role in premature ovarian insufficiency (POI). Human amniotic epithelial stem cells (hAESCs) have recently shown promising treatment effects on chemotherapy-induced POI. However, the therapeutic efficacy and underlying mechanisms of hAESCs in autoimmune POI remain to be investigated. In this study, we showed for the first time that intravenous transplantation of hAESCs could reside in the ovary of zona pellucida 3 peptide (pZP3) induced autoimmune POI mice model for at least 4 weeks. hAESCs could improve ovarian function and fertility, alleviate inflammation and reduce apoptosis of granulosa cells (GCs) in autoimmune POI mice. The transcriptome analysis of mice ovaries and in vitro co-cultivation experiments suggest that activation of the AKT and ERK pathways may be the key mechanism in the therapeutic effect of hAESCs. Our work provides the theoretical and experimental foundation for optimizing the administration of hAESCs, as well as the clinical application of hAESCs in autoimmune POI patients. Graphical Abstract

High dimensional proteomic mapping of bone marrow immune characteristics in immune thrombocytopenia - Feng-Qi Liu; Qing-Yuan Qu; Ying Lei; Qi Chen; Yu-Xiu Chen; Meng-Lin Li; Xue-Yan Sun; Ye-Jun Wu; Qiu-Sha Huang; Hai-Xia Fu; Yuan Kong; Yue-Ying Li; et al. (Science China Life Sciences, 2024)

Research on the rapid tissue breeding technology of the endangered plant Cibotium barometz (L.) J. Sm. - Qiaoling Yu; Wei Lin; Xingjian Yu; Ben Qin; Ying Liang; Fan Wei; Shuangshuang Qin; Kunhua Wei (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Distribution, risk evaluation, and source allocation of cesium and strontium in surface soil in a mining city - Jia-li Li; Chun-dan Gan; Xin-yue Du; Xue-ying Yuan; Wen-lin Zhong; Meng-qi Yang; Rui Liu; Xiao-yu Li; Hao Wang; Yu-liang Liao; Zheng Wang; Mu-cheng Xu; et al. (Environmental Geochemistry and Health, 2024)

Association among polydisperse aerodynamic size of bioaerosols, biodiversity and urbanization in kindergartens - Tzu-Hsien Lin; Ying-Hsiang Chou; Tzu-Yu Hsu; Chun-Hui Hung; Chane-Yu Lai (Chemosphere, 2024)

Global diversity of airborne pathogenic bacteria and fungi from wastewater treatment plants - Ying Wang; Wenwen Wang; Xuezheng Yu; Zixuan Wang; Ziyu Zhou; Yunping Han; Lin Li (Water Research, 2024)

Spatial distribution and assembly processes of bacterial communities in riverine and coastal ecosystems of a rapidly urbanizing megacity in China - Hebin Liang; Jin Huang; Yu Xia; Ying Yang; Yang Yu; Kai Zhou; Lin Lin; Xiaoyan Li; Bing Li (Science of The Total Environment, 2024)

Norditerpenoid alkaloids from Aconitum refractum var. circinatum as autophagy inducers - Mei-Zhen Ye; Zhen-Ling Wan; Hong-Yu Ruan; Yu-Qi Yang; Ying Chen; Lin Chen; Shuai Huang; Xian-Li Zhou (Phytochemistry, 2024)

A conductive and anti-freezing gelatin-PAA-based organic hydrogel (PC-OH) with high adhesion and self-healing activities for wearable electronics - Zhenglin Chen; Jiaqi Yang; Zhicheng Du; Jiansong Ji; Likun Zhang; Haifei Guan; Zhengyang Lei; Xiaopeng Zhang; Canhui Yang; Ying Zhu; Qianhui Sun; Lulu Xu; et al. (Chemical Engineering Journal, 2024)

Erratum to: Cholesterol homeostasis regulated by ABCA1 is critical for retinal ganglion cell survival - Jialiang Yang; Yuhong Chen; Tongdan Zou; Bai Xue; Fang Yang; Xiangzhou Wang; Yibo Huo; Boyun Yan; Yuxia Xu; Shiyu He; Yi Yin; Jing Wang; et al. (Science China Life Sciences, 2024)

Inflammation-Responsive Mesoporous Silica Nanoparticles with Synergistic Anti-inflammatory and Joint Protection Effects for Rheumatoid Arthritis Treatment - Ye-zhen Wu; Wen-yu Chen; Ying Zeng; Qi-lin Ji; Yue Yang; Xu-liang Guo; Xiu Wang (Pharmaceutical Research, 2024)

Assessment of PM2.5-associated mortality burden among the elderly: Insights into demographic, socio-economic, and geographic factors - Ayushi Sharma; Hsi-yu Hsiao; Jia-Yi Liu; Shih-Chun Candice Lung; Huey-Jen Su; Ching-Fen Shen; Nai-Tzu Chen; Pei-Chih Wu; Cheng-Yu Lin; Sheng-Fu Liang; Tain-Junn Cheng; Ta-Chien Chan; et al. (Air Quality, Atmosphere & Health, 2024)

Water addition but not reduction alters plant biomass–diversity relationship - Yan Yu; Josep Peñuelas; Jordi Sardans; Jiu‐ying Pei; Ge Li; Guo‐lin Liu; Jian‐Sheng Ye (Global Change Biology, 2024)
The relationship between plant aboveground biomass and diversity typically follows a unimodal pattern, showing a positive correlation in resource‐poor habitats and a negative correlation in resource‐rich environments. Precipitation is a crucial resource for both plant biomass and diversity in terrestrial ecosystems. However, the impact of precipitation changes on the relationship between plant biomass and diversity remains unclear. We conduct a water addition field experiment in a semiarid grassland and identify a unimodal relationship between plant biomass and species richness under ambient conditions. Water addition delays the declining phase of this unimodal curve and shift it upward compared to ambient conditions. Our meta‐analysis of water addition experiments conducted across major biomes worldwide (grassland, shrubland, desert, and forest) supports this finding, while water reduction does not alter the biomass–diversity relationship. Water addition increases biomass in all climate but only increases species richness in arid and semiarid climate. Similarly, water reduction decreases biomass in all climate but only reduces species richness in arid and semiarid climate. Species richness in dry subhumid and humid climate does not change significantly. Furthermore, our field experiment shows that water addition increases plant diversity while decreasing soil inorganic nitrogen levels. The increase in one resource, such as water, leads to the scarcity of another, such as nutrient, thus postponing the declining phase of the plant biomass–diversity relationship typically observed in resource‐rich habitats. Our research contributes to predicting the plant biomass–diversity relationship under changing precipitation conditions and highlights the complex interplay between water availability, nutrient level, and plant diversity.

Infection by virulent wMelPop Wolbachia improves learning and memory capacity in Drosophila melanogaster - Meng-Yan Chen; Dong Li; Zhi-Ning Wang; Feng-Zhen Xu; Yi-Wei Feng; Qiong-Lin Yu; Ying-Ying Wang; Shu Zhang; Yu-Feng Wang (Animal Behaviour, 2024)

Triclocarban and triclosan promote breast cancer progression in vitro and in vivo via activating G protein-coupled estrogen receptor signaling pathways - Ting-Ting He; Xin Li; Jie-Zhi Ma; Yuan Yang; Shiye Zhu; Jianhua Zeng; Lin Luo; Yu-Long Yin; Lin-Ying Cao (Science of The Total Environment, 2024)

Spatiotemporal characterization of PM2.5, O3, and trace gases associated with East Asian continental outflows via drone sounding - Chih-Yuan Chang; Jia-Lin Wang; Yen-Chen Chen; Wei-Nai Chen; Sheng-Hsiang Wang; Ming-Tung Chuang; Neng-Huei Lin; Charles C.-K. Chou; Wei-Syun Huang; Li-Jin Ke; Xiang-Xu Pan; Yu-Jui Ho; et al. (Science of The Total Environment, 2024)

Isolation of 24-homoscalarane sesterterpenoids from a sponge of the genus Lendenfeldia - Li-Guo Zheng; You-Yan Chen; Chia-Ching Liaw; Yu-Chi Lin; Su-Ying Chien; Yi-Hao Lo; Yu-Chi Tsai; Hao-Chun Hu; You-Ying Chen; Tsong-Long Hwang; Tzu-Ming Ou; Ping-Jyun Sung (Phytochemistry Letters, 2024)

Congener-specific fate and impact of microcystins in the soil-earthworm system - Bai-Lin Liu; Peng-Fei Yu; Jing-Jie Guo; Li-Si Xie; Xiang Liu; Yan-Wen Li; Lei Xiang; Hai-Ming Zhao; Nai-Xian Feng; Quan-Ying Cai; Ce-Hui Mo; Qing X. Li (Journal of Hazardous Materials, 2024)

Reconstruction of Fe sacrifice protective layer enables highly effective CoP catalyst for hydrogen evolution reaction at high current density - Yingying Xu; Yingxia Zhao; Ming Sun; Wei Xie; Ying Wu; Gao Cheng; Yuanhong Zhong; Shenbo Han; Lin Yu (Chemical Engineering Journal, 2024)

Continuous selenite biotransformation and biofuel production by marine diatom in the presence of fulvic acid - Hui-Ying Xu; Ruo-Yu Li; Zi-Qiang Yang; Jia-Fan Qiu; Yu-Bin Su; Carol Sze Ki Lin; Wei-Dong Yang; Hong-Ye Li; Jian-Wei Zheng; Xiang Wang (Bioresource Technology, 2024)

Gas-to-particle partitioning of atmospheric water-soluble organic aerosols: Indications from high-resolution observations of stable carbon isotope - Hao-Ran Yu; Yan-Lin Zhang; Fang Cao; Xiao-Ying Yang; Tian Xie; Yu-Xian Zhang; Yongwen Xue (Atmospheric Environment, 2024)

An Updated Review on Self-Healing Barrier Materials with Potential Application in Contaminated Soil / Groundwater Risk Control - Fuhao Fan; Haibo Li; Ying Lin; Yang Liu; Wei Yu; Yingying Wu (Water, Air, & Soil Pollution, 2024)

Therapeutic effects and mechanisms of isoxanthohumol on DSS-induced colitis: regulating T cell development, restoring gut microbiota, and improving metabolic disorders - Ya-Na Yang; Bing Han; Mao-Qing Zhang; Na-Nan Chai; Feng-Lin Yu; Wen-Hui Qi; Meng-Yuan Tian; Dong-Zhi Sun; Ying Huang; Qing-Xin Song; Yan Li; Mao-Cui Zhu; et al. (Inflammopharmacology, 2024)

Marinobacter albus sp. nov., Isolated from Sand Sediment in a Coastal Intertidal Zone - Tai-Hang Deng; Yu Zhang; Wen-Wu Zhang; Yue Su; Jia-Wei Gao; Jun-Jie Ying; Lin Xu; Xiao-Ming Xia; Cong Sun (Current Microbiology, 2024)

Taxonomy of Two New Peritrich Ciliates (Protozoa: Ciliophora) from Inland Saltwaters of China - Ying Yu; Yong Zhang; Ziyao Liang; Jiqiu Li; Xiaofeng Lin (Journal of Ocean University of China, 2024)

Numerical seismic performance assessment and fragility analysis for gravity-type wharves considering the influence of soil liquefaction - Yung-Yen Ko; Ho-Hsiung Yang; Chi-Wen Hu; Yan-Jhih Huang; Yu-Ying Lin (Soil Dynamics and Earthquake Engineering, 2024)

Corrigendum to “Effects and mechanisms of polycyclic aromatic hydrocarbons in inflammatory skin diseases” [Sci. Total Environ. 925 171492] - Hui Jin; Ziyuan Lin; Tianyi Pang; Jingwen Wu; Cheng Zhao; Ying Zhang; Yu Lei; Qilin Li; Xu Yao; Ming Zhao; Qianjin Lu (Science of The Total Environment, 2024)

Effects and mechanisms of polycyclic aromatic hydrocarbons in inflammatory skin diseases - Hui Jin; Ziyuan Lin; Tianyi Pang; Jingwen Wu; Cheng Zhao; Ying Zhang; Yu Lei; Qilin Li; Xu Yao; Ming Zhao; Qianjin Lu (Science of The Total Environment, 2024)

Metabolic disturbance of short- and medium-chain chlorinated paraffins to zebrafish larva - Shuangshuang Chen; Xiaoqian Ren; Ying Yu; Lin Cheng; Guanghui Ding; Hairong Yang; Haijun Zhang; Jiping Chen; Ningbo Geng (Science of The Total Environment, 2024)

Corrigendum to “Arsenic exposure and pulmonary function decline: Potential mediating role of TRAIL in chronic obstructive pulmonary disease patients” [J. Trace Elem. Med. Biol. 83 (2024) 127415] - Ying Liu; Feng-Min Zhu; Juan Xu; You-Peng Deng; Jing Sun; Qi-Yuan He; Zhen-Yu Cheng; Min-Min Tang; Jin Yang; Lin Fu; Hui Zhao (Journal of Trace Elements in Medicine and Biology, 2024)

Arsenic exposure and pulmonary function decline: Potential mediating role of TRAIL in chronic obstructive pulmonary disease patients - Ying Liu; Feng-Min Zhu; Juan Xu; You-Peng Deng; Jing Sun; Qi-Yuan He; Zhen-Yu Cheng; Min-Min Tang; Jin Yang; Lin Fu; Hui Zhao (Journal of Trace Elements in Medicine and Biology, 2024)

Prenatal exposure to a mixture of organophosphate flame retardants and infant neurodevelopment: A prospective cohort study in Shandong, China - Xiaomeng Cheng; Qi Lu; Nan Lin; Dandan Mao; Shengju Yin; Yu Gao; Ying Tian (International Journal of Hygiene and Environmental Health, 2024)

Regulating photoluminescence through single-crystal-to-single-crystal transformation of solvent-containing zero-dimensional hybrid metal halide isomers - Ying-Chen Peng; Jian-Ce Jin; Sheng-Hua Zhou; Hao-Wei Lin; Dan-Dan Huang; Zhong-Hua Deng; Yu Dong; Hao-Jie Xu; Ke-Zhao Du; Ze-Ping Wang; Xiao-Ying Huang (Chemical Engineering Journal, 2024)

Roles of Neuronal Protein Kinase Cε on Endoplasmic Reticulum Stress and Autophagic Formation in Diabetic Neuropathy - Yu-Yu Kan; Ying-Shuang Chang; Wen-Chieh Liao; Tzu-Ning Chao; Yu-Lin Hsieh (Molecular Neurobiology, 2024)
In chronic diabetic neuropathy (DN), the cellular mechanisms of neuropathic pain remain unclear. Protein kinase C epsilon (PKCε) is an intracellular signaling molecule that mediates chronic pain. This paper addresses the long-term upregulated PKCε in DN associated with endoplasmic reticulum (ER) stress and autophagic formation and correlates to chronic neuropathic pain. We found that thermal hyperalgesia and mechanical allodynia course development were associated with PKCε upregulation after DN but not skin denervation. Pathologically, PKCε upregulation was associated with the expression of inositol-requiring enzyme 1α (IRE1α; ER stress–related molecule) and ubiquitin D (UBD), which are involved in the ubiquitin-proteasome system (UPS)-mediated degradation of misfolded proteins under ER stress. Manders coefficient analyses revealed an approximately 50% colocalized ratio for IRE1α(+):PKCε(+) neurons (0.34–0.48 for M1 and 0.40–0.58 for M2 Manders coefficients). The colocalized coefficients of UBD/PKCε increased (M1: 0.33 ± 0.03 vs. 0.77 ± 0.04, p < 0.001; M2: 0.29 ± 0.05 vs. 0.78 ± 0.04; p < 0.001) in the acute DN stage. In addition, the regulatory subunit p85 of phosphoinositide 3-kinase, which is involved in regulating insulin signaling, exhibited similar expression patterns to those of IRE1α and UBD; for example, it had highly colocalized ratios to PKCε. The ultrastructural examination further confirmed that autophagic formation was associated with PKCε upregulation. Furthermore, PKCεv1-2, a PKCε specific inhibitor, reverses neuropathic pain, ER stress, and autophagic formation in DN. This finding suggests PKCε plays an upstream molecule in DN-associated neuropathic pain and neuropathology and could provide a potential therapeutic target.

Susceptibility assessment of earthquake-induced landslide by using back-propagation neural network in the Southwest mountainous area of China - Yingbin Zhang; Haotian Yang; Jianfeng Lin; Peiyi Xu; Jing Liu; Ying Zeng; Haiying Fu; Haihong Yu; Yunyong He (Bulletin of Engineering Geology and the Environment, 2024)

Advances and development in sampling techniques for marine water resources: a comprehensive review - Ying Wang; Jiawang Chen; Jin Guo; Zhenwu Yu; Yuan Lin; Yuhong Wang (Frontiers in Marine Science, 2024)
Marine water resources (including seawater and pore-water) provide important information for understanding the marine environment, studying marine organisms, and developing marine resources. Obtaining high-quality marine water samples is significant to marine scientific research and monitoring of marine resources. Since the 20th century, marine water resources sampling technology has become the key research direction of marine equipment. In order to have a comprehensive understanding of marine water resource sampling technology, promote the development of marine water resource sampling technology, and obtain high-quality marine water samples, this paper summarizes the current development status of the sampling technology of marine water resources from the aspects of research and application. This paper first provides an overview of seawater and pore water sampling techniques. The two sampling technologies are categorized and discussed according to different sampling means, and the advantages of different sampling means are compared. We also found similarities between seawater and pore water sampling means. Then, a comprehensive analysis of existing technologies and equipment reveals the development trend of marine water resources sampling technology, for example, the need for high temporal and spatial accuracy in sampling, etc. Finally, it explores the challenges facing deep-sea water sampling technology regarding future research, development and equipment industrialization. These reviews not only help researchers better understand the current development of marine water sampling technologies but also provide an important reference for the future development of marine water sampling technology, which provides guidance and support for in-depth marine scientific research and effective use of marine resources.

Potassium diformate alleviated inflammation of IPEC-J2 cells infected with EHEC - Ying Lin; Jun-Lei Zhai; Ya-Ting Wang; Ping-Ting Guo; Jing Zhang; Chang-Kang Wang; Ling Jin; Yu-Yun Gao (Veterinary Microbiology, 2024)

Exploring the differences between express and ride-pooling: A dual perspective on user perception and functional positioning in urban traffic system - Ying Lu; Shuyue Yao; Hongzhi Lin; Jianqiang Cui; Wenhui Yu (Travel Behaviour and Society, 2024)

Comparative analysis of Deinagkistrodon acutus venom from Taiwan and China utilizing chromatographic, electrophoretic, and bioinformatic approaches, along with ELISA employing a monospecific antivenom - Tein-Shun Tsai; Inn-Ho Tsai; Jing-Lin Qiu; Yuen-Ying Chan; Yu-Wei Chiang (Toxicon, 2024)

The SMAC mimetic GDC-0152 is a direct ABCB1-ATPase activity modulator and BIRC5 expression suppressor in cancer cells - I-Li Lin; Yu-Ting Lin; Yung-Chieh Chang; Sree Karani Kondapuram; Kai-Hsuan Lin; Pin-Chen Chen; Chung-Ying Kuo; Mohane Selvaraj Coumar; Chun Hei Antonio Cheung (Toxicology and Applied Pharmacology, 2024)

Estimation of crop residue production and its contribution to carbon neutrality in China - Xin Zhao; Ruo-Chen Li; Wen-Xuan Liu; Wen-Sheng Liu; Ying-Hao Xue; Ren-Hua Sun; Yu-Xin Wei; Zhe Chen; Rattan Lal; Yash Pal Dang; Zhi-Yu Xu; Hai-Lin Zhang (Resources, Conservation and Recycling, 2024)

Minimal learning parameters-based simplified robust adaptive saturated control for dynamic positioning ship with input magnitude and rate saturations - Kun Liang; Jiawei Cui; Peng Lu; Yu Chen; Xiaogong Lin; Yaowei Sun; Qiang Zhang; Xinling Wen; Ying Duan (Ocean Engineering, 2024)

Estimating spatiotemporal pumping amounts using multiple signal decomposition methods - Hua-Ting Tseng; Ying-Fan Lin; Hwa-Lung Yu (Journal of Hydrology, 2024)

Di-n-butyl phthalate promotes the neural differentiation of mouse embryonic stem cells through neurogenic differentiation 1 - Ying-Chu Lin; Kenly Wuputra; Kohsuke Kato; Chia-Chen Ku; Shigeo Saito; Michiya Noguchi; Yukio Nakamura; Michael Hsiao; Chang-Shen Lin; Deng-Chyang Wu; Atsushi Kawaguchi; Hsin-Su Yu; et al. (Environmental Pollution, 2024)

A Pollution Barrier Self-Healing Material: Investigating the Effect of Individual Components on Its Performance and Determining Optimal Ratios and Healing Compositions - Fuhao Fan; Haibo Li; Liuyu Song; Ying Lin; Xiaofei Qin; Yang Liu; Sihan Li; Wei Yu; Yingying Wu (Water, Air, & Soil Pollution, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

Morphology and chemical composition of Taiwan oil millet (Eccoilopus formosanus) epicuticular wax - Marita Anggarani; Yu-Ying Lin; Shao-An Fang; Hshin-Ping Wu; Chi-Chih Wu; Wann-Neng Jane; Thomas James Roscoe; Frederic Domergue; Yue-Ie Caroline Hsing (Planta, 2024)

Cognitive Deficits and Alzheimer’s Disease-Like Pathologies in the Aged Chinese Tree Shrew - Hongli Li; Bo-Lin Xiang; Xiao Li; Cong Li; Yu Li; Ying Miao; Guo-Lan Ma; Yu-Hua Ma; Jia-Qi Chen; Qing-Yu Zhang; Long-Bao Lv; Ping Zheng; et al. (Molecular Neurobiology, 2024)

Emerging role of lncRNAs as mechanical signaling molecules in mechanotransduction and their association with Hippo-YAP signaling: a review - Siyi Lin; Xinyu He; Ying Wang; Yu Chen; Aifu Lin (Journal of Zhejiang University-SCIENCE B, 2024)

Associations of residential greenness exposure and ambient air pollutants with newly-diagnosed drug-resistant tuberculosis cases - Wan-mei Song; Yi Liu; Dan Men; Shi-jin Li; Ning-ning Tao; Qian-yun Zhang; Si-qi Liu; Qi-qi An; Xue-han Zhu; Qi-lin Han; Yu-zhen Zhang; Ying-ying Li; et al. (Environmental Science and Pollution Research, 2024)

Physiological and transcriptome analysis of acclimatory response to cold stress in marine red alga Pyropia yezoensis - Li-Hong Ma; Lin Tian; Yu-Qing Wang; Cong-Ying Xie; Guo-Ying Du (Algae, 2024)
Red macroalga Pyropia yezoensis is a high valuable cultivated marine crop. Its acclimation to cold stress is especially important for long cultivation period across winter in coasts of warm temperate zone in East Asia. In this study, the response of P. yezoensis thalli to low temperature was analyzed on physiology and transcriptome level, to explore its acclimation mechanism to cold stress. The results showed that the practical photosynthesis activity (indicated by ΦPSII and qP) was depressed and pigment allophycocyanin content was decreased during the cold stress of 48 h. However, the Fv/Fm and non-photochemical quenching increased significantly after 24 h, and the average growth rate of thalli also rebounded from 24 to 48 h, indicating a certain extent of acclimation to cold stress. On transcriptionally, the low temperature promoted the expression of differentially expressed genes (DEGs) related to carbohydrate metabolism and energy metabolism, while genes related to photosynthetic system were depressed. The increased expression of DEGs involved in ribosomal biogenesis and lipid metabolism which could accelerate protein synthesis and enhance the degree of fatty acid unsaturation, might help P. yezoensis thallus cells to cope with cold stress. Further co-expression network analysis revealed differential expression trends along with stress time, and corresponding hub genes play important roles in the systemic acquired acclimation to cold stress. This study provides basic mechanisms of P. yezoensis acclimation to cold temperature and may aid in exploration of functional genes for genetic breeding of economic macroalgae.

Impact of occupational noise exposure on the hearing level in hospital staffs: a longitudinal study - Tang-Chuan Wang; You-Cheng Yu; Alan Hsu; Jia-Yi Lin; Yung-An Tsou; Chiu-Shong Liu; Kai-Jen Chuang; Wen-Chi Pan; Chin-An Yang; Sung-Lin Hu; Chien-Yi Ho; Tzu-Liang Chen; et al. (Environmental Science and Pollution Research, 2024)

Combined analysis of transcriptomics and metabolomics provide insights into the antibacterial mechanism of bacteriocin XJS01 against multidrug-resistant Staphylococcus aureus - Jian-Ping Ying; Chao-Min Fu; Yan-Chun Wu; Ya-Mei Chen; Xiao-Yu Liu; Qi-Lin Zhang; Hui Liu; Ming-Zhong Liang (Science of The Total Environment, 2024)

Identifying the source and fate of boron in geothermal water: Evidence from B/Na and B isotopes - Ying Tan; Xiao-Wei Jiang; Tao-Tao Ji; Yin-Fei Luo; Wan Dai; Hong Zhang; Zhao-Xuan Niu; Yu-De Lei; Zhi-Yuan Zhang; Tian-Yi Lin; Hua-Ming Guo (Science of The Total Environment, 2024)

Investigating the antibiotic resistance genes and their potential risks in the megacity water environment: A case study of Shenzhen Bay Basin, China - Hebin Liang; Jin Huang; Yi Tao; Uli Klümper; Thomas U. Berendonk; Kai Zhou; Yu Xia; Ying Yang; Yang Yu; Ke Yu; Lin Lin; Xiaoyan Li; et al. (Journal of Hazardous Materials, 2024)

Characterization of key flavor substances and their microbial sources in traditional sour bamboo shoots - Hui Tang; Jin-Kui Ma; Lin Chen; Li-Wen Jiang; Lin-Zhi Kang; Ying-Yu Guo; Ge-Yang Men; Dan-Xia Nie; Rui-Min Zhong (Food Chemistry, 2024)

Does saponin in quinoa really embody the source of its bitterness? - Lin Meng Song; Yuan Yu; Li Dong Du; Xue Ying Ji; Hui Gao; Yu Qing Cai; Chang Jian Li; Peng Xue (Food Chemistry, 2024)

A comprehensive evaluation of milk protein molecular weight distribution based on exclusion chromatography dataset - Yu Liu; Xiao-Yan Li; Ling Li; Yu-Qi Yin; Han-Lin Zhang; Kun-Long Wang; Jie Zhou; Yun Chen; Ying-Hua Zhang (Food Chemistry, 2024)

LncFASA promotes cancer ferroptosis via modulating PRDX1 phase separation - Xiao Fan; Fangzhou Liu; Xiang Wang; Ying Wang; Yu Chen; Chengyu Shi; Xinwan Su; Manman Tan; Qingfeng Yan; Jinrong Peng; Jianzhong Shao; Yan Xiong; et al. (Science China Life Sciences, 2024)

Identification of water pollution sources and analysis of pollution trigger conditions in Jiuqu River, Luxian County, China - Ying Liu; Fangfei Liu; Zhengjiang Lin; Nairui Zheng; Yu Chen (Environmental Science and Pollution Research, 2024)

Triphenyl phosphate exposure impairs colorectal health by altering host immunity and colorectal microbiota - Changchun Ye; Zilu Chen; Wenhao Lin; Zepeng Dong; Jie Han; Jingyi Zhang; Xueqian Ma; Junhui Yu; Xuejun Sun; Ying Li; Jianbao Zheng (Chemosphere, 2024)

The economic feasibility of aquavoltaics in Taiwan - A case study of whiteleg shrimp (Litopenaeus vannamei) culture - Bo-Ying Chen; Po-Lin Huang; Yen-Lung Hou; Hsun-Yu Lan; Cheng-Ting Huang; Fan-Hua Nan (Aquaculture, 2024)

Assessment of sources and health risks of heavy metals in metropolitan household dust among preschool children: The LEAPP-HIT study - Chi-Sian Kao; Ying-Lin Wang; Chuen-Bin Jiang; Pei-Ju Tai; Yi-Hua Chen; Hsing-Jasmine Chao; Yu-Chun Lo; Zeng-Yei Hseu; Hsing-Cheng Hsi; Ling-Chu Chien (Journal of Environmental Management, 2024)

Dual-functional membranes of CQDs/TiO2 @PI/PES nanofibers for the high filter efficiency of ultrafine particles and photocatalytic activity - Hua-Wei Chen; Yu-Lin Kuo; Shu-Hsien Huang; Chyow-San Chiou; Ying-Cih Chen; Wei-Ting Chen (Journal of Environmental Chemical Engineering, 2024)

Permeability enhancement and coal fines removal through oxidation treatment in coalbed methane reservoirs - Yu Lu; Yili Kang; Chengzhong Bu; Ying Li; Chong Lin; Zhenjiang You (Fuel, 2024)

Molecular and proteomic response of Pseudomonas fluorescens biofilm cultured on lettuce (Lactuca sativa L.) after ultrasound treatment at different intensity levels - Hang Yu; Jiang Lin; Mengru Wang; Su Ying; Shaofeng Yuan; Yahui Guo; Yunfei Xie; Weirong Yao (Food Microbiology, 2024)

Triclocarban exhibits higher adipogenic activity than triclosan through peroxisome proliferator-activated receptors pathways - Jia-Da Zhang; Sen He; Ting-Ting He; Chuan-Hai Li; Bing-Hua Yan; Yuan Yang; Jian Yang; Lin Luo; Yu-Long Yin; Lin-Ying Cao (Environmental Pollution, 2024)

Enhanced organic matter humification by hydroxyl radical generation during electric field-assisted aerobic composting - Ruizhi Xing; Keke Yin; Xian Du; Ying Lin; Zhen Yu; Zhi Chen; Shungui Zhou (Chemical Engineering Journal, 2024)

Mechanical robust, adhesive, self-healable and biodegradable protein-based electronic skin sensors for smart elderly care - Ying-Ao Zhang; Chen-Yu Wang; Xiao-Xue Wang; Meng Yin; Ke Wang; Da-Wei Zhou; Hong-Long Zheng; Shou-Shan Yu; Shuang Li; Ke-Zheng Chen; Sheng-Lin Qiao (Chemical Engineering Journal, 2024)

The role of a small molecular dipole moment for efficient non-doped deep blue thermally activated delayed fluorescence emitters - Hong-Ji Tan; Jie-Rong Yu; Zhi-Zhong Lin; Guo-Xi Yang; Zhi-Qiang Long; Ying-Lan Deng; Ze-Lin Zhu; Xian-Kai Chen; Jing-Xin Jian; Qing-Xiao Tong; Chun-Sing Lee (Chemical Engineering Journal, 2024)

GW4064 inhibits migration and invasion through cathepsin B and MMP2 downregulation in human bladder cancer - Chien-Chang Kao; Chien-Rui Lai; Yi-Hsuan Lin; Tzu-Min Chen; Yu-Ling Tsai; Wen-Chiuan Tsai; Tze-Yun Ong; Hisao-Hsien Wang; Sheng-Tang Wu; Ying Chen (Chemico-Biological Interactions, 2024)

Polyhydroxyalkanoates bioproduction from bench to industry: Thirty years of development towards sustainability - Priskila Adjani Diankristanti; Yu-Chieh Lin; Ying-Chen Yi; I-Son Ng (Bioresource Technology, 2024)

Metal(Loid)s in Aquatic Products and Their Potential Health Risk - Shi-Lin Hu; Xiao-Chen Chen; Ying-Xin Xue; Li-Ying Zhi; Yu-Han Yang; Yong-Guan Zhu; Xi-Mei Xue (Exposure and Health, 2024)

The dynamic mechanism of scientific and technological innovation in China’s marine biomedical industry - Xiu-Mei Fu; Yan-Xin Tan; Ying Liu; Ying-Hui Han; Qiao-Qiao Qi; Jing-Hang Li; Chun-Yu Lin (Frontiers in Marine Science, 2024)
As one of the important forces promoting the development of the marine economy, the marine biomedical industry (MBI) shows typical knowledge and technology-intensive characteristics. It is of great significance to explore the industrial innovation dynamic mechanism for breaking through the bottleneck of innovative development as well as achieving high-quality development. This paper constructed a system dynamics model for scientific and technological innovation (STI) in the MBI and then explored the dynamic mechanism of STI in the industry through simulation. The study found that, in the innovation environment subsystem, the two factors of the intellectual property protection intensity and the government’s scientific research funding input had the most significant positive driving effects on STI of the MBI; the promotion of government education funding input showed a significant strengthening trend over time, while the marine environmental regulation intensity had comparatively little effect on the level of STI. In the subsystem of innovation input, both innovation funding input and innovation personnel input were the direct driving forces for the improvement of the STI level. And enterprises played a dominant role in STI because the STI level of the MBI was more sensitive to the changes in enterprise innovation input. Compared with the individual factor input, the synergistic promotion effect of multiple factors is more significant. In addition, it was found that there was a low conversion rate of scientific research achievements in China’s MBI by analyzing the influence of various factors changing on technological output and economic output. Based on the research results, this paper puts forward corresponding policy suggestions in order to provide theoretical support and a practical basis for promoting the technological innovation level of China’s MBI as well as references for other countries.

Environmental selenium and human longevity: An ecogeochemical perspective - Bo Li; Xu Liu; Tao Yu; Kun Lin; Xudong Ma; Cheng Li; Zhongfang Yang; Qifeng Tang; Guodong Zheng; Jianxun Qin; Ying Wang (Chemosphere, 2024)

Development and evaluation of a bivalent vaccine based on recombinant newcastle disease virus expressing infectious bursal disease virus VP2L-CH3-CH4 in SPF chickens - Wen Ying Sun; Xiao Lin Cao; Yi Xuan Wang; Xiao Chen Guo; Jin Miao Liu; Zhi Qiang Xue; Hui Juan Li; Wei Wang; Ting Ting Zhang; Qianhui Li; Rui Han Qin; Yu Han Jin; et al. (Veterinary Microbiology, 2024)

Permafrost on the Tibetan Plateau is degrading: Historical and projected trends - Tongqing Shen; Peng Jiang; Qin Ju; Jiahui Zhao; Xuegao Chen; Hui Lin; Bin Yang; Changhai Tan; Ying Zhang; Xinting Fu; Zhongbo Yu (Journal of Hydrology, 2024)

Rapid marine degradable poly(butylene oxalate) by introducing promotion building blocks - Zhu Tu; Lizheng Wang; Ying Lu; Yang Li; Lin Sang; Yu Zhang; Zhiyong Wei (Journal of Hazardous Materials, 2024)

Design of bifunctional ultrathin MnO2 nanofilm with laccase-like activity for sensing environmental pollutants containing phenol groups - Sheng-Tao Wu; Hui-Qi Su; Qian-Xiang Xiao; Zhi-Yu Qiu; Gang-Qiang Huang; Man-Ni He; Yi Ge; Cong-Hui Wang; Ying-Wu Lin (Journal of Hazardous Materials, 2024)

Combined microbe-plant remediation of cadmium in saline-alkali soil assisted by fungal mycelium-derived biochar - Zirun Zhao; Lin Liu; Ying Sun; Liling Xie; Shuo Liu; Mingchun Li; Qilin Yu (Environmental Research, 2024)

Potential roles of iron nanomaterials in enhancing growth and nitrogen fixation and modulating rhizomicrobiome in alfalfa (Medicago sativa L.) - Ming-Xu Zhang; Ling-Yu Zhao; Yuan-Yuan He; Jin-Peng Hu; Guo-Wen Hu; Ying Zhu; Aziz Khan; You-Cai Xiong; Jin-Lin Zhang (Bioresource Technology, 2024)

Technological diversity in the tropical-subtropical zone of Southwest China during the terminal Pleistocene: excavations at Fodongdi Cave - Fa-Xiang Huan; Shi-Xia Yang; Feng Gao; Xin-Ying Zhou; Jian-Ping Yue; Yu-Xiu Zhang; Jin-Xu Wu; Qi-Jun Ruan; Kai-Wei Qiu; Jing-wen Xu; Nai-Ru Lin; Yi-Ren Wang; et al. (Archaeological and Anthropological Sciences, 2024)

The Bioeconomic Analysis of Hybrid Giant Grouper (Epinephelus fuscoguttatus × Epinephelus lanceolatus) and Green Grouper (Epinephelus malabaricus): A Case Study in Taiwan - Po-Lin Huang; Farok Afero; Yao Chang; Bo-Ying Chen; Hsun-Yu Lan; Yen-Lung Hou; Cheng-Ting Huang (Fishes, 2023)
Grouper aquaculture is a rapidly growing and dynamic industry within the Taiwan aquaculture sector that serves as an important source of income generation. Farming fishes at a better location (FFABL) is a promising production strategy. This study evaluated the production and economic performance of grouper farming in Taiwan. This investigation employed two steps: (1) a cost–benefit analysis to determine the main component affecting profitability; and (2) multivariate statistics to clarify the relationship between biological and economic factors. The findings suggest that the best choice of species is hybrid giant grouper that generates and highlights a positive income, viable benefit–cost ratio and profit rate. The study found the feed management of hybrid giant groupers requires more consideration due to its low feed conversion ratio. The producers need to replace trash fish in commercial feed during the production cycle to ensure better feed management. Finally, this paper argues that feed is the main constraint for grouper farming, which is sensitive to any change in feed productivity, and this constraint must be solved to sustain the grouper industry in Taiwan.

Impact of Pacific–Japan pattern on temperature and heatwave events in summer over Taiwan - Wan‐Ling Tseng; Szu‐Ying Lin; Yi‐Chi Wang; Shih‐How Lo; Min‐Hui Lo; Shih‐Yu Lee; Chieh‐Ting Tsai; Huang‐Hsiung Hsu (International Journal of Climatology, 2023)
The prediction of heatwave events is vital to provide information on possible hazards caused by extremely high temperature. The Pacific–Japan (PJ) pattern is a significant climate variability that controls the summer climate over East Asia. Previous studies have reported that the meridional propagating wave structure associated with the PJ pattern can modulate summer temperature and heatwave characteristics over northeast Asian countries, such as Korea and Japan. Nevertheless, its impacts on the subtropical regions, including Taiwan, a mountainous subtropical island with an approximate population of 24 million, is not yet fully understood. In this study, we investigate the impacts of the PJ pattern on the summer temperature and heatwave characteristics in Taiwan on the interannual timescale using long‐term station‐based temperature and rainfall dataset. We found an island‐wide increase in temperature during the positive phase of the PJ pattern, which is characterized by an anticyclonic anomalous circulation over Taiwan. Meanwhile, the averaged effective area and frequency of heatwave extremes over Taiwan have increased significantly, indicating an increase of exposure to heatwaves. Our examinations of large‐scale environment suggest that the adiabatic warming due to subsidence anomaly associated with the anticyclone over Taiwan is primary contributor of surface warming, which is balanced by diabatic cooling and meridional advective cooling on a seasonal timescale. Our study consolidated the links between the PJ pattern as a climate driver, hot summers and increased summer heatwave events over Taiwan. By combining with the seasonal prediction systems and early warning systems, such understanding can help sectors that are vulnerable to heat stress to prepare for potential hazards.

Neonicotinoids in tea leaves and infusions from China: Implications for human exposure - Qinru Xiao; Xiangyu Li; Shuyang Xu; Xin Chen; Ying Xu; Yu Lu; Langyan Liu; Liyun Lin; Huimin Ma; Shaoyou Lu (Science of The Total Environment, 2023)

Thickness-variation-insensitive near-infrared quantum dot LEDs - Wan-Shan Shen; Yang Liu; Luke Grater; So Min Park; Haoyue Wan; Yan-Jun Yu; Jia-Lin Pan; Fan-Cheng Kong; Qi-Sheng Tian; Dong-Ying Zhou; Zeke Liu; Wanli Ma; et al. (Science Bulletin, 2023)

Evaluating the toxic mechanism of 1,2-diacetylbenzene in neural cells/tissues: The favorable impact of silibinin - Li-Yu Fay; Jun-Yi Chien; Ching-Feng Weng; Huai-Sheng Kuo; Dann-Ying Liou; Wei-Hao Weng; Chi-Hung Lin; Ya-Tzu Chen; Wen-Hung Huang; Wen-Cheng Huang; May-Jywan Tsai; Henrich Cheng (NeuroToxicology, 2023)

Balanced nitrogen–iron sufficiency boosts grain yield and nitrogen use efficiency by promoting tillering - Ying Song; Guang-Yu Wan; Jing-Xian Wang; Zi-Sheng Zhang; Jin-Qiu Xia; Liang-Qi Sun; Jie Lu; Chuan-Xi Ma; Lin-Hui Yu; Cheng-Bin Xiang; Jie Wu (Molecular Plant, 2023)

A crosslinked waterborne poly(vinyl acetate) for greenhouse gas fixation with improved elastomeric properties, shape-memory ability, and recyclability - Yen-Chuan Chen; Ying-Chi Huang; Yi-Hua Huang; Ying-Feng Lin; Ho-Ching Huang; Ru-Jong Jeng; Yu-Wei Cheng; Chien-Hsin Wu (Journal of Environmental Chemical Engineering, 2023)

Anti-complement factor H (CFH) autoantibodies could delay pristane-induced lupus nephritis - Lin-Lin Li; Zhong-qiu Luan; Ying Tan; Hui Wang; Xiao-Juan Yu; Zhen Qu; Feng Yu; Min Chen (Immunologic Research, 2023)
Purpose Anti-complement factor H (CFH) autoantibodies could be detected in lupus and its significance remained to be elucidated. Herein, we aimed to explore the roles of anti-CFH autoantibodies based on pristane-induced lupus mice. Methods Twenty-four female Balb/c mice were randomly divided into four groups, with one group injected with pristane (pristane group), one group with pristane and then human CFH (hCFH) (pristane-CFH group) 3 times, and the other two as vertical controls, PBS group and PBS-CFH group. Histopathological analysis was performed six months after pristane administration. Levels of hCFH, anti-CFH autoantibodies and anti-dsDNA antibody were detected. Murine IgG (mIgG) were purified and cross-reactivity, epitopes, subclasses and functional analysis were further evaluated in vitro. Results Immunization with hCFH and subsequent development of anti-CFH autoantibodies significantly attenuated nephritis of pristane-induced lupus, including lower levels of urinary protein and serum creatinine, decreased levels of serum anti-dsDNA antibody, greatly ameliorated renal histopathologic damage, decreased IgG, complements (C1q, C3) deposits and lower inflammatory factor (IL-6) expression in glomerulus. Furthermore, the purified mIgG (contained anti-CFH autoantibodies) could recognize both hCFH and murine CFH, and the epitopes were predominantly located in hCFH short consensus repeats (SCRs) 1–4, 7 and 11–14. The IgG subclasses were predominant IgG1. The autoantibodies could enhance the binding between hCFH and C3b, and increase factor I mediated-C3b lysis in vitro. Conclusion Our results suggested that anti-CFH autoantibodies could attenuate pristane-induced lupus nephritis by increasing bio-functions of CFH on regulating complement activation and controlling inflammation.

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Agricultural production efficiency, food consumption, and food waste in the European countries - Tai-Yu Lin; Shih-Yung Chiu; Yung-ho Chiu; Liang-Chun Lu; Kuei-Ying Huang (Environment, Development and Sustainability, 2023)

Analysis of volatile organic compounds and potential odour compounds in food contact paperboard using headspace two-dimensional GC-QTOF-MS - Dan Li; Ying Zeng; Zhi-Kang Ye; Han-Ke Li; Yu-Zhe Li; Ben Dong; Qi-Zhi Su; Qin-Bao Lin; Jing Xiao; Huai-Ning Zhong (Food Additives & Contaminants: Part A, 2023)

IoT-interfaced solid-contact ion-selective electrodes for cyber-monitoring of element- specific nutrient information in hydroponics - Yi-Min Wu; Shao-Yuan Liu; Bo-You Shi; Jui-Yu Peng; Zhi-Wei Kao; Yi-Yi Chen; Ting-Yu Hsieh; Hsing-Ying Chung; Chi-Yi Lin; Wei Fang; Lin-Chi Chen (Computers and Electronics in Agriculture, 2023)

The impact of cooperative innovation network on innovation output of China's marine biomedical industry - Xiu-Mei Fu; Ying-Hui Han; Ying Liu; Qiao-Qiao Qi; Yan-Xin Tan; Meng Gao; Chun-Yu Lin (Ocean & Coastal Management, 2023)

Residues of sulfoxaflor and its metabolites in floral and extrafloral nectar from Hibiscus rosa-sinensis L. (Malvaceae) with or without co-application of tebuconazole - Hong-Xia Zhou; Man-Huan Cheng; Juan-Lin Pan; Peng Cui; Yue-Qin Song; Ying Yu; Jun Cao; Hong-Guang Zha (Pesticide Biochemistry and Physiology, 2023)

Slab dehydration and potassium-lithium recycling in the forearc indicated by potassium and lithium isotope compositions of exhumed metabasites - Haiyang Liu; Tinggen Yang; Ying-Yu Xue; Jianghong Deng; Yilin Xiao; He Sun; Fengtai Tong; Kun Wang; Yongjun Gao; Kuan-Yu Lin; Fangyi Zhang; Xin Jin; et al. (Geochimica et Cosmochimica Acta, 2023)

Study on potential antigenicity and functional properties of whey protein treated by high hydrostatic pressure based on structural analysis - Xin-Xin Yu; Xiao-Hui Wang; Sheng-Ao Zhang; Ying-Hua Zhang; Han-Lin Zhang; Yu-Qi Yin (Food Research International, 2023)

Silver nanoparticle@catechol formaldehyde resin microspheres: One-pot synthesis and application for producing durable antimicrobial cotton fabrics - Lian-Yi Qu; Jiang-Long Liu; An-Le Yang; Lin Zhang; Ping Zhu; Ying-Jun Xu; Yu-Zhong Wang (Chemical Engineering Journal, 2023)

The modification of meteorological factors on the relationship between air pollution and periodontal diseases: an exploration based on different interaction strategies - Kai Huang; Lin-Fei Feng; Zhe-Ye Liu; Zhen-Hua Li; Yi-Cheng Mao; Xin-Qiang Wang; Jia-Wen Zhao; Kang-Di Zhang; Ying-Qing Li; Jie Wang; Wen-Jie Yu; Xin Cheng; et al. (Environmental Geochemistry and Health, 2023)

Arbuscular mycorrhiza changes plant facilitation patterns and increases resource use efficiency in intercropped annual plants - Shuang-Guo Zhu; Hai-Xia Duan; Hong-Yan Tao; Li Zhu; Rui Zhou; Yu-Miao Yang; Xiao-Lin Zhang; Wen-Ying Wang; Hao Zhu; Wei Zhang; Ren-Qing Wang; Xiu-Ping Tao; et al. (Applied Soil Ecology, 2023)

Functional-structural decoupling in visual network is associated with cognitive decline in patients with type 2 diabetes mellitus: evidence from a multimodal MRI analysis - Min-Hua Ni; Ying Yu; Yang Yang; Ze-Yang Li; Teng Ma; Hao Xie; Si-Ning Li; Pan Dai; Xin-Yu Cao; Yan-Yan Cui; Jun-Ling Zhu; Guang-Bin Cui; et al. (Brain Imaging and Behavior, 2023)

Associations between parental and postnatal metal mixture exposure and developmental delays in a Taiwanese longitudinal birth cohort of preschool children - Chi-Sian Kao; Yen-Tzu Fan; Ying-Lin Wang; Yi-Hua Chen; Hsing-Jasmine Chao; Yu-Chun Lo; Chuen-Bin Jiang; Ling-Chu Chien (Environmental Science and Pollution Research, 2023)

Progress in biological activities and biosynthesis of edible fungi terpenoids - Hai-Ying Chen; Jin-Yu Lei; Shu-Li Li; Li-Qiong Guo; Jun-Fang Lin; Guang-Hong Wu; Jun Lu; Zhi-Wei Ye (Critical Reviews in Food Science and Nutrition, 2023)

Environmental exposure to paraben and its association with blood pressure: A cross-sectional study in China - Xu Zhang; Ying Zhang; Hao Lu; Fan Yu; Xueting Shi; Bingchan Ma; Shuang Zhou; Lin Wang; Qing Lu (Chemosphere, 2023)

Dioxin emission prediction from a full-scale municipal solid waste incinerator: Deep learning model in time-series input - Chaojun Wen; Xiaoqing Lin; Yuxuan Ying; Yunfeng Ma; Hong Yu; Xiaodong Li; Jianhua Yan (Waste Management, 2023)

Balanced nitrogen–iron sufficiency boosts grain yield and nitrogen use efficiency by promoting tillering - Ying Song; Guang-Yu Wan; Jing-Xian Wang; Zi-Sheng Zhang; Jin-Qiu Xia; Liang-Qi Sun; Jie Lu; Chuan-Xi Ma; Lin-Hui Yu; Cheng-Bin Xiang; Jie Wu (Molecular Plant, 2023)

Host-derived peptide signals regulate Pseudomonas aeruginosa virulence stress via the ParRS and CprRS two-component systems - Ning-Lin Zhao; Zi-Qi Zhu; Han-Zhong Feng; Ying-Jie Song; Qin Huang; Xing-Yu Mou; Cheng Nong; Yong-Xing He; Rui Bao (Journal of Hazardous Materials, 2023)

Enhancing resilience against geological hazards and soil erosion through sustainable vegetation management: A case study in Shaanxi Province - Qian Wang; Ying Yao; Lin Zhao; Chuan-hao Yang; Yu-chen Zhao; Qi-peng Zhang (Journal of Cleaner Production, 2023)

Insight into the mechanism of water-insoluble dietary fiber from star anise (Illicium verum Hook. f.) on water-holding capacity of myofibrillar protein gels - Ying Xu; Jun Qi; Manman Yu; Ruishu Zhang; Hengxun Lin; Huimin Yan; Chao Li; Jingmin Jia; Yong Hu (Food Chemistry, 2023)

Biodegradable micro-nanofiber medical tape with antibacterial and unidirectional moisture permeability - Ning Zhou; Yu-Fei Gao; Ying Huo; Kai Zhang; Jian Zhu; Ming-Yi Chen; Ling Zhu; Yi-Hang Dong; Hong-Guo Gao; Ick Soo Kim; Ke-Qin Zhang; Rou-Xi Chen; et al. (Chemical Engineering Journal, 2023)

Combining HUMSC secretome and a conductive hydrogel enhances angiogenesis and electrical transmission at myocardial infarct sites to support cardiac repair - Shu-yi He; Lin-yu Long; Zhi-cun Wang; Wen-qi Liu; Wen Zhang; Cheng Hu; Xiao-feng Wu; Ruiqi Dong; Hong-song Fan; Qing-Jiang; Ying-ying Tong; Guang-hua Yang; et al. (Chemical Engineering Journal, 2023)

Advanced electrooxidation of florfenicol using 3D printed Nb2O5/Ti electrodes: Degradation efficiency, dehalogenation performance, and toxicity reduction - Yun-fei Zhang; Jia-le Gao; Shen-gui Chen; Lei Li; Jian-hui Xu; Dan Li; Yu-feng Liu; Xin Quan; Xin Fu; Ya-zi Xie; Jing-nan Wu; Dan-ying Lin; et al. (Chemical Engineering Journal, 2023)

GABAergic Neurons in the Nucleus Accumbens are Involved in the General Anesthesia Effect of Propofol - Jing Yan; Bei-Ning Hang; Lin-Hui Ma; Jia-Tao Lin; Yue Zhou; Xin-Hao Jiao; Ying-Xuan Yuan; Ke-Jie Shao; Le-Meng Zhang; Qi Xue; Zi-Yi Li; Hong-Xing Zhang; et al. (Molecular Neurobiology, 2023)

Biogeographic distribution patterns of the bacterial and archaeal communities in two seamounts in the Pacific Ocean - Ning-Hua Liu; Jun Ma; Si-Qi Lin; Kui-Dong Xu; Yu-Zhong Zhang; Qi-Long Qin; Xi-Ying Zhang (Frontiers in Marine Science, 2023)
Seamounts are important components of seafloor topography and have a significant influence on the biogeographic distribution of marine microorganisms. However, current studies on the biogeographic distribution patterns of microorganisms in the ocean around seamounts are still inadequate. This study investigated the bacterial and archaeal communities present in the water column at various depths around the Kocebu and M5 seamounts located in the western Pacific Ocean using 16S rRNA gene high-throughput sequencing. The analyses showed that microbial communities had different alpha diversities and species compositions in samples from the same depth, and disruption of vertical stratification of microbes was observed in deep water layers at both seamounts. The stochastic processes dominated the microbial community assembly around two seamounts, for the Kocebu Seamount, drift accounted for 34.99% and 64.85% in the bacterial and archaeal community assembly processes, respectively; while the corresponding values for the M5 Seamount were 14.07% and 58.65%. Despite the low explanatory power of environmental variables for microbial communities, dissolved inorganic nitrogen was the most significant factor influencing the microbial community structure in seawater around seamounts. Overall, our results revealed that the presence of Kocebu and M5 seamounts enhance the vertical mixing of microbial communities in the surrounding seawater, and stochastic processes dominate microbial community assembly. Considering the numerous seamounts in the global ocean, the impacts of seamounts on marine ecosystems and biogeochemical cycles may have been underestimated.

Exposure to incense burning, biomarkers, and the physical health of temple workers in Taiwan - Su-Er Guo; Pamela A. Ratner; Sung-Chih Tseng; Chieh-Mo Lin; Miao-Ching Chi; Chiang-Wen Lee; Ying-Chun Yu (Environmental Science and Pollution Research, 2023)
Incense burning releases heavy particulate matter (PM) and nitrogen dioxide (NO 2 ), known to have adverse effects on human health. Long-term exposure to PM and NO 2 increases inflammatory cytokine levels and can induce respiratory diseases. This study examined the association between incense burning exposure and the health status, especially inflammatory biomarkers, of temple workers and volunteers in Taiwan. The longitudinal observational study compared adult temple workers and volunteers, with long-term incense burning exposure, to residents from outpatient clinics in the Chiayi area. Forced expiratory volume in 1 s (FEV1) and serum and exhaled breath condensate (EBC) cytokines were assessed. Nonparametric Mann-Whitney U tests were used to compare cytokine levels of the exposure and control groups during the cold and hot weather seasons. FEV1 was significantly more diminished in the exposed group than in the control group during the cold season. Exposure status was associated with greater hot-cold seasonal differences in serum interleukins (IL)-1β (regression coefficient ( B ) = 6.6, 95% confidence interval (CI) = 5.0 to 8.3, p < .001), IL17-A ( B = 2.4, 95% CI = 0.3 to 4.5, p = .03), and plasminogen activator inhibitor [PAI]-1 ( B = 5.4, 95% CI = 1.5 to 9.3, p = .009). After adjusting for confounders, the groups’ serum levels of IL-1β, IL-17A, and PAI-1 significantly differed. EBC cytokines did not show significant differences. Elevated levels of IL-1β, IL17-A, and PAI-1 have been associated with various autoinflammatory syndromes and diseases. Given the cultural significance of incense burning, culturally sensitive interventions, including education, policy development, and program implementation, are crucial to protect individuals’ health, especially temple workers, from the adverse effects of exposure, addressing the manufacture, importation, and sale of incense.

Carbon source shaped microbial ecology, metabolism and performance in denitrification systems - Yuan Pan; Rui-Zhe Sun; Yan Wang; Guan-Lin Chen; Ying-Ying Fu; Han-Qing Yu (Water Research, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Estimating hydrogeological parameters at groundwater level observation wells without pumping well information - Hwa-Lung Yu; Shih-Yao Lee; Hua-Ting Tseng; Ying-Fan Lin (Journal of Hydrology, 2023)

A novel bacteriocin RSQ01 with antibacterial activity and its application and metabolomic mechanism in milk preservation - Yan-Mei Zhang; Lin-Yu Yang; Jian-Ping Ying; Chao-Min Fu; Gang Wu; Xiao-Ran Li; Qi-Lin Zhang (Food Control, 2023)

Growth-promoting and low-salt adaptation responses boosted by spermidine in Strombidium parasulcatum, a marine bacteriovorous ciliate potentially applied to live feeds for marine larviculture - Hung-Yun Lin; Bo-Ying Su; Nodali Ndraha; Sheng-Fang Tsai; Kuo-Ping Chiang; Hsin-Yun Liu; Yong-Ting Kang; Wei-Yu Yeh; Che-Chia Tsao; Yi-Min Chen; Hsin-I Hsiao; Han-Jia Lin (Aquaculture, 2023)

Method for quantitative extraction of copper hydroxide nanoparticles from farmland soil - Xin-Yuan Li; Yuan Yang; Peng Huang; Ying-Rong Wang; Yu-Lin Nie; Li Zhang; Qiang Wang (Science of The Total Environment, 2023)

Suspended particulate matter-associated environmental corticosteroids in the Pearl River, China: Occurrence, distribution, and partitioning - Jian Gong; Yong-Shun Zhou; Can-Yuan Lin; Qiang Li; Chong Han; Ke-Xin Yang; Ying Huang; Wei-Quan Lin; Cui-Qin Wu; Shu-Han Zhang; Jia-Yu Huang (Science of The Total Environment, 2023)

Semen damage contributed over 50 % to air-pollutant-induced infertility: A prospective cohort study of 3940 men in China - Ying Guo; Qing Chen; Yu Zhan; Wenzheng Zhou; Haiyan Zhang; Niya Zhou; Huan Yang; Yi Chen; Yimeng Wang; Lei Sun; Lin Ao; Jinyi Liu; et al. (Science of The Total Environment, 2023)

Natural resources exploration, efficiency of energy resources and financial development: Resources sector analysis via least square with structural breaks - Meng-Chen Zhang; Chun-Yu Lin; Ying Wei (Resources Policy, 2023)

Katian (Late Ordovician) sphinctozoan-bearing reefs: Hybrid carbonates before the glacial maximum - Qi-jian Li; Lin Na; Shen-yang Yu; Ying-yan Mao; Stephen Kershaw; Yue Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

A novel framework for spatiotemporal groundwater pumping process estimation based on data-driven approaches - Hwa-Lung Yu; Hua-Ting Tseng; Ying-Fan Lin; Chun-Hung Chen; Ying-Chang Kuo; Yun-Ta Cheng (Journal of Hydrology, 2023)

Cleanup of Cr(VI)-polluted groundwater using immobilized bacterial consortia via bioreduction mechanisms - Wei-Han Lin; Chih-Ching Chien; Jiun-Hau Ou; Ying-Liang Yu; Ssu-Ching Chen; Chih-Ming Kao (Journal of Environmental Management, 2023)

Maternal exposure to organophosphate flame retardants and neonatal anthropometric measures - Qi Lu; Nan Lin; Xiaomeng Cheng; Xiaoning Lei; Yan Zhang; Yu Gao; Ying Tian (International Journal of Hygiene and Environmental Health, 2023)

Seismic responses of liquid storage tanks subjected to vertical excitation of near-fault earthquakes - Jie-Ying Wu; Qian-Qian Yu; Qi Peng; Xiang-Lin Gu (Engineering Structures, 2023)

Partial nitritation-anammox for treatment of saline wastewater: Hydrazine-assisted salinity adaptation and nitrate control - Ying-yu Li; Lin Lin; Xiaowu Huang; Xiao-yan Li (Chemical Engineering Journal, 2023)

Rational design of surface reconstruction with pinning effect to relieving bulk fatigue for high energy single-crystal Ni-rich cathodes - Ying-de Huang; Han-Xin Wei; Pei-Yao Li; Lin-Bo Tang; Yu-Hong Luo; Xin-Ming Fan; Cheng Yan; Jing Mao; Ke-Hua Dai; He-Zhang Chen; Xia-hui Zhang; Jun-chao Zheng (Chemical Engineering Journal, 2023)

Fog event is possibly a source rather than a sink of atmospheric nitrate aerosols: Insights from isotopic measurements in Nanjing, China - Hao-Ran Yu; Yan-Lin Zhang; Fang Cao; Zhu-Yu Zhao; Mei-Yi Fan; Xiao-Ying Yang (Applied Geochemistry, 2023)

Annual variation of in situ sedimentation of planktonic Ciliophora cysts in a temperate bay - Ying Yu; Wuchang Zhang; Zhenxian Lin (Frontiers in Marine Science, 2023)
Marine planktonic Ciliophora serve as a key component of the plankton food web. The formation of cysts is of common occurrence among planktonic Ciliophora, and encystment plays an important role in the persistence and diffusion of population. However, studies on the seasonal pattern of encystment of planktonic Ciliophora in natural environments were limited. Here, we investigated the sedimentation of Ciliophora cysts, and explored the seasonal differences of encystment between aloricate Oligotrichea and Tintinnina in Bohai Bay. Ciliophora cysts were collected monthly with a sediment trap from July 2019 to June 2020 at a fixed station, and identified according to the morphological characteristics of cysts by fluorescence microscopy. Ten types of aloricate Oligotrichea cysts were identified and only three species of Tintinnina cysts were recognized, namely, Favella sp., Helicostomella longa and Tintinnopsis sp. There were obvious seasonal differences of encystment between aloricate Oligotrichea and Tintinnina. Encystment of Tintinnina mainly occurred in summer, while encystment of aloricate Oligotrichea was found at all seasons and the seasonal patterns varied among species. The production rate of several types of cysts showed significant positive correlations with water temperature and Chlorophyll a concentration, and a significant negative correlation with salinity. Our study exhibited that the seasonal pattern of encystment of Ciliophora varied greatly from species to species, and assessing seasonal patterns of encystment will aid our ability to understand the mechanism of vegetative population dynamics.

An electronic sense-based machine learning model to predict formulas and processes for vegetable-fruit beverages - Hai-Bin Ren; Bao-Long Feng; Hong-Yue Wang; Jing-Jian Zhang; Xiao-Sen Bai; Fei Gao; Yan Yang; Qi Zhang; Ye-Hui Wang; Li-Li Wang; Ya-Ting Rong; Yu-Lin Sun; et al. (Computers and Electronics in Agriculture, 2023)

Priming effects of nZVI on carbon sequestration and iron uptake are positively mediated by AM fungus in semiarid agricultural soils - Yu-Miao Yang; Minha Naseer; Ying Zhu; Bao-Zhong Wang; Song Wang; Yue Ma; Xiao-Lin Zhang; Xu-Zhe Zhao; Wen-Ying Wang; Shuang-Guo Zhu; Hong-Yan Tao; You-Cai Xiong (Science of The Total Environment, 2023)

The deficiency of N6-methyladenosine demethylase ALKBH5 enhances the neurodegenerative damage induced by cobalt - Chunyan Zheng; Guangxia Yu; Qianqian Su; Lingyan Wu; Jianping Tang; Xinpei Lin; Yao Chen; Zhenkun Guo; Fuli Zheng; Hong Zheng; Liqiong Lin; Ying Tang; et al. (Science of The Total Environment, 2023)

Purification and identification of xanthine oxidase inhibitory peptides from enzymatic hydrolysate of α-lactalbumin and bovine colostrum casein - Yi-Fang Gao; Meng-Qi Liu; Zhong-Han Li; Han-Lin Zhang; Jia-Qi Hao; Bo-Hao Liu; Xiao-Yan Li; Yu-Qi Yin; Xiao-Hui Wang; Qian Zhou; Di Xu; Bao-Ming Shi; et al. (Food Research International, 2023)

Phod-harboring bacterial communities mediated slow and fast phosphorus transformation in alkaline soil of a Robinia pseudoacacia afforestation chronosequence - Ying Wang; Lin Yang; Jiawen Zhang; Yan Li; Haibin Kang; Xiaoxiong Bai; Yongxing Cui; Min Zhang; Liguo Dong; Xuan Yu (Plant and Soil, 2023)

Phylogenetic divergence associated with climate oscillations and topology illustrates the dispersal history of Formosan sambar deer (Rusa unicolor swinhoii) in Taiwan - Kuan-Yi Li; Chen Hsiao; Shih-Ching Yen; Chien-Yi Hung; You-Zhu Lin; Sheng-Wun Jheng; Pei-Ju Yu; Mei-Hsiu Hwang; Guo-Jing Weng; Ku-Lin Chen; Shu-Fen Lin; Shih-Wei Chang; et al. (Mammal Research, 2023)
The island of Taiwan represents an ideal context for studying the effects of climatic oscillations and topographic variation on large herbivores due to its varied tropical to sub-tropical climate zones at different elevational ranges. We explored the phylogenetics of Formosan sambar deer ( Rusa unicolor swinhoii ) using the control region of the mitochondrial genome. We detected 18 haplotypes among 454 sequences across the island and grouped them into six regions based on SAMOVA, with 68.78% variance among regions. A Bayesian phylogenetic dendrogram revealed two spatially segregated genetic clades. Neutrality tests and Bayesian skyline plots uncovered different demographic expansion histories for the two clades. We further tested divergence times and chronology to propose potential phylogenetic scenarios, which were examined using approximate Bayesian computation. Finally, we present a credible hypothesis for a glacial refugium in the northern part of the Central Mountain Range. Subsequent secondary contact between the two clades during interglacial periods has led to the extant genetic structure of Formosan sambar deer.

Environmental quality mediates the ecological dominance of cooperatively breeding birds - Yu‐Heng Lin; Ying‐Yu Chen; Dustin R. Rubenstein; Ming Liu; Mark Liu; Sheng‐Feng Shen (Ecology Letters, 2023)
Although social species as diverse as humans and ants are among the most abundant organisms on Earth, animals cooperate and form groups for many reasons. How these different reasons for grouping affect a species' ecological dominance remains unknown. Here we use a theoretical model to demonstrate that the different fitness benefits that animals receive by forming groups depend on the quality of their environment, which in turn impacts their ecological dominance and resilience to global change. We then test the model's key predictions using phylogenetic comparative analysis of >6500 bird species. As predicted, we find that cooperative breeders occurring in harsh and fluctuating environments have larger ranges and greater abundances than non‐cooperative breeders, but cooperative breeders occurring in benign and stable environments do not. Using our model, we further show that social species living in harsh and fluctuating environments will be less vulnerable to climate change than non‐social species.

Assessment of the impact of climate change on endangered conifer tree species by considering climate and soil dual suitability and interspecific competition - Wenhuan Xu; Jing Jiang; Huan-yu Lin; Tze-Ying Chen; Shiyi Zhang; Tongli Wang (Science of The Total Environment, 2023)

U-shaped association between low-density lipoprotein cholesterol levels and risk of all-cause mortality mediated by post-stroke infection in acute ischemic stroke - Zi-Mo Chen; Hong-Qiu Gu; Jing-Lin Mo; Kai-Xuan Yang; Ying-Yu Jiang; Xin Yang; Chun-Juan Wang; Jie Xu; Xia Meng; Yong Jiang; Hao Li; Li-Ping Liu; et al. (Science Bulletin, 2023)

Gestational cadmium exposure disrupts fetal liver development via repressing estrogen biosynthesis in placental trophoblasts - Yi-Ting Fu; Jin Zhang; Wei-Bo Liu; Yu-Feng Zhang; Shuang Zhang; Lu-Lu Tan; Qing Lin; Kong-Wen Ou-Yang; Yong-Wei Xiong; Wei Chang; Hao Li; Jun-Ying Yu; et al. (Food and Chemical Toxicology, 2023)

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

A temporally relaxed theory of physically or chemically non-equilibrium solute transport in heterogeneous porous media - Ying-Fan Lin; Junqi Huang; Elliot J. Carr; Tung-Chou Hsieh; Hongbin Zhan; Hwa-Lung Yu (Journal of Hydrology, 2023)

Polyethylene and polypropylene microplastics reduce chemisorption of cadmium in paddy soil and increase its bioaccessibility and bioavailability - Jing-Jie Guo; Fen Li; Hai-Chuan Xiao; Bai-Lin Liu; Lin-Nan Feng; Peng-Fei Yu; Can Meng; Hai-Ming Zhao; Nai-Xian Feng; Yan-Wen Li; Quan-Ying Cai; Lei Xiang; et al. (Journal of Hazardous Materials, 2023)

Microplastics affect arsenic bioavailability by altering gut microbiota and metabolites in a mouse model - Shan Chen; Jin-Lei Yang; Yao-Sheng Zhang; Hong-Yu Wang; Xin-Ying Lin; Rong-Yue Xue; Meng-Ya Li; Shi-Wei Li; Albert L. Juhasz; Lena Q. Ma; Dong-Mei Zhou; Hong-Bo Li (Environmental Pollution, 2023)

QTL-seq and transcriptomic integrative analyses reveal two positively regulated genes that control the low-temperature germination ability of MTP–maize introgression lines - Ru-Yu He; Jun-Jun Zheng; Yu Chen; Ze-Yang Pan; Tao Yang; Yang Zhou; Xiao-Feng Li; Xinyi Nan; Ying-Zheng Li; Ming-Jun Cheng; Yan Li; Yang Li; et al. (Theoretical and Applied Genetics, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Aestuariibaculum lutulentum sp. nov., a marine bacterium isolated from coastal sediment in Beihai - Jia-Wei Gao; Dong-Yan He; Wen-Wu Zhang; Yu-Ruo Wang; Yue Su; Jun-Jie Ying; Zhi-Cheng Wu; Wu Qu; Lin Xu; Cong Sun (Archives of Microbiology, 2023)

Transition of carbon-nitrogen coupling under different anthropogenic disturbances in subtropical small mountainous rivers - Li-Chin Lee; Gabriele Weigelhofer; Thomas Hein; Shin-Chien Chan; Ying-San Liou; Chien-Sen Liao; Fuh-Kwo Shiah; Yu-Lin Yu; Tsung-Yu Lee; Jr-Chuan Huang (Science of The Total Environment, 2023)

Two new germacrane sesquiterpenoids from the inflorescences of Mikania micrantha - Tao Lou; Qiao-Lin Xu; Yu-Ling Tan; Shao-Bo Liu; Shan-Xuan Zhang; Ying Zeng; Feng-Qiang Jiang; Jian-Wen Tan (Phytochemistry Letters, 2023)

Biofouling-resistant polyamidoxime-based natural hierarchical porous bamboo strips prepared by in-situ polymerization for uranium extraction from seawater - Ying Wang; Zaiwen Lin; Jing Yu; Jiahui Zhu; Jingyuan Liu; Qi Liu; Rongrong Chen; Peili Liu; Jun Wang (Journal of Environmental Chemical Engineering, 2023)

Effect of ferulic acid covalent conjugation on the functional properties and antigenicity of β-lactoglobulin - Yu-Ting Xue; Ya-Ning Han; Yan Wang; Ying-Hua Zhang; Yu-Qi Yin; Bo-Hao Liu; Han-Lin Zhang; Xin-Huai Zhao (Food Chemistry, 2023)

The ability of pre-magnetized zero-valent iron for peroxymonosulfate activation to remove ofloxacin - Yang Wu; Jing-ying Zhu; Jia-wen Bai; Li-feng Lin; Chang-ping Yu (Chemical Engineering Journal, 2023)

A novel 4-O-endosulfatase with high potential for the structure-function studies of chondroitin sulfate/dermatan sulfate - Lin Wei; Yingying Xu; Min Du; Ying Fan; Ruyi Zou; Xiangyu Xu; Qingdong Zhang; Yu-Zhong Zhang; Wenshuang Wang; Fuchuan Li (Carbohydrate Polymers, 2023)

α7 nicotinic acetylcholine receptor agonist improved brain injury and impaired glucose metabolism in a rat model of ischemic stroke - Ya-Yu Wang; Shih-Yi Lin; Cheng-Yi Chang; Chih-Cheng Wu; Wen-Ying Chen; Wei-Chi Huang; Su-Lan Liao; Wen-Yi Wang; Chun-Jung Chen (Metabolic Brain Disease, 2023)

Evaluation of imide substance from Streptomyces atratus PY-1 for the biocontrol of Phytophthora blight - Chaoqun Zang; Tingting Kong; Bingbing Liang; Xiaozhou Liu; Jinhui Xie; Ying Lin; Xue Pei; Shuyi Yu; Chunhao Liang (European Journal of Plant Pathology, 2023)

Long-term exposure to particulate matter and COPD mortality: Insights from causal inference methods based on a large population cohort in southern China - Ying Wang; Zhicheng Du; Yuqin Zhang; Shirui Chen; Shao Lin; Philip K. Hopke; David Q. Rich; Kai Zhang; Xiaobo X. Romeiko; Xinlei Deng; Yanji Qu; Yu Liu; et al. (Science of The Total Environment, 2023)

Roles of radical species in vacuum-UV/UV/peroxydisulfate advanced oxidation processes and contributions of the species to contaminant degradation at different water depths - Yu-Jia Nong; Yi-Lin Zhang; Uwe Hübner; Wen-Long Wang; Qian-Yuan Wu; Nan Huang; Jörg E. Drewes; Hong-Ying Hu (Journal of Hazardous Materials, 2023)

Modeling collective motion for fish schooling via multi-agent reinforcement learning - Xin Wang; Shuo Liu; Yifan Yu; Shengzhi Yue; Ying Liu; Fumin Zhang; Yuanshan Lin (Ecological Modelling, 2023)

Spinal P2X4 Receptors Involved in Visceral Hypersensitivity of Neonatal Maternal Separation Rats - Ying Tang; Li Chen; Bin Liu; Pei Sun; Zhong Chen; Yang Huang; Chen Ai-qin; Yu Chen; Chun Lin (Purinergic Signalling, 2023)

Sex difference on fibroblast growth factors (FGFs) expression in skin and wound of streptozotocin(STZ)-induced type 1 diabetic mice - Nuo-qi Wang; Wei-hua Jia; Lin Yin; Na Li; Mei-dai Liang; Jia-min Shang; Bi-yu Hou; Li Zhang; Gui-fen Qiang; Guan-hua Du; Xiu-ying Yang (Molecular Biology Reports, 2023)

RNA-seq analysis reveals the effect of the metamorphic cue (juvenile oysters) on the Rapana venosa larvae - Mei-Jie Yang; Ying Shi; Zhi-Shu Lin; Pu Shi; Zhi Hu; Cong Zhou; Peng-Peng Hu; Zheng-Lin Yu; Tao Zhang; Hao Song (Frontiers in Marine Science, 2023)
As a vital developmental event, metamorphosis controls the population dynamics of most marine invertebrates and affects the breeding of economic shellfish. Rapana venosa is an economically important species in China, but artificial aquaculture has hampered its metamorphosis process. Previous studies have found that juvenile oysters can effectively induce the metamorphosis of R. venosa , but the specific induction mechanism is not clear. Here, we investigated the mechanism underlying the response of R. venosa to juvenile oysters through the RNA-seq analysis. In this study, the gene set responses to metamorphosis cues (juvenile oysters) in R. venosa were identified, and GO and KEGG enrichment analyses were further performed on these gene sets. The results showed that the expression of the prototype of the class of immediate early genes, the transcription factor AP-1, was rapidly and significantly increased, and the molecular chaperone of NOS, HSP90, exhibited lower expression in the M12 group than in the control group. In contrast, the expression of inhibitors of apoptosis (IAPs) was significantly increased upon exposure to juvenile oysters. Additionally, the Wnt signaling pathway and MAPK signaling pathway were enriched in the trend analysis. These pathways may also play critical regulatory roles in the response to juvenile oysters. Taken together, the results show that competent larvae rapidly respond to the inducing effects of oysters via some immediate early genes, such as the transcription factor AP-1, which may further regulate downstream pathways such as the MAPK signaling pathway to cause subsequent changes, including a decrease in HSP90 and an increase in IAPs. These changes together may regulate the metamorphosis of R. venosa . This study provides further evidence that juvenile oysters are the metamorphosis cues of R. venosa , which may enhance our understanding of the metamorphosis mechanism in this marine invertebrate.

Butyl benzyl phthalate as a key component of phthalate ester in relation to cognitive impairment in NHANES elderly individuals and experimental mice - Yongquan Yu; Yucheng Wang; Yu Dong; Shuge Shu; Di Zhang; Jiayi Xu; Ying Zhang; Wei Shi; Shou-Lin Wang (Environmental Science and Pollution Research, 2023)

Ecological value of mariculture shellfish resources in China: Assessment and management - Chun-Yu Lin; Gui-Lin Dai; Yang Liu; Meng-Qi Zhang; Ying Liu; Wen Jiang; Xiu-Mei Fu; Han-Xue Chen (Marine Policy, 2023)

Triclocarban and triclosan exacerbate high-fat diet-induced hepatic lipid accumulation at environmental related levels: The potential roles of estrogen-related receptors pathways - Xin Li; Jia-Da Zhang; Han Xiao; Sen He; Ting-Ting He; Xiao-Min Ren; Bing-Hua Yan; Lin Luo; Yu-Long Yin; Lin-Ying Cao (Science of The Total Environment, 2023)

Antibacterial activity and mechanism of action of bacteriocin LFX01 against Staphylococcus aureus and Escherichia coli and its application on pork model - Wei-Gang Xin; Gang Wu; Jian-Ping Ying; Yi-Zhou Xiang; Yu-Hang Jiang; Xian-Yu Deng; Lian-Bing Lin; Qi-Lin Zhang (Meat Science, 2023)

Emission, partition, and formation pathway of polychlorinated dibenzo-p-dioxins and dibenzofurans during co-disposal of industrial waste with municipal solid waste - Yuxuan Ying; Yunfeng Ma; Xiaoxiao Wang; Hong Yu; Angjian Wu; Shengyong Lu; Xiaodong Li; Xiaoqing Lin; Lijun Liu; Wenhua Yin (Journal of Environmental Chemical Engineering, 2023)

Comprehensive application possibility: Construction hydrophilic, amphiphilic and hydrophobic system of modified zein by enzymatic or cysteine modification - An-Qi Zhang; Xiao-Yan Li; Bo-Hao Liu; Yu-Qi Yin; Han-Lin Zhang; Ying-Hua Zhang (Food Hydrocolloids, 2023)

Engineering electron redistribution of bimetallic phosphates with CeO2 enables high-performance overall water splitting - Xin Guo; Menggang Li; Longyu Qiu; Fenyang Tian; Lin He; Shuo Geng; Yequn Liu; Ying Song; Weiwei Yang; Yongsheng Yu (Chemical Engineering Journal, 2023)

Cholesterol homeostasis regulated by ABCA1 is critical for retinal ganglion cell survival - Jialiang Yang; Yuhong Chen; Tongdan Zou; Bai Xue; Fang Yang; Xiangzhou Wang; Yibo Huo; Boyun Yan; Yuxia Xu; Shiyu He; Yi Yin; Jing Wang; et al. (Science China Life Sciences, 2023)

The detection of major clades and new species of Mallocybe (Inocybaceae, Agaricales) from China with elongate cheilocystidia - Jian-Hua Hu; Wen-Jie Yu; Lun-Sha Deng; Yu-Guang Fan; Tolgor Bau; Li-Ping Tang; Wen-Fei Lin; Chun-Ying Deng (Mycological Progress, 2023)

Seasonal spermatogenesis, epididymal storage, and creatine kinase expression in Pelodiscus sinensis - Yu-Fei Yang; Jia-Hao Wu; Run-Lan Lin; Shang-Jun Yin; Guo-Ying Qian; Wei Wang; Yong-Doo Park (Animal Reproduction Science, 2023)

A fluorescent probe based on a phenylalanine derivative is capable of sequential detection of Zn2+ and Cys/His - Qiu-Yu Yu; Chuan-Wan Wei; Xiao-Juan Wang; Shu-Qin Gao; Xin-Yi Tong; Ying-Wu Lin (JBIC Journal of Biological Inorganic Chemistry, 2023)

Evaluating the release and metabolism of ricinine from castor cake fertilizer in soils using a LC-QTOF/MS coupled with SIRIUS workflow - Kai-Xuan Zheng; Cheng-Hua Liu; Sichao Wang; Yu-Min Tzou; Chih-Min Chiang; Shiou-Ruei Lin; Hsiao-Ying Yang; Jerry J. Wu; Ya-Hui Chuang (Chemosphere, 2023)

Formation pathways, gas-solid partitioning, and reaction kinetics of PCDD/Fs associated with baghouse filters operated at high temperatures: A case study - Xiaoqing Lin; Xiaoxiao Wang; Yuxuan Ying; Angjian Wu; Zhiliang Chen; Lei Wang; Hong Yu; Hao Zhang; Aizhong Ruan; Xiaodong Li; Jianhua Yan (Science of The Total Environment, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Seasonal variations of low molecular alkyl amines in PM2.5 in a North China Plain industrial city: Importance of secondary formation and combustion emissions - Xiao-Ying Yang; Fang Cao; Mei-Yi Fan; Yu-Chi Lin; Feng Xie; Yan-Lin Zhang (Science of The Total Environment, 2023)

Triclosan in paired-maternal and cord blood, and their relationships with congenital heart disease of baby - Yu-Ling Luan; Yan-Qiu Ou; Xiao-Qing Liu; Shao Lin; Ying Guo (Science of The Total Environment, 2023)

Experimental study on the distribution law of the blade foot resistance of a large deep-water open caisson in sand - Bing-nan Jiang; Ting Yu; Wen-ming Peng; Ying-bin Zhang; Shun-bin He; Jian-lin Ma (Ocean Engineering, 2023)

A low-cost eco-friendly fast drug extraction (FaDEx) technique for environmental and bio-monitoring of psychoactive drug in urban water and sports-persons’ urine samples - Swapnil Gurrani; Karthikeyan Prakasham; Jess Lim Zii Ying; Jentaie Shiea; Yi-Jia Ku; Yu-Chia Lin; Po-Chin Huang; Gangadhar Andaluri; Kung-Che Lee; Vinoth Kumar Ponnusamy (Environmental Research, 2023)

Lightweight Flexible Polyimide-Derived Laser-Induced Graphenes for High-Performance Thermal Management Applications - Yu-Sheng Hsiao; Cai-Wan Chang-Jian; Tzu-Yen Huang; Ying-Lin Chen; Chung-Wei Huang; Jen-Hsien Huang; Nian-Jheng Wu; Shih-Chieh Hsu; Chih-Ping Chen (Chemical Engineering Journal, 2023)

Characterising the influence of acid rain on the growth and physiological characteristics of Mirabilis jalapa Linn. in southern China - Lan-ying Chen; Lin Wang; Hao-yu Wang; Xun Zhu (Acta Physiologiae Plantarum, 2023)

Physiological and transcriptome analysis of Mytilus coruscus in response to Prorocentrum lima and microplastics - Xiao-wen Tang; Rong Yu; Mei-hua Fan; Zhi Yang; Zhi Liao; Zong-xin Yang; Chen-ying Xie; Yu-kun Xuan; Jian-xin Wang; Xiao-lin Zhang; Xiao-jun Yan (Frontiers in Marine Science, 2022)
Nowadays, diarrheic shellfish toxicity (DSP) toxin and microplastics (MPs) are commonly found in coastal waters worldwide. Due to their widespread use, their persistence and toxicity, they may induce adverse effects on Mytilus coruscus . However, the underlying toxic mechanisms of DSP and MPs on M. coruscus remain unclear. This study explored the physiological index and transcriptome change of the digestive gland of adult M. coruscus exposed for 3 days to polystyrene (PS) MPs (0.2 mg/L, 90-100 μm) and Prorocentrum lima alone or in combination. The results showed that the CAT activity and MDA content significantly increased, respiration rate and feeding rate significantly decreased. The combination of MPs and P. lima caused more structural damage to the rough surface endoplasmic reticulum and mitochondria in the digestive glands of M. coruscus . The transcriptome analysis showed that 485 and 220 genes were up- and down-regulated, respectively, after exposure to P. lima ; 1,989 up-regulated DEGs and 1,098 down-regulated DEGs were identified after exposure to MP treatment, and 1,004 up-regulated DEGs and 664 down-regulated DEGs were identified after exposure to the combination of P. lima and MPs. The DEGs were mainly enriched in the lysosome, mRNA surveillance pathway, carbon metabolism, the mTOR signaling pathway, the complement and coagulation cascades, and the TNF signaling pathway. The MP, P. lima exposure mainly induced the expression of RNA-binding protein musashi, serine/arginine repetitive matrix protein 1, low affinity immunoglobulin epsilon Fc receptor, toll-like receptor 2, caspase 7, calmodulin, E3 ubiquitin-protein ligase, serine/threonine-protein kinase PRP4, glutathione S-transferase, and heat shock 70 kDa protein. MPs and P. lima poison mainly influence the expression of RNA transport, immune related gene, apoptosis, signal related gene, and antioxidant gene change. The combination of MPs and P. lima has a synergistic toxic effect. This study provides a new insights into its physiological and molecular responses of M. coruscus to MPs and P. lima toxic exposure.

Phycospheric bacterial community structure and function succession during the typical harmful macroalgal blooms - Tongfei Qu; Chengzong Hou; Chen Guan; Xinyu Zhao; Jun Chen; Yi Zhong; Jinhui Xu; Zhihao Lin; Yu Xu; Xuexi Tang; Ying Wang (Frontiers in Marine Science, 2022)
Based on the diversity and importance of phycospheric microorganisms as well as their complex interaction with algae, their ecological correlation with algal bloom events has become a research topic of great interest that remains unclear in the natural dynamic process of harmful macroalgal blooms (HMBs). The world’s largest green tides caused by macroalgae Ulva prolifera have occurred in the Yellow Sea for 16 consecutive years, and seriously affected the coastal ecosystem. Here, we monitored the spatiotemporal dynamics of the phycospheric bacterial community during the U . prolifera green tide bloom. The 73-day continuous field survey covered the whole process of initial invasion until the extinction of the green tide. The phycospheric bacterial community has a higher richness than the control seawater bacteria; in addition, it has more enriched taxa with organic nutrition preference and environmental pressure adaption, such as Bacteroidetes, Firmicutes, and Desulfobacterota. The same differences in populations and functional profiles were observed among the epiphytic bacterial and phycospheric seawater bacterial communities, which may be driven by the spatial heterogeneity of biogenic elements (e.g., organic nutrients and oxygen) among the habitats. Significant succession occurred in both the epiphytic bacterial and phycospheric seawater bacterial communities; their diversity and richness exhibited significant heterogeneity variation patterns, and their community structure became more similar in late phases. Our study revealed that macroalgal phycospheric microbial communities have a highly complex and dynamic composition and variable ecological functions, which indicate that phycospheric microorganisms are closely related to the fate of HMBs and may have the profound effect coastal biogeochemical cycles.

Mesenchymal Stem Cell Secreted-Extracellular Vesicles are Involved in Chondrocyte Production and Reduce Adipogenesis during Stem Cell Differentiation - Yu-Chen Tsai; Tai-Shan Cheng; Hsiu-Jung Liao; Ming-Hsi Chuang; Hui-Ting Chen; Chun-Hung Chen; Kai-Ling Zhang; Chih-Hung Chang; Po-Cheng Lin; Chi-Ying F. Huang (Tissue Engineering and Regenerative Medicine, 2022)
Background: Extracellular vesicles (EVs) are derived from internal cellular compartments, and have potential as a diagnostic and therapeutic tool in degenerative disease associated with aging. Mesenchymal stem cells (MSCs) have become a promising tool for functional EVs production. This study investigated the efficacy of EVs and its effect on differentiation capacity. Methods: The characteristics of MSCs were evaluated by flow cytometry and stem cell differentiation analysis, and a production mode of functional EVs was scaled from MSCs. The concentration and size of EVs were quantitated by Nanoparticle Tracking Analysis (NTA). Western blot analysis was used to assess the protein expression of exosome-specific markers. The effects of MSC-derived EVs were assessed by chondrogenic and adipogenic differentiation analyses and histological observation. Results: The range of the particle size of adipose-derived stem cells (ADSCs)- and Wharton’s jelly -MSCs-derived EVs were from 130 to 150 nm as measured by NTA, which showed positive expression of exosomal markers. The chondrogenic induction ability was weakened in the absence of EVs in vitro . Interestingly, after EV administration, type II collagen, a major component in the cartilage extracellular matrix, was upregulated compared to the EV-free condition. Moreover, EVs decreased the lipid accumulation rate during adipogenic induction. Conclusion: The results indicated that the production model could facilitate production of effective EVs and further demonstrated the role of MSC-derived EVs in cell differentiation. MSC-derived EVs could be successfully used in cell-free therapy to guide chondrogenic differentiation of ADSC for future clinical applications in cartilage regeneration.

An association study on the risk, glucocorticoids effectiveness, and prognosis of systemic lupus erythematosus: insight from mitochondrial DNA copy number - Zhen Li; Qi-Qun Zong; Chun-Xia Zhai; Guang-Hui Yu; Wan-Qin Hu; Yu-Hua Wang; Lin-Lin Wang; Zi-Ye Yan; Ting-Yu Zhang; Ying Teng; Shuang Liu; Jing Cai; et al. (Immunologic Research, 2022)

Taxonomy and phylogeny of Pseudovorticella ciliates (Ciliophora, Peritrichia): Two new and one rare species from the coastal waters of China - Yong Zhang; Ying Yu; Zhishuai Qu; Mengmeng Jiang; Zhuo Shen; Jiqiu Li; Xiaofeng Lin (Frontiers in Marine Science, 2022)
Peritrich ciliates are a species-rich group of sessile unicellular eukaryotes, which can be found in various aquatic habitats from all over the world. It is well accepted that there are still many ciliates to be uncovered. During a survey on ciliate biodiversity in the coastal waters of China, three solitary peritrich species were identified as members of the genus Pseudovorticella Foissner & Schiffmann, 1975, including two new species and a rare one. Pseudovorticella zhejiangensis sp. n. differs from its congeners mainly by having a conical-shaped zooid, conspicuous pellicular blisters, one ventral and one dorsal contractile vacuoles, and an infundibular polykinety 3 with three rows of nearly equal length but different beginning positions. Pseudovorticella dalianensis sp. n. can be defined mainly by an obovoid-shaped zooid, one ventral contractile vacuole, and a three-rowed infundibular polykinety 3 with the middle row being the longest. The rare species, Pseudovorticella verrucosa (Dons, 1915) Sun et al., 2009, was redescribed. The small subunit (SSU) rDNA sequences of these three species were sequenced for the first time, the phylogeny of Pseudovorticella species was analyzed, and the results verified the non-monophyly of this genus. This study demonstrates that the morphologic and gene barcoding data are the optimum combination to disclose the biodiversity of ciliates.

7,8-Dihydroxyflavone attenuates the virulence of Staphylococcus aureus by inhibiting alpha-hemolysin - Nan Bian; Xiangqian Chen; Xinran Ren; Zishu Yu; Mengli Jin; Xiaoyu Chen; Chang Liu; Yanhe Luan; Lin Wei; Ying Chen; Wu Song; Yicheng Zhao; et al. (World Journal of Microbiology and Biotechnology, 2022)

Synthesis and biological evaluation of new thiazolyl-urea derivatives as potential dual C-RAF/FLT3 inhibitors - Zhi-Hua Zhang; Bi-Fan Zeng; Zhe-Xue Song; Ying-Yu Yang; Kai-yun Zhang; Xue Du; Lin-lin Zhang; Dong Cai (Medicinal Chemistry Research, 2022)

A Facile, Label-free and Versatile Fluorescence Sensing Nanoplatform Based on Titanium Carbide Nanosheets for the Detection of Various Targets - Meishuang Liang; Bixia Lin; Zhijiao Tang; Li Zhang; Manli Guo; Yujuan Cao; Yumin Wang; Ying Yu (Journal of Fluorescence, 2022)

Impact of Petroleum Contamination on the Structure of Saline Soil Bacterial Communities - Ying Zhang; Xiaojie Sun; Cheng Qian; Lin Li; Xiufang Shang; Xinfeng Xiao; Yu Gao (Current Microbiology, 2022)

Behavioral and transcriptomic changes in butenolide treated larvae of the cosmopolitan fouling bryozoan Bugulina (Bugula) neritina - Jin-You Liang; Yi-Fan Cheng; Xiao-Lin Huang; Ying Xu; Yue Him Wong; Yu Zhang (Frontiers in Marine Science, 2022)
The arborescent bryozoan Bugulina neritina is a cosmopolitan fouling species in sub-tropical to sub-temperate waters. The butenolide compound 5-octylfuran-2(5H)-one (hereafter named butenolide) reportedly inhibits larval settlement of B. neritina , but its effect on the larval behavioral and transcriptomic responses remained unclear. We report that 10 μg mL -1 or higher concentration of butenolide and/or prolonged treatment (10 h or longer) resulted in significant increase in larval mortality and prominent spiral larval swimming behavior. The transcriptomic analyses not only revealed up-regulation of typical stress-related protein genes in response to 10 mg mL -1 butenolide treatment, but also indicated up-regulation of mucin , synaptic genes and nitric oxide signaling genes. In addition, the expression of developmental genes and lipid biosynthesis genes were also affected. Overall, our larval behavior and transcriptome analyses reflected the impact of butenolide on the metabolism, neuronal and molecular signaling in B. neritina larvae.

Identification and characteristic analysis of urban vegetation spectra under different dust deposition - Xumiao Yu; Wenpeng Lin; Dan Wang; Ying Li; Yue Sun (Environmental Science and Pollution Research, 2022)

Evaluation of the Potential of the Hard Clam (Meretrix meretrix) Shell Which Can Be Used as the Bioindicator for Heavy Metal Accumulation - Yen-Ting Lin; Fang-Chi Chang; Ming-Tsung Chung; Ze-Kai Li; Chang-Chuan Chan; Ying-Sheng Huang; Kuo-Fang Huang; Yu-San Han (Fishes, 2022)
Clams, Meretrix meretrix, were one of the favorite aquatic products in Taiwan and the world. It was reported that the water pollutants such as heavy metals and chemicals might accumulate in the clam body and shell through filter-feeding behavior. Thus, the bivalves could be used as bioindicators in the aquatic environment. The present study analyzed 20 trace elements, Mg, Sr, Li, Cd, Ba, Mn, Al, U, Ti, Pb, Nd, B, S, Zn, Fe, P, Na, K, Cu, and Ni, in the shells of the clams collected from the wild coastal area and cultured ponds to evaluate which elements have the potential to be biomarkers. The concentrations of 20 elements were detected by Solution-Based Inductively Coupled Plasma Mass Spectrometry (SB-ICPMS). Among them, Cd, Al, U, Ti, Nd, S, and K were below the detection limit. The remaining elements were analyzed for accumulation. The levels of Zn, Fe, and Ni possess high variation in an identical environment; so, a PCA was conducted without these three elements to reduce noise. The PCA result proved that the clam could absorb specific trace elements from the habitat. After a period of time, the contents of the absorption in the shells of the clams living in an identical environment became more similar. The analyzed element, Pb, was not found with a special difference in this study. The levels of Na, Sr, Mg, B, Mn, P, Ba, Li, and Cu reflected different sampling sites, which suggested that these elements in the species M. meretrix had the potential to be used as biomarkers for assessing heavy metal accumulation in the environment.

The influence of climate change on the allocation efficiency of new and tradition energy - Kuei-Ying Huang; Yung-ho Chiu; Tzu-Han Chang; Tai-Yu Lin (Environmental Science and Pollution Research, 2022)

Construction of a core germplasm bank of upland cotton (Gossypium hirsutum L.) based on phenotype, genotype and favorable alleles - Peng Han; Xiaomin Tian; Ying Wang; Cong Huang; Yizan Ma; Xiaofeng Zhou; Yu Yu; Dawei Zhang; Haijiang Xu; Yang Cao; Bo Zhu; Zhenxiu Feng; et al. (Genetic Resources and Crop Evolution, 2022)

Methods to control harmful algal blooms: a review - Barathan Balaji-Prasath; Ying Wang; Yu Ping Su; David P. Hamilton; Hong Lin; Luwei Zheng; Yong Zhang (Environmental Chemistry Letters, 2022)

ZAKβ Alleviates Oxidized Low-density Lipoprotein (ox-LDL)-Induced Apoptosis and B-type Natriuretic Peptide (BNP) Upregulation in Cardiomyoblast - Yueh-Min Lin; Jiro Hasegawa Situmorang; Jia-Zun Guan; Dennis Jine-Yuan Hsieh; Jaw-Ji Yang; Michael Yu-Chih Chen; Ching-Hui Loh; Chia-Hua Kuo; Shang-Yeh Lu; Ying-Ming Liou; Chih-Yang Huang (Cell Biochemistry and Biophysics, 2022)

Oral Magnesium Supplementation for the Prevention of Preeclampsia: a Meta-analysis or Randomized Controlled Trials - Jing Yuan; Ying Yu; Tongyu Zhu; Xiaohan Lin; Xincheng Jing; Juan Zhang (Biological Trace Element Research, 2022)

Fissistiganoids A and B: two new flavonoids from the Fissistigma tungfangense - Wan-Lin Zhong; Xue-Ming Zhou; Ji-Ling Yi; Xin-Ming Song; Bin Zhang; Jing-Yu Yang; Guang-Ying Chen (Natural Product Research, 2022)

Investment Feasibility Analysis of Large Submersible Cage Culture in Taiwan: A Case Study of Snubnose Pompano (Trachinotus anak) and Cobia (Rachycentron canadum) - Hsun-Yu Lan; Farok Afero; Cheng-Ting Huang; Bo-Ying Chen; Po-Lin Huang; Yen-Lung Hou (Fishes, 2022)
Onshore farming for premium aquaculture is under scrutiny and criticism partially due to possible causes of adverse environmental impacts on other resource users and the surrounding environment. The best alternative to preventing or minimizing these impacts is to utilize open seawater by large submersible cage culture. The current operation in Taiwan has demonstrated that the culture operation is technically feasible but economically demanding because of high capital and operating costs. Therefore, this study conducted an economic analysis of the expansion of large submersible cage culture by selecting two premium species of snubnose pompano (Trachinotus anak) and cobia (Rachycentron canadum) and examined the profitability of large submersible cage culture investment. This study found that the current operation of four-unit cages highlighted a negative net present value and internal rate of return with a payback period of over ten and six years, respectively. Large submersible cage culture can be financially profitable when its operation unit expands from 8 to 24 units. Increasing unit cages to eight incurred a gross margin of 17.09%, BCR 1.21, with a payback period of 5.36 years. Expanding the operation to 24-unit cages was a potentially lucrative investment with a gross margin of 18.51%, BCR 1.23, PI 2.15, internal rate of return of 20.84%, and a payback period of 3.55 years. Sensitivity analyses revealed that market price and survival rate significantly impact the profitability of large submersible cage culture. Finally, it is suggested that producers could invest in 8-unit cages and maintaining the survival rate of snubnose pompano and cobia at 80% and 40%, respectively.

Lactobacillus plantarum PS128 Promotes Intestinal Motility, Mucin Production, and Serotonin Signaling in Mice - Chih-Ming Chen; Chien-Chen Wu; Chin-Lin Huang; Min-Yu Chang; Shih-Hsuan Cheng; Ching-Ting Lin; Ying-Chieh Tsai (Probiotics and Antimicrobial Proteins, 2022)
Lactobacillus plantarum PS128 has been reported as a psychobiotic to improve mental health through the gut–brain axis in experimental animal models. To explore its mechanism of action in the gut, this study aimed to analyze the effects of L. plantarum PS128 ingestion on naïve and loperamide (Lop)-induced constipation mice. We found that, in the two mouse models, the weight, number, and water content of feces in the L. plantarum PS128 group were higher than those in the vehicle control group. Histological observation revealed that L. plantarum PS128 increased the level of colonic mucins including the major mucin MUC2. In addition, the charcoal meal test showed that L. plantarum PS128 significantly increased the small intestine transit in naïve mice, but not in the Lop-treated mice. Since intestinal serotonin has been found to modulate motility, we further analyzed the expression of genes related to serotonin signal transduction in the small intestine of naïve mice. The results showed that L. plantarum PS128 significantly altered the expression levels of Tph1 , Chga , Slc6a4 , and Htr4 , but did not affect the expression levels of Tph2 , Htr3a , and Maoa . Furthermore, immunohistochemistry revealed that L. plantarum PS128 significantly increased the number of serotonin-containing intestinal cells in mice. Taken together, our results suggest that L. plantarum PS128 could promote intestinal motility, mucin production, and serotonin signal transduction, leading to a laxative effect in mice.

Use of piggyBac Transposon System Constructed Murine Breast Cancer Model for Reporter Gene Imaging and Characterization of Metastatic Tumor Cells - Ying-Ling Chen; Yung-Cheng Wang; Kuei-Yuan Hou; Min-Ying Lin; Yu-Chuan Lin; Hui-Yen Chuang; Yi-Jang Lee (Journal of Medical and Biological Engineering, 2022)

Natural Feed Supplements Improve Growth, Non-Specific Immune Responses and Resistance against Vibrio alginolyticus in Lates calcarifer - Zhen-Hao Liao; Huai-Ting Huang; Yu-Ru Lin; Bo-Ying Chen; Yi-Fan Lee; Yuan-Heng Lin; Chieh-Yuan Chuang; Fan-Hua Nan (Journal of Marine Science and Engineering, 2022)
This study aimed to investigate the effects of dietary natural feed supplement on the growth performance, non-specific responses, and disease resistance in Lates calcarifer. Three commercial products (A, B, and C) containing a basal probiotic mixture were tested. Product A contained a basal mixture of Paenibacillus sp., Bacillus subtilis, Bacillus amyloliquefaciens, and Lactobacillus rhamnosus (107 cfu/g for each probiotic); product B contained additional Lactobacillus plantarum (1010 cfu/g); and product C contained additional soybean peptides (500 g/kg) and garlic powder (1 g/kg). Each product was supplemented into subject diets at dosages of 1 or 2 g/kg (designated as the A1, A2, B1, B2, C1, and C2 groups, respectively). Following an eight-week trial, growth parameters (specific growth rate and feed conversion ratio), non-specific immune responses (O2− production, phagocytic rate, and phagocytic index), and the results of a challenge test against Vibrio alginolyticus were evaluated. The results show that all probiotic supplement groups exhibited an improvement in growth performance compared to the control group (non-probiotic diet). In terms of non-specific immunity parameters, a significant improvement in O2− production was found in the C2 group, whereas significant improvements in phagocytic activity were found in all the B and C groups. The C2 group displayed optimal O2− production, phagocytic rate, and phagocytic index results. For the challenge test, the C groups showed higher Vibrio resistance than the other experimental groups and the control group. These results suggest that product C, given at dosages of 2 g/kg, may serve as a growth-promoting and immunostimulatory additive for the cultivation of Asian seabass.

Metabolic tuning of a stable microbial community in the surface oligotrophic Indian Ocean revealed by integrated meta-omics - Zhang-Xian Xie; Ke-Qiang Yan; Ling-Fen Kong; Ying-Bao Gai; Tao Jin; Yan-Bin He; Ya-Yu Wang; Feng Chen; Lin Lin; Zhi-Long Lin; Hong-Kai Xu; Zong-Ze Shao; et al. (Marine Life Science & Technology, 2022)
Understanding the mechanisms, structuring microbial communities in oligotrophic ocean surface waters remains a major ecological endeavor. Functional redundancy and metabolic tuning are two mechanisms that have been proposed to shape microbial response to environmental forcing. However, little is known about their roles in the oligotrophic surface ocean due to less integrative characterization of community taxonomy and function. Here, we applied an integrated meta-omics-based approach, from genes to proteins, to investigate the microbial community of the oligotrophic northern Indian Ocean. Insignificant spatial variabilities of both genomic and proteomic compositions indicated a stable microbial community that was dominated by Prochlorococcus , Synechococcus , and SAR11. However, fine tuning of some metabolic functions that are mainly driven by salinity and temperature was observed. Intriguingly, a tuning divergence occurred between metabolic potential and activity in response to different environmental perturbations. Our results indicate that metabolic tuning is an important mechanism for sustaining the stability of microbial communities in oligotrophic oceans. In addition, integrated meta-omics provides a powerful tool to comprehensively understand microbial behavior and function in the ocean.

Bioeconomic evaluation of Eleutheronema tetradactylum farming: a case study in Taiwan - Cheng-Ting Huang; Farok Afero; Fang-Yu Lu; Bo-Ying Chen; Po-Lin Huang; Hsun-Yu Lan; Yen-Lung Hou (Fisheries Science, 2022)

Ocean Currents May Influence the Endolithic Bacterial Composition in Coral Skeletons - Po-Yu Liu; Sung-Yin Yang; Chih-Ying Lu; Naohisa Wada; Stéphane De Palmas; Shu-Shuo Yeh; Hideyuki Yamashiro; Sen-Lin Tang; Shan-Hua Yang (Frontiers in Marine Science, 2022)
Coral endolithic microbes can be an important nutrients support for hosts while under stresses. Previous studies have found that the endolithic microbial composition of a single coral species can be biogeographical diverse. However, the potential environmental factors, such as salinity, temperature, pH, and nutrient, that might influence the composition of the endolithic microbes remain unclear. In this study, we used both amplicon sequence variants (ASV) and a kmer-based taxonomic unit (KTU) to characterize the endolithic bacterial constitution of Isopora spp. located in the western Pacific Ocean—where it is subjected to the Kuroshio Current (in Okinawa, Japan and Green Island, Taiwan)—and the South China Sea (Dongsha Atoll). The endolithic bacterial community compositions showed a significant geographical difference, and we suggest that the ocean current and primary productivity are the most essential environmental factors influencing the bacterial communities in the skeleton of Isopora spp. In addition, our results showed that, technically, compared to ASV, bacterial composition based on KTU avoids extreme data, making it a suitable tool for explaining the associations between microbes and environmental factors.

The effect of preoperative statin treatment on acute kidney injury in elderly patients undergoing valve replacement surgery - Bing-qi Fu; Xue-biao Wei; Zedazhong Su; Ying-wen Lin; Zu-hui Ke; Tong Tan; Ji-yan Chen; Shou-hong Wang; Dan-qing Yu (European Journal of Clinical Pharmacology, 2022)

Estimation of permafrost thermal behavior using Fourier series model - Yan-yu Zhang; Shu-ying Zang; Lin Zhao; Da-long Ma; Yue Lin; Hao Li (Journal of Mountain Science, 2022)

Description of Aureibaculum luteum sp. nov. and Aureibaculum flavum sp. nov. isolated from Antarctic intertidal sediments - Xiao-yan He; Ning-hua Liu; Chao-yi Lin; Mei-ling Sun; Xiu-lan Chen; Yu-zhong Zhang; Yu-qiang Zhang; Xi-ying Zhang (Antonie van Leeuwenhoek, 2022)

MoOpy2 is essential for fungal development, pathogenicity, and autophagy in Magnaporthe oryzae - Ying‐Ying Cai; Jing‐Yi Wang; Xi‐Yu Wu; Shuang Liang; Xue‐Ming Zhu; Lin Li; Jian‐Ping Lu; Xiao‐Hong Liu; Fu‐Cheng Lin (Environmental Microbiology, 2022)
Summary The development and pathogenicity of the fungus Magnaporthe oryzae , the causal agent of destructive rice blast disease, require it to perceive external environmental signals. Opy2, an overproduction‐induced pheromone‐resistant protein 2, is a crucial protein for sensing external signals in Saccharomyces cerevisiae . However, the biological functions of the homologue of Opy2 in M. oryzae are unclear. In this study, we identified that MoOPY2 is involved in fungal development, pathogenicity, and autophagy in M. oryzae . Deletion of MoOPY2 resulted in pleiotropic defects in hyphal growth, conidiation, germ tube extension, appressorium formation, appressorium turgor generation, and invasive growth, therefore leading to attenuated pathogenicity. Furthermore, MoOpy2 participates in the Osm1 MAPK pathway and the Mps1 MAPK pathway by interacting with the adaptor protein Mst50. The interaction sites of Mst50 and MoOpy2 colocalized with the autophagic marker protein MoAtg8 in the preautophagosomal structure sites (PAS). Notably, the Δ Moopy2 mutant caused cumulative MoAtg8 lipidation and rapid GFP‐MoAtg8 degradation in response to nitrogen starvation, showing that MoOpy2 is involved in the negative regulation of autophagy activity. Taken together, our study revealed that MoOpy2 of M. oryzae plays an essential role in the orchestration of fungal development, appressorium penetration, autophagy and pathogenesis.

Propagation and Separation of Downslope Gravity Currents over Rigid and Emergent Vegetation Patches in Linearly Stratified Environments - Ying-Tien Lin; Yi-Qi Ye; Dong-Rui Han; Yu-Jia Chiu (Journal of Marine Science and Engineering, 2022)
Large eddy simulation (combined with the mixture model) and laboratory experiment were used to investigate the impact of emergent and rigid vegetation on the dynamics of downslope gravity currents in stratified environments. The reliability of the numerical model was assessed with the corresponding laboratory measurements. The results show that the vegetation cylinders lead to severe lateral non-uniformity of the current front, causing more evident lobe and cleft structures. In stratified environments, the smaller driving force leads to less propagating velocity until the current separates from the slope. The transition point (from acceleration to deceleration phases) of current velocity appears earlier as the vegetation becomes denser. The peak value of the bulk entrainment coefficient Ebuik is inversely proportional to the vegetation density, while the final converged value of Ebuik is proportional to the vegetation density. Vegetation patches make the degree of fluctuation of the instantaneous entrainment coefficient Einst more intense, and even negative values appear locally, indicating that the gravity current is detrained into the ambient fluid. The velocity profiles of gravity current develop multi-peak patterns in stratified environments due to fingering intrusive patterns. Our analysis reveals that as the vegetation density increases, the generated wakes behind vegetation cylinders increase local entrainment and mixing, causing the density of current flow from vegetation to decrease and reach the neutral buoyancy layer of ambient fluids earlier, finally leading to a smaller separation depth.

A First Insight Into the Heat-Induced Changes in Proteomic Profiles of the Coral Symbiotic Bacterium Endozoicomonas montiporae - Ya-Fan Chan; Chia-Yu Chen; Chih-Ying Lu; Yung-Chi Tu; Kshitij Tandon; Shinya Shikina; Sen-Lin Tang (Frontiers in Marine Science, 2022)
Endozoicomonas , a core bacterial group in corals, may also be a coral symbiont. Endozoicomonas communities often decrease rapidly in corals under heat stress. However, how the bacteria respond to changes in temperature and coral host during heat stress is unknown. Here, we employed the cultivable, dominant species E. montiporae as a working organism to explore how Endozoicomonas responds to heat stress. We designed two experiments to clarify the extent to which E. montiporae is influenced by temperature and coral host. We detected differentially expressed protein (DEP) profiles in this bacterium at 31 and 33°C compared to 25°C by tandem mass tags-based quantitative proteome analysis. Fifty DEPs, including many heat shock proteins, were detected when the temperature changed. The expression of antioxidant defense proteins and key pyruvate synthase proteins decreased, suggesting that E. montiporae were in a physiology of stress at 33°C. Furthermore, some proteins were differentially expressed because of the heat-stress-treated coral lysate specifically, suggesting that not only heat but also heat-induced host factors can affect the protein expression of the bacterium. This study provides an in-depth analysis of how the molecular mechanisms of Endozoicomonas are affected by heat stress and coral host.

Correction to: Comparative chloroplast genomes of Prunus subgenus Cerasus (Rosaceae): insights into sequence variations and phylogenetic relationships - Jiawen Yan; Jianhui Li; Lin Yu; Wenfu Bai; Dongling Nie; Ying Xiong; Sizheng Wu (Tree Genetics & Genomes, 2022)

New paraconic acids from the endophytic fungus Xylariaceae sp. J4 - Chao Yuan; Xue-Chun Shu; Lin Fan; Ying-Bo Zhang; Ling-Liang Guan; Fu-Lai Yu; Xiao-Lu Chen; Gang Li (Natural Product Research, 2022)

The brown root rot fungus Phellinus noxius affects microbial communities in different root‐associated niches of Ficus trees - Tse‐Yen Liu; Chao‐Han Chen; Yu‐Liang Yang; Isheng J. Tsai; Ying‐Ning Ho; Chia‐Lin Chung (Environmental Microbiology, 2022)
Summary Brown root rot (BRR) caused by Phellinus noxius is a destructive tree disease in tropical and subtropical areas. To understand how BRR affects the composition of the plant rhizoplane‐enriched microbiota, the microbiomes within five root‐associated compartments (i.e., bulk soil, old/young root rhizosphere soil, old/young root tissue) of Ficus trees naturally infected by P. noxius were investigated. The level of P. noxius infection was determined by quantitative PCR. Illumina sequencing of the internal transcribed spacer and 16S rRNA revealed that P. noxius infection caused a significant reduction in fungal diversity in the bulk soil, the old root rhizosphere soil, and the old root tissue. Interestingly, Cosmospora was the only fungal genus positively correlated with P. noxius . The abundance and composition of dominant bacterial taxa such as Actinomadura , Bacillus , Rhodoplanes , and Streptomyces differed between BRR‐diseased and healthy samples. Furthermore, 838 isolates belonging to 26 fungal and 35 bacterial genera were isolated and tested for interactions with P. noxius . Antagonistic activities were observed for isolates of Bacillus , Pseudomonas , Aspergillus , Penicillium , and Trichoderma . Cellophane overlay and cellulose/lignin utilization assays suggested that Cosmospora could tolerate the secretions of P. noxius and that the degradation of lignin by P. noxius may create suitable conditions for Cosmorpora growth.

Comparative chloroplast genomes of Prunus subgenus Cerasus (Rosaceae): insights into sequence variations and phylogenetic relationships - Jiawen Yan; Jianhui Li; Lin Yu; Wenfu Bai; Dongling Nie; Ying Xiong; Sizheng Wu (Tree Genetics & Genomes, 2021)

Realization of Natural Human Motion on a 3D Biped Robot For Studying the Exoskeleton Effective - Chi-Ying Lee; Shih Chieh Lan; Jung-Ji Lin; Yu-Ting Lin; Po-Shen Chiang; Wei-Li Hsu; Kuo-Kuang Jen; Andy Y. S. Huang; Jia-Yush Yen (Journal of Medical and Biological Engineering, 2021)

Sandaracinobacteroides hominis gen. nov., sp. nov., isolated from human skin - Ping-Hua Qu; Hai-Min Luo; Jun-Hui Feng; Song Li; Cha Chen; Lei Dong; Yu-Zhen Ming; Wen-Jun Li; Ying Lin (Archives of Microbiology, 2021)

The ATP Level in the mPFC Mediates the Antidepressant Effect of Calorie Restriction - Qian Wang; Ying Kong; Song Lin; Ding-Yu Wu; Jian Hu; Lang Huang; Wen-Si Zang; Xiao-Wen Li; Jian-Ming Yang; Tian-Ming Gao (Neuroscience Bulletin, 2021)

Associations of Sleep Characteristics with Cerebrospinal Fluid sTREM2 in Cognitively Normal Older Adults: the CABLE Study - He-Ying Hu; Ling-Zhi Ma; Hao Hu; Yan-Lin Bi; Ya-Hui Ma; Xue-Ning Shen; Ya-Nan Ou; Qiang Dong; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2021)

Synthesis and biological evaluation of novel 1,3-diphenylurea quinoxaline derivatives as potent anticancer agents - Gui-Zhen Li; Xi-Lin Ouyang; Zu-Yu Mo; Yao Gu; Xiao-Lin Cao; Li Yang; Hai-Tao Tang; Ying-Ming Pan (Medicinal Chemistry Research, 2021)

Risk of two common glandular cell-type cancers (breast and colorectal cancers) in Chinese occupational chefs: a nationwide ecological study in Taiwan - Pei-Chen Lin; Chiung‑Yu Peng; Chih‑Hong Pan; Jui-Ying Lee; Tusty-Jiuan Hsieh; Yun-Shiuan Chuang; Robert J. Turesky; Chia-Fang Wu; Ming-Tsang Wu (International Archives of Occupational and Environmental Health, 2021)

Refractory organic compounds in coal chemical wastewater treatment by catalytic ozonation using Mn-Cu-Ce/Al2O3 - Kang-He Zhao; Yu-Long Ma; Feng Lin; Shao-Ying Ge; Li Zhu (Environmental Science and Pollution Research, 2021)

Dynamic analysis of residential and enterprise water supply and leakage efficiencies - Ying Li; Yung-ho Chiu; Yushan Li; Hongyi Cen; Tai-Yu Lin (Environmental Science and Pollution Research, 2021)

RSF1 requires CEBP/β and hSNF2H to promote IL-1β-mediated angiogenesis: the clinical and therapeutic relevance of RSF1 overexpression and amplification in myxofibrosarcomas - Chien-Feng Li; Ti-Chen Chan; Cheng-I. Wang; Fu-Min Fang; Po-Chun Lin; Shih-Chen Yu; Hsuan-Ying Huang (Angiogenesis, 2021)

Geographic and subsequent biotic isolations led to a diversity anomaly of section Heterotropa (genus Asarum : Aristolochiaceae) in insular versus continental regions of the Sino‐Japanese Floristic Region - Daiki Takahashi; Shota Sakaguchi; Yu Feng; Yuji Isagi; Ying‐Xiong Qiu; Pan Li; Rui‐Sen Lu; Chang‐Tse Lu; Shih‐Wen Chung; Yang‐Shan Lin; Yun‐Chao Chen; Atsushi J. Nagano; et al. (Journal of Biogeography, 2021)
Aim The Sino‐Japanese Floristic Region has extremely high species diversity with respect to temperate plants; however, the reasons for this diversity are poorly understood because most studies have only considered geographic isolation caused by climatic oscillations. In some plant groups, high floral trait diversity and uneven species diversity between insular systems and the continental area suggest other factors may have important roles too. The primary purpose of this study is to reveal how abiotic and biotic factors have shaped the species diversity anomaly of Heterotropa between the insular systems and the continental area. Location The Sino‐Japanese Floristic Region. Taxon Section Heterotropa (genus Asarum ; Aristolochiaceae). Methods Using ddRAD‐seq and chloroplast genome data, we built a time‐calibrated phylogenetic tree including 79 species. We estimated the patterns of floral traits (flowering time and floral size) evolution using macroevolutionary modelling, and tested the correlation of speciation rate with the trait evolution rates. Finally, we estimated the isolation factors of all taxa pairs and sister‐taxa pairs based on distribution range and floral traits. Results Phylogenetic analysis indicated that Heterotropa was diverged into two clades (continental clade and insular clade) in the Miocene, and the major subclades corresponded to geographic entities. Most rate shifts accelerating floral trait's evolution occurred during the Pleistocene period. Evolution rate of floral traits showed positive correlation with the speciation rate. Large proportion of taxa in the insular clade are distributed allopatrically. Several sister pairs showed floral trait divergence with geographic overlap. Main Conclusions The diversification of Heterotropa appears to have been triggered by geographic and climatic events, and subsequent repeated floral trait evolution with and without geographic isolation. Furthermore, the high species diversity in the insular systems would have been formed by the repeated range fragmentations and contractions. Our study demonstrates the importance of multidimensional studies to understand the diversification process of temperate plants in the Sino‐Japanese Floristic Region.

Seed blends of pyramided Cry/Vip maize reduce Helicoverpa zea populations from refuge ears - Jianguo Guo; Isaac Oyediran; Marlin E. Rice; Sebe Brown; Marcelo Dimase; Shucong Lin; Wade Walker; Wenbo Yu; Ying Niu; Fangneng Huang (Journal of Pest Science, 2021)

Cytotoxic p -terphenyls from the deep-sea-derived Aspergillus candidus - Yu-Kun Lin; Chun-Lan Xie; Cui-Ping Xing; Bao-Qu Wang; Xiao-Xue Tian; Jin-Mei Xia; Ling-Yun Jia; Ying-Ni Pan; Xian-Wen Yang (Natural Product Research, 2021)

Calcium signalling mediated the regulation of growth and polysaccharide accumulation by light quality in Dendrobium officinale protocorms - Ting Lei; Suping Gao; Xiao Lin; Kaihui Zhang; Yingqi Liu; Wenji Li; Di Hu; Xiaofang Yu; Mingyan Jiang; Qibing Chen; Ying Sun (Horticulture, Environment, and Biotechnology, 2021)

Efficiency assessment of coal energy and non-coal energy under bound dynamic DDF DEA - Ying Li; Tai-Yu Lin; Yung-ho Chiu; Hongyi Cen; Yi-Nuo Lin (Environmental Science and Pollution Research, 2021)

Increased resting state functional irregularity of T2DM brains with high HbA1c: sign for impaired verbal memory function? - Xin Zhang; Ying Yu; Zhe-Sheng Shi; Ke Xu; Jia-Hao Feng; Ze-Yang Li; Xiang-Nan Zhang; Shu-Ning Shen; Yang Yang; Lin-Feng Yan; Jin Zhang; Qian Sun; et al. (Brain Imaging and Behavior, 2021)

Western North Pacific Tropical Cyclone Database Created by the China Meteorological Administration - Xiaoqin Lu; Hui Yu; Ming Ying; Bingke Zhao; Shuai Zhang; Limin Lin; Lina Bai; Rijin Wan (Advances in Atmospheric Sciences, 2021)
This paper describes the access to, and the content, characteristics, and potential applications of the tropical cyclone (TC) database that is maintained and actively developed by the China Meteorological Administration, with the aim of facilitating its use in scientific research and operational services. This database records data relating to all TCs that have passed through the western North Pacific (WNP) and South China Sea (SCS) since 1949. TC data collection has expanded over recent decades via continuous TC monitoring using remote sensing and specialized field detection techniques, allowing collation of a multi-source TC database for the WNP and SCS that covers a long period, with wide coverage and many observational elements. This database now comprises a wide variety of information related to TCs, such as historical or real-time locations (i.e., best track and landfall), intensity, dynamic and thermal structures, wind strengths, precipitation amounts, and frequency. This database will support ongoing research into the processes and patterns associated with TC climatic activity and TC forecasting.

New secondary metabolite with cytotoxicity from spawning soft coral Asterospicularia laurae in Taiwan - Jui-Hsin Su; Chih-I Liu; Mei-Chin Lu; Chi-I Chang; Min-Ying Hsieh; Yu-Chi Lin; Chang-Feng Dai; Ya-Han Zhang; Zheng-Yu Lin; Yun-Sheng Lin (Natural Product Research, 2021)

Syndecan-3 contributes to the regulation of the microenvironment at the node of Ranvier following end-to‑side neurorrhaphy: sodium image analysis - Chiung-Hui Liu; Yu-Chen Kuo; Che-Yu Wang; Chao-Chun Hsu; Ying-Jui Ho; Yun-Chi Chiang; Fu-Der Mai; Wei-Jhih Lin; Wen-Chieh Liao (Histochemistry and Cell Biology, 2021)

Delayed association of acute particulate matter 2.5 air pollution exposure with loss of complexity in cardiac rhythm dynamics: insight from detrended fluctuation analysis - Tsung-Ying Tsai; Li-Wei Lo; Shin-Huei Liu; Wen-Han Cheng; Yu-Hui Chou; Wei-Lun Lin; Yenn-Jiang Lin; Shih-Lin Chang; Yu-Feng Hu; Fa-Po Chung; Jo-Nan Liao; Tze-Fan Chao; et al. (Environmental Science and Pollution Research, 2021)

Polycyclic aromatic hydrocarbon and n-alkane pollution characteristics and structural and functional perturbations to the microbial community: a case-study of historically petroleum-contaminated soil - Jian Li; Ying Xu; Quanwei Song; Jie Yang; Lin Xie; Shihang Yu; Lei Zheng (Environmental Science and Pollution Research, 2021)

Effects of degradation succession of alpine wetland on soil organic carbon and total nitrogen in the Yellow River source zone, west China - Chun-ying Lin; Xi-lai Li; Jing Zhang; Hua-fang Sun; Juan Zhang; Hui-bang Han; Qi-hua Wang; Cheng-biao Ma; Cheng-yi Li; Yu-xing Zhang; Xue-qian Ma (Journal of Mountain Science, 2021)

First report of turnip mosaic virus on yellow passion fruit in China - Li Juan Chen; Xing Xing Zhang; Ying Lin Lu; Yu Xing An (Journal of Plant Pathology, 2021)

Experimental evidence for long‐term coexistence of copiotrophic and oligotrophic bacteria in pelagic surface seawater - Yi Li; Zhi‐Bin Wang; Xi‐Ying Zhang; Yan‐Ru Dang; Lin‐Lin Sun; Wei‐Peng Zhang; Hui‐Hui Fu; Gui‐Peng Yang; Min Wang; Andrew McMinn; Xiu‐Lan Chen; Yin Chen; et al. (Environmental Microbiology, 2021)
Summary Most marine copiotrophic bacteria can produce extracellular enzymes to degrade biopolymers into bio‐available smaller solutes, while oligotrophic bacteria usually cannot. Bacterial extracellular enzymes and enzymatic products can be a common resource that could be utilized by both copiotrophs and oligotrophs; when present, oligotrophs may outcompete the enzyme‐producing copiotrophs. However, copiotrophs and oligotrophs consistently coexist in the ocean. How they maintain coexistence has still not been experimentally studied. In this study, the interaction and coexistence of a copiotroph and an oligotroph, isolated from the same surface seawater sample and utilizing the same proteinaceous substrate, were experimentally investigated. The copiotroph could secrete extracellular proteases to degrade and then utilize the proteinaceous substrate. The oligotroph was unable to utilize the proteinaceous substrate by itself, but could grow by using the hydrolysate amino acids. The copiotroph outcompeted the oligotroph by adsorbing the amino acids quickly and having a higher growth rate in the rich medium. The oligotroph survived by adapting to low concentration of nutrients. The copiotroph and oligotroph were able to maintain long‐term (up to 142 days) coexistence in the laboratory. This study indicates that differences in the utilization of different concentrations of nutrients can drive the coexistence of marine copiotrophs and oligotrophs.

TDM-guided medication of polymyxin B in a patient with CRKP-induced bloodstream infection: a case report - Xuben Yu; Jingye Pan; Ziye Zhou; Xin Wen; Ying Dai; Guanyang Lin; Zheng Jiao; Chunhong Zhang (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

First report of ramie mosaic virus on passion fruit in Guangdong, southern China - Li Juan Chen; Dong Lei Sun; Ying Lin Lu; Yu Xing An (Journal of Plant Pathology, 2020)

Optimizing the MIC breakpoints of amoxicillin and tetracycline for antibiotic selection in the rescue therapy of H. pylori with bismuth quadruple regimen - Ming-Tsung Hsieh; Wei-Lun Chang; Chung-Tai Wu; Hsiao-Bai Yang; Hsin-Yu Kuo; Meng-Ying Lin; Hsiu-Chi Cheng; Yu-Chin Tsai; Bor-Shyang Sheu (European Journal of Clinical Pharmacology, 2020)

Cerebral Organoids Repair Ischemic Stroke Brain Injury - Shu-Na Wang; Zhi Wang; Tian-Ying Xu; Ming-He Cheng; Wen-Lin Li; Chao-Yu Miao (Translational Stroke Research, 2020)
Stroke is the second leading cause of death and main cause of disability worldwide, but with few effective therapies. Although stem cell-based therapy has been proposed as an exciting regenerative medicine strategy for brain injury, there are limitations. The developed cerebral organoids (COs) represent a promising transplantation source for stroke that remains to be answered. Here, we transplanted COs at 55 days and explored the feasibility in the rat middle cerebral artery occlusion (MCAO) model of stroke. COs transplantation at 6 h or even 24 h after MCAO significantly reduces brain infarct volume and improves neurological motor function. Transplanted COs show the potential of multilineage differentiation to mimic in vivo cortical development, support motor cortex region-specific reconstruction, form neurotransmitter-related neurons, and achieve synaptic connection with host brain via in situ differentiation and cell replacement in stroke. Cells from transplanted COs show extensive migration into different brain regions along corpus callosum. The mechanisms underlying COs transplantation therapy are also associated with enhanced neurogenesis, synaptic reconstruction, axonal regeneration and angiogenesis, and decreased neural apoptosis with more survival neurons after stroke. Moreover, COs transplantation promotes predominantly exogenous neurogenesis in the transplantation periphery of ipsilateral cortex and predominantly endogenous neurogenesis in the hippocampus and subventricular zone. Together, we demonstrate the efficacy and underlying mechanisms of COs transplantation in stroke. This preliminary but promising study provides first-hand preclinical evidence for COs transplantation as a potential and effective intervention for stroke treatment.

Infusion of Human Mesenchymal Stem Cells Improves Regenerative Niche in Thioacetamide-Injured Mouse Liver - Ying-Hsien Kao; Yu-Chun Lin; Po-Huang Lee; Chia-Wei Lin; Po-Han Chen; Tzong-Shyuan Tai; Yo-Chen Chang; Ming-Huei Chou; Chih-Yang Chang; Cheuk-Kwan Sun (Tissue Engineering and Regenerative Medicine, 2020)

Modification-bioremediation of copper, lead, and cadmium-contaminated soil by combined ryegrass (Lolium multiflorum Lam.) and Pseudomonas aeruginosa treatment - Guang-yu Shi; Ying-jia Yan; Zhi-qiang Yu; Lu Zhang; Yuan-yuan Cheng; Wei-lin Shi (Environmental Science and Pollution Research, 2020)

Roles of MicroRNA-122 in Cardiovascular Fibrosis and Related Diseases - Ying Liu; Jia-Wei Song; Jian-Yu Lin; Ran Miao; Jiu-Chang Zhong (Cardiovascular Toxicology, 2020)

Association Between PSD95 Gene 3′UTR Single Nucleotide Polymorphism and Risk of Acute Ischemic Stroke in Chinese Han Population - Ying-Ying Lin; Tong-ya Yu; Hui Quan; Yu-Juan Chen; Xue-Yuan Liu; Dong-Ya Huang (Journal of Molecular Neuroscience, 2020)

Interferon-α2b spray inhalation did not shorten virus shedding time of SARS-CoV-2 in hospitalized patients: a preliminary matched case-control study - Shao-rui Hao; Ren Yan; Shan-yan Zhang; Jiang-shan Lian; Huan Cai; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Taxonomy and Phylogeny of a New Marine Planktonic Ciliate, Strombidium pseudorapulum sp. n. (Protozoa, Ciliophora, Oligotrichia) - Fenfen Li; Yaoyao Huang; Ying Yu; Weiwei Liu; Xiaofeng Lin (Journal of Ocean University of China, 2020)

Ancestral niche separation and evolutionary rate differentiation between sister marine flavobacteria lineages - Chun‐Xu Xue; Hao Zhang; He‐Yu Lin; Ying Sun; Danli Luo; Yongjie Huang; Xiao‐Hua Zhang; Haiwei Luo (Environmental Microbiology, 2020)
Summary Marine flavobacteria are specialists for polysaccharide degradation. They dominate in habitats enriched with polysaccharides, but are also prevalent in pelagic environments where polysaccharides are less available. These niches are likely occupied by distinct lineages, but evolutionary processes underlying their niche differentiation remain elusive. Here, genomic analyses and physiological assays indicate that the sister flavobacteria lineages Leeuwenhoekiella and Nonlabens likely explore polysaccharide‐rich macroalgae and polysaccharide‐poor pelagic niches respectively. Phylogenomic analyses inferred that the niche separation likely occurred anciently and coincided with increased sequence evolutionary rate in Nonlabens compared with Leeuwenhoekiella . Further analyses ruled out the known mechanisms likely driving evolutionary rate acceleration, including reduced selection efficiency, decreased generation time and increased mutation rate. In particular, the mutation rates were determined using an unbiased experimental method, which measures the present‐day populations and may not reflect ancestral populations. These data collectively lead to a new hypothesis that an ancestral and transient mutation rate increase resulted in evolutionary rate increase in Nonlabens . This hypothesis was supported by inferring that gains and losses of genes involved in SOS response, a mechanism known to drive transiently increased mutation rate, coincided with evolutionary rate acceleration. Our analyses highlight the evolutionary mechanisms underlying niche differentiation of flavobacteria lineages.

Drought-tolerant plant growth-promoting rhizobacteria isolated from jujube (Ziziphus jujuba) and their potential to enhance drought tolerance - Min Zhang; Lin Yang; Ruqian Hao; Xiaoxiong Bai; Ying Wang; Xuan Yu (Plant and Soil, 2020)

Targeting Inflammation, PHA-767491 Shows a Broad Spectrum in Protein Aggregation Diseases - Yu-Han Chung; Chia-Wei Lin; Hsin-Yu Huang; Shu-Ling Chen; Hei-Jen Huang; Ying-Chieh Sun; Guan-Chiun Lee; Guey-Jen Lee-Chen; Ya-Ching Chang; Hsiu Mei Hsieh-Li (Journal of Molecular Neuroscience, 2020)

Hispidulin Inhibits Neuroinflammation in Lipopolysaccharide-Activated BV2 Microglia and Attenuates the Activation of Akt, NF-κB, and STAT3 Pathway - Chung-I Yu; Cheng-I Cheng; Ya-Fei Kang; Po-Chih Chang; In-Pin Lin; Yu-His Kuo; An-Jie Jhou; Mei-Ying Lin; Chung-Yi Chen; Chien-Hsing Lee (Neurotoxicity Research, 2020)

Influence of Aphis gossypii feeding on defense strategy of native and introduced populations of Ageratina adenophora - Ying Lin; Shu-Qi He; Zhi-Hui Lu; Yu-Lin Gao; Yan-Ru Duan; Zheng-Yue Li; Bin Chen; Fu-Rong Gui (Arthropod-Plant Interactions, 2020)

Combined effect of polymorphisms of MTHFR and MTR and arsenic methylation capacity on developmental delay in preschool children in Taiwan - Yu-Mei Hsueh; Ying-Chin Lin; Chi-Jung Chung; Ya-Li Huang; Ru-Lan Hsieh; Pai-Tsang Huang; Mei-Yi Wu; Horng-Sheng Shiue; Ssu-Ning Chien; Chih-Ying Lee; Ming-I. Lin; Shu-Chi Mu; et al. (Archives of Toxicology, 2020)

Comparison of epidemiological and clinical characteristics of COVID-19 patients with and without Wuhan exposure - Jiang-shan Lian; Huan Cai; Shao-rui Hao; Xi Jin; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Shan-yan Zhang; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Comparative transcriptomic analysis of vascular endothelial cells after hypoxia/re-oxygenation induction based on microarray technology - Jia Xu; Jiu-kun Jiang; Xiao-lin Li; Xiao-peng Yu; Ying-ge Xu; Yuan-qiang Lu (Journal of Zhejiang University-SCIENCE B, 2020)

Endometrial autophagy is essential for embryo implantation during early pregnancy - Yan Su; Juan-Juan Zhang; Jun-Lin He; Xue-Qing Liu; Xue-Mei Chen; Yu-Bin Ding; Chao Tong; Chuan Peng; Yan-Qing Geng; Ying-Xiong Wang; Ru-Fei Gao (Journal of Molecular Medicine, 2020)

Assessing dietary exposure risk to neonicotinoid residues among preschool children in regions of Taiwan - Min-Pei Ling; Huai-An Hsiao; Szu-Chieh Chen; Wei-Yu Chen; Wei-Chun Chou; Yi-Jun Lin; Shu-Han You; Ying-Fei Yang; Hsing-Chieh Lin; Chi-Yun Chen; Tien-Hsuan Lu; Chung-Min Liao (Environmental Science and Pollution Research, 2020)

An alternative splicing variant of mineralocorticoid receptor discovered in preeclampsia tissues and its effect on endothelial dysfunction - Mengxi Guo; Chengliang Zhou; Gufeng Xu; Lin Tang; Yechun Ruan; Ying Yu; Xianhua Lin; Dandan Wu; Hao Chen; Priscilla Yu; Luyang Jin; Yinyu Wang; et al. (Science China Life Sciences, 2020)

Bioaugmentation-assisted phytoremediation of manganese and cadmium co-contaminated soil by Polygonaceae plants (Polygonum hydropiper L. and Polygonum lapathifolium L.) and Enterobacter sp. FM-1 - Yi Li; Jiamin Lin; Yuanyuan Huang; Yawei Yao; Xueru Wang; Chengzhao Liu; Ying Liang; Kehui Liu; Fangming Yu (Plant and Soil, 2020)

Development of Climate and Earth System Models in China: Past Achievements and New CMIP6 Results - Tianjun Zhou; Ziming Chen; Liwei Zou; Xiaolong Chen; Yongqiang Yu; Bin Wang; Qing Bao; Ying Bao; Jian Cao; Bian He; Shuai Hu; Lijuan Li; et al. (Journal of Meteorological Research, 2020)

Prenatal exposure to organophosphate pesticides, maternal paraoxonase 1 genotype, and childhood neurodevelopment at 24 months of age in Shandong, China - Yiwen Wang; Yan Zhang; Lin Ji; Yijun Zhou; Rong Shi; Michihiro Kamijima; Jun Ueyama; Yu Gao; Ying Tian (Environmental Science and Pollution Research, 2020)

Stabilization of hydrophobic organic contaminants in sediments by natural zeolites: bioavailability-based assessment of efficacy using equilibrium passive sampling - Yiqin Chen; Wenjian Yu; Ling Jin; Qian Wang; Jie Yin; Jianwei Lin; Juan-Ying Li (Journal of Soils and Sediments, 2019)

Application of Cas12a and nCas9-activation-induced cytidine deaminase for genome editing and as a non-sexual strategy to generate homozygous/multiplex edited plants in the allotetraploid genome of tobacco - Chen-Tran Hsu; Yu-Jung Cheng; Yu-Hsua Yuan; Wei-Fon Hung; Qiao-Wei Cheng; Fu-Hui Wu; Lan-Ying Lee; Stanton B. Gelvin; Choun-Sea Lin (Plant Molecular Biology, 2019)

Disfiguring Mucor irregularis Infection Cured by Amphotericin B and Itraconazole: A Case Report and Treatment Experience - Lin-wei Wei; Hong Wang; Ying-gai Song; Jin Yu (Mycopathologia, 2019)

Association of plasma folate, vitamin B12 levels, and arsenic methylation capacity with developmental delay in preschool children in Taiwan - Ying-Chin Lin; Chi-Jung Chung; Ya-Li Huang; Ru-Lan Hsieh; Pai-Tsang Huang; Mei-Yi Wu; Pui-Lam Ao; Horng-Sheng Shiue; Shiau-Rung Huang; Chien-Tien Su; Ming-I Lin; Shu-Chi Mu; et al. (Archives of Toxicology, 2019)

Algicoccus marinus gen. nov. sp. nov., a marine bacterium isolated from the surface of brown seaweed Laminaria japonica - Jun-Jie Ying; Shun-Li Zhang; Chao-Yu Huang; Lin Xu; Zhe Zhao; Min Wu; Cong Sun (Archives of Microbiology, 2019)

Long non-coding RNA and mRNA analysis of Ang II-induced neuronal dysfunction - Lin-Lin Shao; Yue-Hua Jiang; Ling-Yu Jiang; Chuan-Hua Yang; Ying-Zi Qi (Molecular Biology Reports, 2019)

Intragenic Transcriptional cis-Antagonism Across SLC6A3 - Ying Zhao; Jinlong Yu; Juan Zhao; Xiaowu Chen; Nian Xiong; Tao Wang; Hong Qing; Zhicheng Lin (Molecular Neurobiology, 2019)

PARK14 (D331Y) PLA2G6 Causes Early-Onset Degeneration of Substantia Nigra Dopaminergic Neurons by Inducing Mitochondrial Dysfunction, ER Stress, Mitophagy Impairment and Transcriptional Dysregulation in a Knockin Mouse Model - Ching-Chi Chiu; Chin-Song Lu; Yi-Hsin Weng; Ying-Ling Chen; Ying-Zu Huang; Rou-Shayn Chen; Yi-Chuan Cheng; Yin-Cheng Huang; Yu-Chuan Liu; Szu-Chia Lai; Kun-Jun Lin; Yan-Wei Lin; et al. (Molecular Neurobiology, 2019)

Permanent displacement models of earthquake-induced landslides considering near-fault pulse-like ground motions - Ying-bin Zhang; Chen-lin Xiang; Yan-long Chen; Qian-gong Cheng; Li Xiao; Peng-cheng Yu; Zhi-wang Chang (Journal of Mountain Science, 2019)

Lasiodiplodia spp. associated with Aquilaria crassna in Laos - Yu Wang; Sen Lin; Lin Zhao; Xiang Sun; Wei He; Ying Zhang; Yu-Cheng Dai (Mycological Progress, 2019)

Evaluation of particulate matter deposition in the human respiratory tract during winter in Nanjing using size and chemically resolved ambient measurements - Xiaoyuan Liu; Dongyang Nie; Kai Zhang; Ziyao Wang; Xiaoqian Li; Zhihao Shi; Yiyi Wang; Lin Huang; Mindong Chen; Xinlei Ge; Qi Ying; Xingna Yu; et al. (Air Quality, Atmosphere & Health, 2019)

Magnesium sulfate inhibits binding of lipopolysaccharide to THP-1 cells by reducing expression of cluster of differentiation 14 - Ya-Ying Chang; Tzu-Yu Lin; Ming-Chang Kao; Tsung-Ying Chen; Ching-Feng Cheng; Chih-Shung Wong; Chun-Jen Huang (Inflammopharmacology, 2019)

Herpes zoster and the risks of osteoporosis and fracture: a nationwide cohort study - Shu-Man Lin; Chih-Yung Wang; Ying-Yu Chen; Jen-Hung Wang; Chung-Chao Liang; Huei-Kai Huang (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Contrastive removal of oxytetracycline and chlortetracycline from aqueous solution on Al-MOF/GO granules - Lin-ling Yu; Zi-fen Luo; Ying-ying Zhang; Shi-chuan Wu; Cao Yang; Jian-hua Cheng (Environmental Science and Pollution Research, 2019)

The analgesic effect and possible mechanisms by which koumine alters type II collagen-induced arthritis in rats - Gui-Lin Jin; Jian Yang; Wan-Qing Chen; Jie Wang; Hong-Qiang Qiu; Ying Xu; Chang-Xi Yu (Journal of Natural Medicines, 2019)

EGb761 improves the cognitive function of elderly db/db−/− diabetic mice by regulating the beclin-1 and NF-κB signaling pathways - Zhu-Fei Guan; Xiao-Ming Zhang; Ying-Hong Tao; Yu Zhang; Yan-Yan Huang; Gang Chen; Wei-Jun Tang; Gang Ji; Qi-Lin Guo; Ming Liu; Qian Zhang; Na-Na Wang; et al. (Metabolic Brain Disease, 2018)

Risk factors and drug resistance in early-onset neonatal group B streptococcal disease - Ying-wei Wang; Yao-qiang Du; Xiao-lin Miao; Guang-yong Ye; Yi-yun Wang; Ai-bo Xu; Yun-zhong Jing; Yu Tong; Kai Xu; Mei-qin Zheng; Dong Chen; Zhen Wang (Journal of Zhejiang University-SCIENCE B, 2018)

The influences of industrial gross domestic product, urbanization rate, environmental investment, and coal consumption on industrial air pollutant emission in China - Wei-yu Zhou; Wen-lin Yang; Wen-xin Wan; Jing Zhang; Wei Zhou; Hao-shen Yang; Hua Yang; Hong Xiao; Shi-huai Deng; Fei Shen; Ying-jun Wang (Environmental and Ecological Statistics, 2018)

Proteomic discovery of H2O2 response in roots and functional characterization of PutGLP gene from alkaligrass - Juanjuan Yu; Yongxue Zhang; Junming Liu; Lin Wang; Panpan Liu; Zepeng Yin; Siyi Guo; Jun Ma; Zhuang Lu; Tai Wang; Yimin She; Yuchen Miao; et al. (Planta, 2018)

NTF3 Is a Novel Target Gene of the Transcription Factor POU3F2 and Is Required for Neuronal Differentiation - Yi-Mei J. Lin; I-Lun Hsin; H. Sunny Sun; Shankung Lin; Yen-Ling Lai; Hsuan-Ying Chen; Ting-Yu Chen; Ya-Ping Chen; Yi-Ting Shen; Hung-Ming Wu (Molecular Neurobiology, 2018)

Response to “Letter to the editor re: Cheng YH, Chou WC, Yang YF, et al. Environ Sci Pollut Res (2018). https://doi.org/10.107/s11356-017-0875-4” - Yi-Hsien Cheng; Wei-Chun Chou; Ying-Fei Yang; Chi-Wei Huang; Chun Ming How; Szu-Chieh Chen; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Jun Lin; Shu-Han You; Chung-Min Liao (Environmental Science and Pollution Research, 2018)

Pseudomonas pharmafabricae sp. nov., Isolated From Pharmaceutical Wastewater - Xiao-Yun Yu; Jing-Yu Zhai; Chen Wu; Chong-Ya Zhang; Jie-Ying Shi; Lin-Xian Ding; Min Wu (Current Microbiology, 2018)

pTAC10, an S1-domain-containing component of the transcriptionally active chromosome complex, is essential for plastid gene expression in Arabidopsis thaliana and is phosphorylated by chloroplast-targeted casein kinase II - Qing-Bo Yu; Tuan-Tuan Zhao; Lin-Shan Ye; Ling Cheng; Ying-Qian Wu; Chao Huang; Zhong-Nan Yang (Photosynthesis Research, 2018)

Proteomic analysis of human umbilical vein endothelial cells exposed to PM2.5 - Ji Zhu; Lin-wen-si Zhu; Jin-huan Yang; Ying-ling Xu; Cui Wang; Zhuo-yu Li; Wei Mao; De-zhao Lu (Journal of Zhejiang University-SCIENCE B, 2018)

Impact of International Collaborative Training Programs on Medical Students’ Research Ability - Remila Rezhake; Shang-Ying Hu; Yu-Qian Zhao; Li Zhang; Xue-Lian Zhao; Ayling Z. Dominguez; You-Lin Qiao; Cai-Hong Zhou; Fang-Hui Zhao (Journal of Cancer Education, 2018)

A Quninolylthiazole Derivatives as an ICT-Based Fluorescent Probe of Hg(II) and its Application in Ratiometric Imaging in Live HeLa Cells - Jian-Ying Bai; Yu-Zhong Xie; Chang-Jiang Wang; Shu-Qing Fang; Lin-Nan Cao; Ling-Li Wang; Jing-Yi Jin (Journal of Fluorescence, 2018)

Characterization of the complete chloroplast genome of the Chinese cherry Prunus pseudocerasus (Rosaceae) - Ying Feng; Tao Liu; Xiao-Yu Wang; Bin-Bin Li; Cheng-Lin Liang; Yu-Liang Cai (Conservation Genetics Resources, 2018)

Correction to: Age at menarche and age at natural menopause in East Asian women: a genome-wide association study - Jiajun Shi; Ben Zhang; Ji-Yeob Choi; Yu-Tang Gao; Huaixing Li; Wei Lu; Jirong Long; Daehee Kang; Yong-Bing Xiang; Wanqing Wen; Sue K. Park; Xingwang Ye; et al. (GeroScience, 2018)

PBPK/PD assessment for Parkinson’s disease risk posed by airborne pesticide paraquat exposure - Yi-Hsien Cheng; Wei-Chun Chou; Ying-Fei Yang; Chi-Wei Huang; Chun Ming How; Szu-Chieh Chen; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Jun Lin; Shu-Han You; Chung-Min Liao (Environmental Science and Pollution Research, 2018)

A new cycloartane triterpenoid glycoside from Souliea vaginata - Hai-Feng Wu; Xin Liu; Yin-Di Zhu; Jing Zhou; Ying-Ying Gong; Guo-Xu Ma; Xu-Dong Xu; Yi-Lin Liu; Zheng-Hong Luo; Di-Zhao Chen; Qiong-Yu Zou; Zi-Jian Zhao (Natural Product Research, 2017)

The Effect of Sodium Fluoride on Cell Apoptosis and the Mechanism of Human Lung BEAS-2B Cells In Vitro - Jun Ying; Jie Xu; Liping Shen; Zhijie Mao; Jingchen Liang; Shuangxiang Lin; Xinyan Yu; Ruowang Pan; Chunxia Yan; Shengbin Li; Qiyu Bao; Peizhen Li (Biological Trace Element Research, 2017)

The analgesic effect of trans-resveratrol is regulated by calcium channels in the hippocampus of mice - Weijie Wang; Yingcong Yu; Jing Li; Lin Wang; Zhi Li; Chong Zhang; Linlin Zhen; Lianshu Ding; Gang Wang; Xiaoyang Sun; Ying Xu (Metabolic Brain Disease, 2017)

Delayed Treatment with Green Tea Polyphenol EGCG Promotes Neurogenesis After Ischemic Stroke in Adult Mice - Jian-Cheng Zhang; Hang Xu; Yin Yuan; Jia-Yi Chen; Yu-Jing Zhang; Yun Lin; Shi-Ying Yuan (Molecular Neurobiology, 2017)

Tunable and Nontoxic Fluorescent Probes Based on Carbon Dots for Imaging of Indole Propionic Acid Receptor in Plant Tissues in Situ - Bixia Lin; Ying Yu; Fangfei Liu; Yujuan Cao; Manli Guo (Journal of Fluorescence, 2017)

Groundwater origins and recharge in a well field near Chien-Shih, Shinchu, Taiwan - Pei-Ying Lin; Louis Loung-Yie Tsai; Chung-Ho Wang; Kuei-Wen Chang; Yu-Yen Sheng; I-Tzu Chu; Wang-Ru Lee (Sustainable Water Resources Management, 2017)

IL-28 and IL-29 as protective markers in subject with dengue fever - Chih-Hsing Hung; Chung-Hao Huang; Lin Wang; Chun-Chi Huang; Meng-Chieh Wu; Yi-Ying Chin; Chun-Yu Lin; Ko Chang; Deng-Chyang Wu; Yen-Hsu Chen (Medical Microbiology and Immunology, 2017)

The effects and the toxicity increases caused by bicarbonate, chloride, and other water components during the UV/TiO2 degradation of oxazaphosphorine drugs - Webber Wei-Po Lai; Ying-Chih Chuang; Angela Yu-Chen Lin (Environmental Science and Pollution Research, 2017)

Identification and expression patterns of 20-hydroxyecdysone-responsive genes from Procambarus clarkii - Bao-Jian Zhu; Lin Tang; Ying-Ying Yu; Dao-Jun Wang; Chao-Liang Liu (Genes & Genomics, 2017)

Genetic Variants of Microtubule Actin Cross-linking Factor 1 (MACF1) Confer Risk for Parkinson’s Disease - Xin Wang; Nuomin Li; Nian Xiong; Qi You; Jie Li; Jinlong Yu; Hong Qing; Tao Wang; Heather J. Cordell; Ole Isacson; Jeffery M. Vance; Eden R. Martin; et al. (Molecular Neurobiology, 2017)

Identification of the Genetic Cause for Childhood Disintegrative Disorder by Whole-Exome Sequencing - Zhu Wen; Tian-Lin Cheng; Da-Zhi Yin; Shi-Bang Sun; Zheng Wang; Shun-Ying Yu; Yi Zhang; Zilong Qiu; Ya-Song Du (Neuroscience Bulletin, 2017)

Integrative multi-omics analysis revealed SNP-lncRNA-mRNA (SLM) networks in human peripheral blood mononuclear cells - Wei Xia; Xiao-Wei Zhu; Xin-Bo Mo; Long-Fei Wu; Jian Wu; Yu-Fan Guo; Ke-Qin Zeng; Ming-Jun Wang; Xiang Lin; Ying-Hua Qiu; Lan Wang; Pei He; et al. (Human Genetics, 2017)

Impacts of CD33 Genetic Variations on the Atrophy Rates of Hippocampus and Parahippocampal Gyrus in Normal Aging and Mild Cognitive Impairment - Wen-Ying Wang; Ying Liu; Hui-Fu Wang; Lin Tan; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

A Missense Variant in TREML2 Reduces Risk of Alzheimer’s Disease in a Han Chinese Population - Teng Jiang; Yu Wan; Jun-Shan Zhou; Meng-Shan Tan; Qing Huang; Xi-Chen Zhu; Huan Lu; Hui-Fu Wang; Qi Chen; Lin Tan; Ying-Dong Zhang; Lan Tan; et al. (Molecular Neurobiology, 2017)

Use of electroacupuncture and transcutaneous electrical acupoint stimulation in reproductive medicine: a group consensus - Fan Qu; Rong Li; Wei Sun; Ge Lin; Rong Zhang; Jing Yang; Li Tian; Guo-gang Xing; Hui Jiang; Fei Gong; Xiao-yan Liang; Yan Meng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Characterization of BcMF23a and BcMF23b, two putative pectin methylesterase genes related to pollen development in Brassica campestris ssp. chinensis - Sue Lin; Li Huang; Xiaolin Yu; Xingpeng Xiong; Xiaoyan Yue; Tingting Liu; Ying Liang; Meiling Lv; Jiashu Cao (Molecular Biology Reports, 2017)

Coagulation increased the growth potential of various species bacteria of the effluent of a MBR for the treatment of domestic wastewater - Tong Yu; Guoqiang Li; Wenqi Lin; Hong-Ying Hu; Yun Lu (Environmental Science and Pollution Research, 2017)

In vitro and in vivo studies of nematophagous fungi Arthrobotrys musiformis and Arthrobotrys robusta against the larvae of the trichostrongylides - Kui Zheng Cai; Bo Bo Wang; Qiang Xu; Jun Lin Liu; Kang Ying Wang; Yu Jia Xue; Hai Yan Zhang; Hai Yu Wang; Xin Cao; Zhong Ren Ma (Acta Parasitologica, 2017)
Six isolates of

Erratum to: Fine mapping and candidate gene analysis of qHD5, a novel major QTL with pleiotropism for yield-related traits in rice (Oryza sativa L.) - Bin Sun; Xiao-Deng Zhan; Ze-Chuan Lin; Wei-Xun Wu; Ping Yu; Ying-Xin Zhang; Lian-Ping Sun; Li-Yong Cao; Shi-Hua Cheng (Theoretical and Applied Genetics, 2017)

Fine mapping and candidate gene analysis of qHD5, a novel major QTL with pleiotropism for yield-related traits in rice (Oryza sativa L.) - Bin Sun; Xiao-Deng Zhan; Ze-Chuan Lin; Wei-Xun Wu; Ping Yu; Ying-Xin Zhang; Lian-Ping Sun; Li-Yong Cao; Shi-Hua Cheng (Theoretical and Applied Genetics, 2017)

Analysis of QTL for seed oil content in Brassica napus by association mapping and QTL mapping - Ying Fu; Dongqing Zhang; Madeleine Gleeson; Yaofeng Zhang; Baogang Lin; Shuijin Hua; Houdong Ding; Martin Frauen; Jiana Li; Wei Qian; Huasheng Yu (Euphytica, 2017)

Characteristics of the sea ice reflectance spectrum polluted by oil spills based on field experiments in the Bohai Sea - Jinlong Chao; Chengyu Liu; Ying Li; Xia Lin; Yu Yan (Acta Oceanologica Sinica, 2017)

miR-137 and miR-491 Negatively Regulate Dopamine Transporter Expression and Function in Neural Cells - Xiaojian Jia; Feng Wang; Ying Han; Xuewen Geng; Minghua Li; Yu Shi; Lin Lu; Yun Chen (Neuroscience Bulletin, 2016)

RhoB/ROCK mediates oxygen–glucose deprivation-stimulated syncytiotrophoblast microparticle shedding in preeclampsia - Jian Han; Bo-ping Yang; Yi-lin Li; Hong-mei Li; Xiu-hui Zheng; Li-li Yu; Qiong Zhang; Ying-ru Zheng; Ping Yi; Li Li; Jian-xin Guo; Yuan-guo Zhou (Cell and Tissue Research, 2016)

Piperine potentiates the effects of trans-resveratrol on stress-induced depressive-like behavior: involvement of monoaminergic system and cAMP-dependent pathway - Ying Xu; Chong Zhang; Feiyan Wu; Xiaoxiao Xu; Gang Wang; Mengmeng Lin; Yingcong Yu; Yiran An; Jianchun Pan (Metabolic Brain Disease, 2016)

Assessing exposure risks for freshwater tilapia species posed by mercury and methylmercury - Yi-Hsien Cheng; Yi-Jun Lin; Shu-Han You; Ying-Fei Yang; Chun Ming How; Yi-Ting Tseng; Wei-Yu Chen; Chung-Min Liao (Ecotoxicology, 2016)

Polymorphisms of human 8-oxoguanine DNA glycosylase 1 and 8-hydroxydeoxyguanosine increase susceptibility to arsenic methylation capacity-related urothelial carcinoma - Chao-Yuan Huang; Yeong-Shiau Pu; Horng-Sheng Shiue; Wei-Jen Chen; Ying-Chin Lin; Yu-Mei Hsueh (Archives of Toxicology, 2016)

Anisotropic Drained Deformation Behavior and Shear Strength of Natural Soft Marine Clay - Yu-Ke Wang; Lin Guo; Yu-Feng Gao; Yue Qiu; Xiu-Qing Hu; Ying Zhang (Marine Georesources & Geotechnology, 2016)

Influence of Soluplus on Solid-State Properties and Physical Stability of Indomethacin-Saccharin Co-crystal Formation Prepared by Air-Drying Process - Shan-Yang Lin; Hong-Liang Lin; Ying-Ting Chi; Ru-Ying Hung; Yu-Ting Huang; Wei-Hsien Hsieh; Chi-Yu Kao (Journal of Pharmaceutical Innovation, 2016)

Molecular phylogenetic analysis of key Jatropha species inferred from nrDNA ITS and chloroplast (trnL-F and rbcL) sequences - Guo-ye Guo; Sheng-hua Wang; Ying Xu; Lin Tang; Mao-qun Yu; Fang Chen (Genes & Genomics, 2016)

A new phenylethanoid glycoside from Orobanche cernua Loefling - Zheng-yi Qu; Yu-wei Zhang; Si-wen Zheng; Chun-lin Yao; Yin-ping Jin; Pei-he Zheng; Cheng-he Sun; Ying-ping Wang (Natural Product Research, 2016)

Differential expression of ATP-gated P2X receptors in DRG between chronic neuropathic pain and visceralgia rat models - Lin Chen; Yu-wei Liu; Kai Yue; Qin Ru; Qi Xiong; Bao-miao Ma; Xiang Tian; Chao-ying Li (Purinergic Signalling, 2016)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

Species-specific differences in the role of L-type Ca2+ channels in the regulation of coronary arterial smooth muscle contraction - Hui Yang; Su-Juan Kuang; Fang Rao; Yu-Mei Xue; Xiao-Ying Liu; Zhi-Xin Shan; Xiao-Hong Li; Jie-Ning Zhu; Zhi-Ling Zhou; Xiao-juan Zhang; Qiu-Xiong Lin; Xi-Yong Yu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Onychomycosis Associated with Exophiala oligosperma in Taiwan - Yu-Min Wen; Ranjith Kumar Rajendran; Ying-Fang Lin; Roland Kirschner; Sindy Hu (Mycopathologia, 2016)

Erratum to: Identification of the Avulsion-Injured Spinal Motoneurons - Min Tan; Ming-zhou Yuan; Tian-yu Sun; Ying-yu Xie; Lin-Lin Liu; Ying Tang; Ze-min Ling; Ying-qin Li; Guang-yin Yu; Li Hua Zhou (Journal of Molecular Neuroscience, 2016)

CTRP3 attenuates post-infarct cardiac fibrosis by targeting Smad3 activation and inhibiting myofibroblast differentiation - Dan Wu; Hong Lei; Jin-Yu Wang; Cheng-Lin Zhang; Han Feng; Feng-Ying Fu; Li Li; Li-Ling Wu (Journal of Molecular Medicine, 2015)

Effects of simulated acid rain on microbial characteristics in a lateritic red soil - Hua-qin Xu; Jia-en Zhang; Ying Ouyang; Ling Lin; Guo-ming Quan; Ben-liang Zhao; Jia-yu Yu (Environmental Science and Pollution Research, 2015)

Retraction Note to: Lactoferrin promote primary rat osteoblast proliferation and differentiation via up-regulation of insulin-like growth factor-1 expression - Jian-ming Hou; Man Wu; Qing-ming Lin; Fan Lin; Ying Xue; Xu-hua Lan; En-yu Chen; Mei-li Wang; Hai-yan Yang; Feng-xiong Wang (Molecular Biology Reports, 2015)

The diversity of coral associated bacteria and the environmental factors affect their community variation - Yan-Ying Zhang; Juan Ling; Qing-Song Yang; You-Shao Wang; Cui-Ci Sun; Hong-Yan Sun; Jing-Bin Feng; Yu-Feng Jiang; Yuan-Zhou Zhang; Mei-Lin Wu; Jun-De Dong (Ecotoxicology, 2015)

Identification of the Avulsion-Injured Spinal Motoneurons - Min Tan; Ming-zhou Yuan; Tian-yu Sun; Ying-yu Xie; Lin-Lin Liu; Ying Tang; Ze-min Ling; Ying-qin Li; Guang-yin Yu; Li Hua Zhou (Journal of Molecular Neuroscience, 2015)

Pretreatment with Evans blue, a stimulator of BKCa channels, inhibits compound 48/80-induced shock, systemic inflammation, and mast cell degranulation in the rat - Yaw-Syan Fu; Su-Yu Kuo; Hsuan-Yea Lin; Chun-Lin Chen; Shi-Ying Huang; Zhi-Hong Wen; Kun-Zer Lee; Hung-Tu Huang (Histochemistry and Cell Biology, 2015)

The differential roles of Slit2-exon 15 splicing variants in angiogenesis and HUVEC permeability - Yun-Chiu Yang; Pei-Ni Chen; Siou-Yu Wang; Chen-Yi Liao; Yu-Ying Lin; Shih-Rhong Sun; Chun-Ling Chiu; Yih-Shou Hsieh; Jia-Ching Shieh; Jinghua Tsai Chang (Angiogenesis, 2015)

Genetic relationships and ecological divergence in Salix species and populations in Taiwan - Chun-Lin Huang; Chung-Te Chang; Bing-Hong Huang; Jeng-Der Chung; Jui-Hung Chen; Yu-Chung Chiang; Shih-Ying Hwang (Tree Genetics & Genomes, 2015)

JcCBF2 gene from Jatropha curcas improves freezing tolerance of Arabidopsis thaliana during the early stage of stress - Linghui Wang; Jihai Gao; Xiaobo Qin; Xiaodong Shi; Lin Luo; Guozhen Zhang; Hongwu Yu; Chenyang Li; Minchao Hu; Qifan Liu; Ying Xu; Fang Chen (Molecular Biology Reports, 2015)

Association between the CYP1A2 polymorphisms and risk of cancer: a meta-analysis - Wen-Xia Sun; Ying-Hua Chen; Zhi-Zhong Liu; Jian-Jun Xie; Wei Wang; Ya-Ping Du; Yu Chen; Xu-Liang Shen; Xiao-Feng He; Li-Xia Wu; Wu Wei; Lin Zhang (Molecular Genetics and Genomics, 2015)

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

Increase of Zinc Finger Protein 179 in Response to CCAAT/Enhancer Binding Protein Delta Conferring an Antiapoptotic Effect in Astrocytes of Alzheimer’s Disease - Shao-Ming Wang; Yi-Chao Lee; Chiung-Yuan Ko; Ming-Derg Lai; Ding-Yen Lin; Ping-Chieh Pao; Jhih-Ying Chi; Yu-Wei Hsiao; Tsung-Lin Liu; Ju-Ming Wang (Molecular Neurobiology, 2015)

Antidepressant-like effects of ferulic acid: involvement of serotonergic and norepinergic systems - Jianliang Chen; Dan Lin; Chong Zhang; Gaowen Li; Nianping Zhang; Lina Ruan; Qizhi Yan; Jianxin Li; Xuefeng Yu; Xupei Xie; Cong Pang; Liang Cao; et al. (Metabolic Brain Disease, 2015)

The Akt inhibitor MK-2206 enhances the cytotoxicity of paclitaxel (Taxol) and cisplatin in ovarian cancer cells - Ying-Hsi Lin; Bert Yu-Hung Chen; Wei-Ting Lai; Shao-Fu Wu; Jih-Hwa Guh; Ann-Lii Cheng; Lih-Ching Hsu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2015)

Effects of rapamycin against paraquat-induced pulmonary fibrosis in mice - Xue Shao; Meng Li; Chong Luo; Ying-ying Wang; Ying-ying Lu; Shi Feng; Heng Li; Xia-bing Lang; Yu-cheng Wang; Chuan Lin; Xiu-jin Shen; Qin Zhou; et al. (Journal of Zhejiang University-SCIENCE B, 2015)

Contamination of commercially available seafood by key diarrhetic shellfish poisons along the coast of China - Chao Lin; Zeng-Shan Liu; Cai-Yun Tan; Yi-Ping Guo; Lin Li; Hong-Lin Ren; Yan-Song Li; Pan Hu; Sheng Gong; Yu Zhou; Shi-Ying Lu (Environmental Science and Pollution Research, 2015)

Association of IL-18 promoter gene polymorphisms with rheumatoid arthritis: a meta-analysis - Li-Ping Cai; Li-Juan Zhou; Shun-Yu Lu; Ying-E Liang; Xiao-Ying Chen; Lin Liu; Jun Lin (Molecular Biology Reports, 2014)

Genetic diversity and identification of race 3 of Fusarium oxysporum f. sp. lactucae in Taiwan - Ying-Hong Lin; Po-Jung Lai; Tao-Ho Chang; Yu-Ling Wan; Jenn-Wen Huang; Jin-Hsing Huang; Pi-Fang Linda Chang (European Journal of Plant Pathology, 2014)

Global and local brain network reorganization in attention-deficit/hyperactivity disorder - Pan Lin; Jubao Sun; Gang Yu; Ying Wu; Yong Yang; Meilin Liang; Xin Liu (Brain Imaging and Behavior, 2014)

Impacts of uncertainty in AVOC emissions on the summer ROx budget and ozone production rate in the three most rapidly-developing economic growth regions of China - Feng Wang; Junling An; Ying Li; Yujia Tang; Jian Lin; Yu Qu; Yong Chen; Bing Zhang; Jing Zhai (Advances in Atmospheric Sciences, 2014)

Identifying candidate genes for discrimination of ulcerative colitis and Crohn’s disease - Lian-Jie Lin; Ying Zhang; Yan Lin; Yu Jin; Chang-Qing Zheng (Molecular Biology Reports, 2014)

GSK3β Promotes the Differentiation of Oligodendrocyte Precursor Cells via β-Catenin-Mediated Transcriptional Regulation - Liang Zhou; Chong-Yu Shao; Si-min Xu; Jiao Ma; Ya-Jun Xie; Lin Zhou; Peng Teng; Yin Wang; Mengsheng Qiu; Ying Shen (Molecular Neurobiology, 2014)

Two Frequent Mutations Associated with the Classic Form of Propionic Acidemia in Taiwan - Yen-Hui Chiu; Yu-Ning Liu; Wei-Ling Liao; Ying-Chen Chang; Shuan-Pei Lin; Chia-Chi Hsu; Pao-Chin Chiu; Dau-Ming Niu; Chung-Hsing Wang; Yu-Yuan Ke; Yin-Hsiu Chien; Kwang-Jen Hsiao; et al. (Biochemical Genetics, 2014)

The Melanogenesis-Inhibitory Effect and the Percutaneous Formulation of Ginsenoside Rb1 - Lin Wang; Ai-Ping Lu; Zhi-Ling Yu; Ricky N. S. Wong; Zhao-Xiang Bian; Hoi-Hin Kwok; Patrick Ying-Kit Yue; Li-Min Zhou; HuBiao Chen; Min Xu; Zhijun Yang (AAPS PharmSciTech, 2014)

Effects of Bone Marrow Mesenchymal Stem Cells on Hematopoietic Recovery and Acute Graft-Versus-Host Disease in Murine Allogeneic Umbilical Cord Blood Transplantation Model - Zhen Yu Li; Chun Qing Wang; Guang Lu; Xiu Ying Pan; Kai Lin Xu (Cell Biochemistry and Biophysics, 2014)

RETRACTED ARTICLE: Lactoferrin promote primary rat osteoblast proliferation and differentiation via up-regulation of insulin-like growth factor-1 expression - Jian-ming Hou; Man Wu; Qing-ming Lin; Fan Lin; Ying Xue; Xu-hua Lan; En-yu Chen; Mei-li Wang; Hai-yan Yang; Feng-xiong Wang (Molecular Biology Reports, 2014)

Degradation of polyurethane by bacterium isolated from soil and assessment of polyurethanolytic activity of a Pseudomonas putida strain - Yu-Huei Peng; Yang-hsin Shih; Yen-Chun Lai; Yuan-Zan Liu; Ying-Tong Liu; Nai-Chun Lin (Environmental Science and Pollution Research, 2014)

Concentrations of particulates in ambient air, gaseous elementary mercury (GEM), and particulate-bound mercury (Hg(p)) at a traffic sampling site: a study of dry deposition in daytime and nighttime - Guor-Cheng Fang; Yen-Heng Lin; Chia-Ying Chang; Yu-Cheng Zheng (Environmental Geochemistry and Health, 2014)

Quantitative trait loci analysis of individual and total isoflavone contents in soybean seeds - HAI JUN ZHANG; JING WEN LI; YA JING LIU; WEN ZHU JIANG; XING LIN DU; LIN LI; XIAO WEI Li; LIAN TAI SU; QING YU WANG; YING WANG (Journal of Genetics, 2014)

Complete genome sequence analysis identifies a new genotype of brassica yellows virus that infects cabbage and radish in China - Xiao-Yan Zhang; Hai-Ying Xiang; Cui-Ji Zhou; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2014)

A novel method for the rapid detection of benzo(a)pyrene in liquid milk by dimethyl sulfoxide selectively enhanced synchronous fluorescence spectrometry - Li-Rong Lin; He-Dong Luo; Xiu-Ying Li; Na Li; Na Zhou; Yu-Zhu Jia; Yi-Hong Liu; Yao-Qun Li (Food Additives & Contaminants: Part A, 2014)

Identification of the substrate recognition region in the Δ6-fatty acid and Δ8-sphingolipid desaturase by fusion mutagenesis - Li-Ying Song; Yan Zhang; Shu-Fen Li; Jun Hu; Wei-Bo Yin; Yu-Hong Chen; Shan-Ting Hao; Bai-Lin Wang; Richard R.-C. Wang; Zan-Min Hu (Planta, 2014)

Sustained endoplasmic reticulum stress inhibits hepatocyte proliferation via downregulation of c-Met expression - Yihuai He; Jun Long; Weiwei Zhong; Yu Fu; Ying Li; Shide Lin (Molecular and Cellular Biochemistry, 2014)

Analyzing and modeling rheological behavior of liver fibrosis in rats using shear viscoelastic moduli - Ying Zhu; Yi Zheng; Yuan-yuan Shen; Xin Chen; Xin-yu Zhang; Hao-ming Lin; Yan-rong Guo; Tian-fu Wang; Si-ping Chen (Journal of Zhejiang University-SCIENCE B, 2014)

cDNA cloning and molecular characterization of five cellulose synthase A genes from Eucalyptus camaldulensis - Yen Lin; Yu-Ying Kao; Zenn-Zong Chen; Fang-Hua Chu; Jeng-Der Chung (Journal of Plant Biochemistry and Biotechnology, 2014)

Genetic variations in TP53 binding sites are predictors of clinical outcomes in prostate cancer patients - Victor C. Lin; Chao-Yuan Huang; Yung-Chin Lee; Chia-Cheng Yu; Ta-Yuan Chang; Te-Ling Lu; Shu-Pin Huang; Bo-Ying Bao (Archives of Toxicology, 2014)

Synthesis and anti-cancer activity of a glycosyl library of $$\varvec{N}$$ N -acetylglucosamine-bearing oleanolic acid - Yi-Bing Zeng; Hsin-Min Hsiao; She-Hung Chan; Ying-Hsin Wang; You-Yu Lin; Yu-Hsuan Kuo; Jih-Hwa Guh; Pi-Hui Liang (Molecular Diversity, 2014)

Piperine potentiates the antidepressant-like effect of trans-resveratrol: involvement of monoaminergic system - Wu Huang; Zhuoyou Chen; Qiandong Wang; Mengmeng Lin; Shujuan Wu; Qizhi Yan; Fan Wu; Xuefeng Yu; Xupei Xie; Gaowen Li; Ying Xu; Jianchun Pan (Metabolic Brain Disease, 2013)

HOXA9 Gene Expression in Acute Myeloid Leukemia - De-Peng Li; Zhen-Yu Li; Wei Sang; Hai Cheng; Xiu-Ying Pan; Kai-Lin Xu (Cell Biochemistry and Biophysics, 2013)

Beta Amyloid Peptide (25-35) Leading to Inflammation Through Toll-Like Receptors and the Anti-inflammatory Effect of Genistein in BV-2 Cells - Huan-Ling Yu; Xiao-Ying Li; Xin Zhou; Lin-Hong Yuan; Wei-Wei Ma; Yuan-Di Xi; Xia Zhao; Jian Wu; Rong Xiao (Journal of Molecular Neuroscience, 2013)

Responses to booster hepatitis B vaccination are significantly correlated with genotypes of human leukocyte antigen (HLA)-DPB1 in neonatally vaccinated adolescents - Tzu-Wei Wu; Chen-Chung Chu; Tzu-Ying Ho; Huei-Wen Chang Liao; Sheng-Kai Lin; Marie Lin; Hans Hsienhong Lin; Li-Yu Wang (Human Genetics, 2013)

Effects of extracellular calcium on viability and osteogenic differentiation of bone marrow stromal cells in vitro - Shaowen Cheng; Wei Wang; Zhongqin Lin; Ping Zhou; Xiaolei Zhang; Wei Zhang; Qingyu Chen; Dongquan Kou; Xiaozhou Ying; Yue Shen; Xiaojie Cheng; Ziming Yu; et al. (Human Cell, 2013)

Identification and Characterization of an Extracellular Alkaline Phosphatase in the Marine Diatom Phaeodactylum tricornutum - Hung-Yun Lin; Chi-Yu Shih; Hung-Chun Liu; Jeng Chang; Ying-Lan Chen; Yet-Ran Chen; Han-Tso Lin; Yu-Yung Chang; Chun-Hua Hsu; Han-Jia Lin (Marine Biotechnology, 2013)

QTL mapping and correlation analysis for 1000-grain weight and percentage of grains with chalkiness in rice - JIAN-MIN BIAN; HUAN SHI; CUI-JUAN LI; CHANG-LAN ZHU; QIU-YING YU; XIAO-SONG PENG; JUN-RU FU; XIAO-PENG HE; XIAO-RONG CHEN; LI-FANG HU; LIN-JUAN OUYANG; HAO-HUA HE (Journal of Genetics, 2013)

Molecular detection and genomic characterization of Torque teno sus virus 1 and 2 from domestic pigs in central China - Kun Li; Lin-Qing Wang; Yu-Yang Wu; An-Jun Chao; Quan-Wei Lu; Zhan-Yong Wei; Bao-An Cui; Hong-Ying Chen (Virus Genes, 2013)

Hyperinakin, a new anti-inflammatory phloroglucinol derivative from Hypericum nakamurai - Yuan-Bin Cheng; Ahmed Eid Fazary; Yu-Chi Lin; I-Wen Lo; Seow-Chin Ong; Shun-Ying Chen; Ching-Te Chien; Yen-Jung Lin; Wan-Wan Lin; Ya-Ching Shen (Natural Product Research, 2013)

Relationship Between Myocardial Bridging and Coronary Arteriosclerosis - Jian Ling Sun; Wei Min Huang; Ji Hong Guo; Xiao Ying Li; Xian Lin Ma; Chong Yu Wang (Cell Biochemistry and Biophysics, 2013)

Quantitative evaluation of Candia antarctica lipase B displayed on the cell surface of a Pichia pastoris based on an FS anchor system - Xing-xiang Liang; Bei-bei Wang; Yu-fei Sun; Ying Lin; Shuang-yan Han; Sui-ping Zheng; Tang-bing Cui (Biotechnology Letters, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Estrogen stimulates the proliferation of human endometrial cancer cells by stabilizing nucleophosmin/B23 (NPM/B23) - Angel Chao; Chiao-Yun Lin; Chia-Lung Tsai; Swei Hsueh; Ying-Yu Lin; Cheng-Tao Lin; Hung-Hsueh Chou; Tzu-Hao Wang; Chyong-Huey Lai; Hsin-Shih Wang (Journal of Molecular Medicine, 2013)

A molecular diagnosis method using real-time PCR for quantification and detection of Fusarium oxysporum f. sp. cubense race 4 - Ying-Hong Lin; Ching-Chung Su; Chih-Ping Chao; Chi-Yu Chen; Chung-Jan Chang; Jenn-Wen Huang; Pi-Fang Linda Chang (European Journal of Plant Pathology, 2013)

Novel differential transcript expression identified by LongSAGE in the mouse endometrium during the implantation window - Yu-Bin Ding; Jun-Lin He; Xue-Mei Chen; Xue-Qing Liu; Ying-Xiong Wang (Molecular Biology Reports, 2013)

The Diagnostic Value of Treadmill Exercise Test Parameters for Coronary Artery Disease - Jian Ling Sun; Rong Han; Ji Hong Guo; Xiao Ying Li; Xian Lin Ma; Chong Yu Wang (Cell Biochemistry and Biophysics, 2013)

Effects of Ibutilide on Canine Cardiac Pacing Threshold and on Induction Rates of Atrial Fibrillation - Jian-ling Sun; Rong Han; Ji-hong Guo; Xiao-ying Li; Xian-lin Ma; Chong-yu Wang (Cell Biochemistry and Biophysics, 2012)

Strengthening of paleo‐typhoon and autumn rainfall in Taiwan corresponding to the Southern Oscillation at late Holocene - Huei‐Fen Chen; Shie‐Ying Wen; Shen‐Rong Song; Tien‐Nan Yang; Teh‐Quei Lee; Sue‐Fen Lin; Shih‐Chieh Hsu; Kuo‐Yen Wei; Ping‐Yu Chang; Pai‐Sen Yu (Journal of Quaternary Science, 2012)
The purpose of this study is to improve prehistoric knowledge of paleo‐typhoon and winter monsoon activity in the western North Pacific after 8 cal. ka BP. We examine two sediment cores derived from lakes located to the south and north of the Ilan Plain in northeastern Taiwan. Seasonal and typhoon rainfall data over the past several decades are collected for this study region. We also use mineral indicators, K/Rb ratios and grain size to estimate sediment sources, intensity of chemical weathering and rainfall intensity. The results show that the chemical weathering index (K/Rb ratio) of Meihua Lake indicates the continuing effects of autumn rainfall, while coarse grain sizes of Dahu Lake sediments suggest increased intensity in typhoon rainfall. Grain size results reveal that increasing El Niño–Southern Oscillation intensity in the tropical Pacific has intensified the activity of super typhoons in the western North Pacific. Finally, we find that frequent activity of super paleo‐typhoons occurred in Taiwan during the La Niña‐like state, and the strengthening winter monsoon activity and higher sea surface temperature enhanced plentiful autumn rainfall in El Niño‐like state. After comparing our results with the paleo‐typhoon data in Japan and south China, we suggest that the tracks of super typhoon are mainly affected by variations in the warm pool and subtropical Northwestern Pacific High in the western Pacific. Copyright © 2012 John Wiley & Sons, Ltd.

Chemoselective synthesis, antiproliferative activities, and SAR study of 1H-pyrazol-5-yl-N,N-dimethylformamidines and pyrazolyl-2-azadienes - Kau-Shan Wen; Hui-Yi Lin; Yu-Ying Huang; Kimiyoshi Kaneko; Hiroyuki Takayama; Masayuki Kimura; Shin-Hun Juang; Fung Fuh Wong (Medicinal Chemistry Research, 2012)

Effect of Ibutilide on the Canine Cardiac Conduction System - Jian Ling Sun; Rong Han; Ji Hong Guo; Xiao Ying Li; Xian Lin Ma; Chong Yu Wang (Cell Biochemistry and Biophysics, 2012)

Transcriptional responses to drought stress in root and leaf of chickpea seedling - Xiansheng Wang; Ying Liu; Yuying Jia; Hanyan Gu; Hongyu Ma; Tian Yu; Hua Zhang; Quanjia Chen; Lin Ma; Aixing Gu; Jusong Zhang; Shubing Shi; et al. (Molecular Biology Reports, 2012)

Production of monoclonal antibody and application in indirect competitive ELISA for detecting okadaic acid and dinophytoxin-1 in seafood - Shi-Ying Lu; Yu Zhou; Yan-Song Li; Chao Lin; Xian-Mei Meng; Dong-Ming Yan; Zhao-Hui Li; Shi-Yu Yu; Zeng-Shan Liu; Hong-Lin Ren (Environmental Science and Pollution Research, 2012)

Juglanthraquinone C, a novel natural compound derived from Juglans mandshurica Maxim, induces S phase arrest and apoptosis in HepG2 cells - Yao Yao; Yu-Wei Zhang; Lu-Guo Sun; Biao Liu; Yong-Li Bao; Hua Lin; Yu Zhang; Li-Hua Zheng; Ying Sun; Chun-Lei Yu; Yin Wu; Guan-Nan Wang; et al. (Apoptosis, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Nucleotide sequence of a chickpea chlorotic stunt virus relative that infects pea and faba bean in China - Cui-Ji Zhou; Hai-Ying Xiang; Tao Zhuo; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2012)

Risk stratification of spontaneous bacterial peritonitis in cirrhosis with ascites based on classification and regression tree analysis - Ke-Qing Shi; Yu-Chen Fan; Li Ying; Xian-Feng Lin; Mei Song; Ling-Fei Li; Xie-Yan Yu; Yong-Ping Chen; Ming-Hua Zheng (Molecular Biology Reports, 2012)

Complete genomic sequence analysis reveals a novel fabavirus infecting cucurbits in China - Shu-Wei Dong; Hai-Ying Xiang; Qiao-Xia Shang; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2012)

FTH1 binds to Daxx and inhibits Daxx-mediated cell apoptosis - Fang Liu; Zhi-Yin Du; Jun-Lin He; Xue-Qing Liu; Qiu-Bo Yu; Ying-Xiong Wang (Molecular Biology Reports, 2012)

Identification of secretory gelsolin as a plasma biomarker associated with distant organ metastasis of colorectal cancer - Ming-Hung Tsai; Chih-Ching Wu; Pei-Hua Peng; Ying Liang; Yung-Chin Hsiao; Kun-Yi Chien; Jeng-Ting Chen; Shin-Jie Lin; Rei-Ping Tang; Ling-Ling Hsieh; Jau-Song Yu (Journal of Molecular Medicine, 2012)

A Novel Mutation in CACNA1S Gene Associated with Hypokalemic Periodic Paralysis Which has a Gender Difference in the Penetrance - Fei-Feng Li; Qian-Qian Li; Zhen-Xuan Tan; Si-Yao Zhang; Ji Liu; Er-ying Zhao; Gui-Chun Yu; Jin Zhou; Li-Ming Zhang; Shu-Lin Liu (Journal of Molecular Neuroscience, 2012)

G6PD Genotype and Its Associated Enzymatic Activity in a Chinese Population - Wei Ying Jiang; Bing Yi Zhou; Guo Long Yu; Han Liu; Jing Bo Zeng; Qun Di Lin; Hong Li Xi; Hua Liang (Biochemical Genetics, 2012)

Association between polymorphisms in the signal transducer and activator of transcription and dilated cardiomyopathy in the Chinese Han population - Ying Peng; Bin Zhou; Yanyun Wang; Yu Chen; Hui Li; Yaping Song; Lin Zhang; Li Rao (Molecular and Cellular Biochemistry, 2012)

ADAM17 regulates prostate cancer cell proliferation through mediating cell cycle progression by EGFR/PI3K/AKT pathway - Ping Lin; Xicai Sun; Tian Feng; Haifeng Zou; Ying Jiang; Zijun Liu; Dandan Zhao; Xiaoguang Yu (Molecular and Cellular Biochemistry, 2012)

Molecular characterization of two genotypes of a new polerovirus infecting brassicas in China - Hai-Ying Xiang; Shu-Wei Dong; Qiao-Xia Shang; Cui-Ji Zhou; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2011)

Eukaryotic translation elongation factor 1 delta inhibits the ubiquitin ligase activity of SIAH-1 - Huiling Wu; Yan Shi; Ying Lin; Wei Qian; Yao Yu; Keke Huo (Molecular and Cellular Biochemistry, 2011)

A convolution algorithm to calculate differential cross sections of the Ring effect in the Earth’s atmosphere based on rotational Raman scattering - Dong Han; LiangFu Chen; Lin Su; JinHua Tao; ShenShen Li; Chao Yu; Ying Zhang; BaoHua He (Science China Earth Sciences, 2011)

Dexamethasone attenuates development of monocrotaline-induced pulmonary arterial hypertension - Wei Wang; Yu-lin Wang; Xiao-ying Chen; Yu-tang Li; Wei Hao; You-peng Jin; Bo Han (Molecular Biology Reports, 2011)

Interaction of green tea polyphenol epigallocatechin-3-gallate with sunitinib: potential risk of diminished sunitinib bioavailability - Jun Ge; Ben-Xu Tan; Ye Chen; Li Yang; Xing-Chen Peng; Hong-Ze Li; Hong-Jun Lin; Yu Zhao; Meng Wei; Ke Cheng; Long-Hao Li; Hang Dong; et al. (Journal of Molecular Medicine, 2011)

Characterization and expression of chicken selenoprotein W - Bor-Rung Ou; Mei-Jung Jiang; Chao-Hsiang Lin; Yu-Chuan Liang; Kuei-Jen Lee; Jan-Ying Yeh (BioMetals, 2011)

Molecular epidemiology of Echovirus 30 in Taiwan, 1988–2008 - Guan-Ming Ke; Kuei-Hsiang Lin; Po-Liang Lu; Yi-Chin Tung; Chu-Feng Wang; Liang-Yin Ke; Min-Sheng Lee; Pei-Chin Lin; Hui-Ju Su; Yi-Ying Lin; Tzu-Ping Huang; Jen-Ren Wang; et al. (Virus Genes, 2011)

A novel strain of Beet western yellows virus infecting sugar beet with two distinct genotypes differing in the 5′-terminal half of genome - Cui-Ji Zhou; Hai-Ying Xiang; Tao Zhuo; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Virus Genes, 2011)

Effects of Tai Chi on adiponectin and glucose homeostasis in individuals with cardiovascular risk factors - Rei-Yeuh Chang; Malcolm Koo; Meng-Ying Ho; Zi-Zi Lin; Zer-Ran Yu; Yen-Fen Lin; Be-Jen Wang (European Journal of Applied Physiology, 2011)

An intelligent electronic capsule system for automated detection of gastrointestinal bleeding - Hong-ying Liu; Gang Wang; Kang Wei; Xi-tian Pi; Lan Zhu; Xiao-lin Zheng; Zhi-yu Wen (Journal of Zhejiang University-SCIENCE B, 2010)

Inhibition of phosphodiesterase-4 reverses memory deficits produced by Aβ25–35 or Aβ1–40 peptide in rats - Yu-Fang Cheng; Chuang Wang; Huan-Bing Lin; Yun-Feng Li; Ying Huang; Jiang-Ping Xu; Han-Ting Zhang (Psychopharmacology, 2010)

Morphological changes of Fusarium oxysporum induced by CF66I, an antifungal compound from Burkholderia cepacia - Xin Li; Hui-Ying Yu; Yi-Feng Lin; Hong-Mei Teng; Lei Du; Guo-Gang Ma (Biotechnology Letters, 2010)

Constitutive expression of a fungal glucose oxidase gene in transgenic tobacco confers chilling tolerance through the activation of antioxidative defence system - Subbiyan Maruthasalam; Yi Lun Liu; Ching Mei Sun; Pei Ying Chen; Chih Wen Yu; Pei Fang Lee; Chin Ho Lin (Plant Cell Reports, 2010)

The envelope glycoprotein domain III of dengue virus type 2 induced the expression of anticoagulant molecules in endothelial cells - Lien-Cheng Chen; Trai-Ming Yeh; Yi-Ying Lin; Yi-Fen Wang; Shu-Jem Su; Chang-Yu Chen; Kuan-Hua Lin; Miao-Chen Chou; Huey-Wen Shyu (Molecular and Cellular Biochemistry, 2010)

Molecular characterization of two Chinese isolates of Beet western yellows virus infecting sugar beet - Hai-Ying Xiang; Shu-Wei Dong; Hui-Zhong Zhang; Wei-Lin Wang; Min-Quan Li; Cheng-Gui Han; Da-Wei Li; Jia-Lin Yu (Virus Genes, 2010)

Over-expression of the AtGA2ox8 gene decreases the biomass accumulation and lignification in rapeseed (Brassica napus L.) - Xiao-ying Zhao; Deng-feng Zhu; Bo Zhou; Wu-sheng Peng; Jian-zhong Lin; Xing-qun Huang; Re-qing He; Yu-hong Zhuo; Dan Peng; Dong-ying Tang; Ming-fang Li; Xuan-ming Liu (Journal of Zhejiang University-SCIENCE B, 2010)

Responses of phospholipase D and lipoxygenase to mechanical wounding in postharvest cucumber fruits - Yu-ying Zhao; Chun-lu Qian; Ji-cheng Chen; Yan Peng; Lin-chun Mao (Journal of Zhejiang University-SCIENCE B, 2010)

Geniposide inhibits interleukin-6 and interleukin-8 production in lipopolysaccharide-induced human umbilical vein endothelial cells by blocking p38 and ERK1/2 signaling pathways - Hong-Tao Liu; Jun-Lin He; Wen-Ming Li; Zhu Yang; Ying-Xiong Wang; Juan Yin; Yu-Guang Du; Chao Yu (Inflammation Research, 2010)

Two genetic divergence centers revealed by chloroplastic DNA variation in populations of Cinnamomum kanehirae Hay - Dai-Chang Kuo; Chia-Chia Lin; Kuo-Chieh Ho; Yu-Pin Cheng; Shih-Ying Hwang; Tsan-Piao Lin (Conservation Genetics, 2010)

Transgenic Amorphophallus konjac expressing synthesized acyl-homoserine lactonase (aiiA) gene exhibit enhanced resistance to soft rot disease - Huifang Ban; Xinli Chai; Yongjun Lin; Ying Zhou; Donghai Peng; Yi Zhou; Yulan Zou; Ziniu Yu; Ming Sun (Plant Cell Reports, 2009)

Erratum to: Role of the Conserved Thr399 and Thr417 Residues of Bacillus licheniformis γ-Glutamyltranspeptidase as Evaluated by Mutational Analysis - Rui-Cin Lyu; Hui-Yu Hu; Lih-Ying Kuo; Huei-Fen Lo; Ping-Lin Ong; Hui-Ping Chang; Long-Liu Lin (Current Microbiology, 2009)

Human papillomavirus type-distribution in cervical cancer in China: the importance of HPV 16 and 18 - Wen Chen; Xun Zhang; Anco Molijn; David Jenkins; Ju-Fang Shi; Wim Quint; Johannes E. Schmidt; Ping Wang; Yu-Ling Liu; Lian-Kun Li; Hong Shi; Ji-Hong Liu; et al. (Cancer Causes & Control, 2009)

Characterization of the complete genome sequence of pike fry rhabdovirus - Hong-Lian Chen; Hong Liu; Zong-Xiao Liu; Jun-Qiang He; Long-Ying Gao; Xiu-Jie Shi; Yu-Lin Jiang (Archives of Virology, 2009)

Role of the Conserved Thr399 and Thr417 Residues of Bacillus licheniformis γ-Glutamyltranspeptidase as Evaluated by Mutational Analysis - Rui-Cin Lyu; Hui-Yu Hu; Lih-Ying Kuo; Huei-Fen Lo; Ping-Lin Ong; Hui-Ping Chang; Long-Liu Lin (Current Microbiology, 2009)

KIFC1 participates in acrosomal biogenesis, with discussion of its importance for the perforatorium in the Chinese mitten crab Eriocheir sinensis - Keming Yu; Lin Hou; Jun-Quan Zhu; Xue-Ping Ying; Wan-Xi Yang (Cell and Tissue Research, 2009)

Human mesenchymal stem cells-like cells as cellular vehicles for delivery of immunotoxin in vitro - Chang-chen Hu; Yi-quan Ke; Xin-lin Sun; Xiao-dan Jiang; Ru-xiang Xu; Jun Lv; Yu-sheng Wang; Ying-qian Cai; Ling-sha Qin; Yu-xi Zou (Biotechnology Letters, 2009)

Genetic analysis of H3 subtype influenza viruses isolated from domestic ducks in northern China during 2004–2005 - Juan Pu; Qin-Fang Liu; Ying-Ju Xia; Yu-Lei Fan; Earl G. Brown; Fu-Lin Tian; Jin-Hua Liu (Virus Genes, 2009)

Baicalein attenuates intimal hyperplasia after rat carotid balloon injury through arresting cell-cycle progression and inhibiting ERK, Akt, and NF-κB activity in vascular smooth-muscle cells - Chieh-Yu Peng; Shiow-Lin Pan; Ying-Wen Huang; Jih-Hwa Guh; Ya-Ling Chang; Che-Ming Teng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2008)

Identification of a Kunitz inhibitor from Albizzia kalkora and its inhibitory effect against pest midgut proteases - Jia-Yu Zhou; Hai Liao; Nian-Hui Zhang; Lin Tang; Ying Xu; Fang Chen (Biotechnology Letters, 2008)

Complete sequence analysis reveals two distinct poleroviruses infecting cucurbits in China - Hai-ying Xiang; Qiao-xia Shang; Cheng-gui Han; Da-wei Li; Jia-lin Yu (Archives of Virology, 2008)

A collection of 10,096 indica rice full-length cDNAs reveals highly expressed sequence divergence between Oryza sativa indica and japonica subspecies - Xiaohui Liu; Tingting Lu; Shuliang Yu; Ying Li; Yuchen Huang; Tao Huang; Lei Zhang; Jingjie Zhu; Qiang Zhao; Danlin Fan; Jie Mu; Yingying Shangguan; et al. (Plant Molecular Biology, 2007)

Mitochondrial anchoring of PKCα by PICK1 confers resistance to etoposide-induced apoptosis - Wei-Li Wang; Sheau-Farn Yeh; Eagle Yi-Kung Huang; Yu-Ling Lu; Chun-Fa Wang; Chi-Ying F. Huang; Wey-Jinq Lin (Apoptosis, 2007)

Basic Characteristics of Sporolactobacillus inulinus BCRC 14647 for Potential Probiotic Properties - Hui-Ying Huang; Shih-Yi Huang; Pei-Yu Chen; V. An-Erl King; Yeu-Pyng Lin; Jen-Horng Tsen (Current Microbiology, 2007)

Pleomorphic extra-renal manifestation of the glomerular podocyte marker podocalyxin in tissues of normal beagle dogs - Wei-Ling Lin; Victor Fei Pang; Chen-Hsuan Liu; Jen-Yau Chen; Kuo-Fang Shen; Yu-Yu Lin; Chun-Ying Yu; Yung-Ho Hsu; Tzuu-Shuh Jou (Histochemistry and Cell Biology, 2007)

The contents and forms of solid-phase species of radioactive strontium and cesium in Taiwan soils - S. W. Chang Chien; M. C. Wang; C. L. Chiu; Yu-Ming Lin; Shu-Ying Lai (Environmental Monitoring and Assessment, 2007)

Ex vivo expansion and pluripotential differentiation of cryopreserved human bone marrow mesenchymal stem cells - Ying Xiang; Qiang Zheng; Bing-bing Jia; Guo-ping Huang; Yu-lin Xu; Jin-fu Wang; Zhi-jun Pan (Journal of Zhejiang University-SCIENCE B, 2007)

Effect of Epstein–Barr virus infection on global gene expression in nasopharyngeal carcinoma - Yuan-Chii Gladys Lee; Yu-Chyi Hwang; Kuang-Chi Chen; Yong-Shiang Lin; Dah-Yeou Huang; Tao-Wei Huang; Cheng-Yan Kao; Han-Chung Wu; Chin-Tarng Lin; Chi-Ying F. Huang (Functional & Integrative Genomics, 2006)

IGFBP7 plays a potential tumor suppressor role against colorectal carcinogenesis with its expression associated with DNA hypomethylation of exon 1 - Wen-jing Ruan; Jie Lin; En-ping Xu; Fang-ying Xu; Yu Ma; Hong Deng; Qiong Huang; Bing-jian Lv; Hu Hu; Jing Cui; Mei-juan Di; Jian-kang Dong; et al. (Journal of Zhejiang University-SCIENCE B, 2006)

Over-expressed estrogen receptor-α up-regulates hTNF-α gene expression and down-regulates β-catenin signaling activity to induce the apoptosis and inhibit proliferation of LoVo colon cancer cells - Hsi-Hsien Hsu; Sue-Fei Cheng; Li-Mien Chen; Jer-Yu Liu; Chun-Hsien Chu; Yi-Jiun Weng; Zih-Ying Li; Chung-Sheng Lin; Shin-Da Lee; Wei-Wen Kuo; Chih-Yang Huang (Molecular and Cellular Biochemistry, 2006)

Mutation analysis of 218 Chinese patients with Wilson disease revealed no correlation between the canine copper toxicosis gene MURR1 and Wilson disease - Zhi-Ying Wu; Gui-Xian Zhao; Wan-Jin Chen; Ning Wang; Bo Wan; Min-Ting Lin; Shen-Xing Murong; Long Yu (Journal of Molecular Medicine, 2006)

Contrasting phylogeographical patterns of two closely related species, Machilus thunbergii and Machilus kusanoi (Lauraceae), in Taiwan - Su‐Hwa Wu; Ching‐Yuan Hwang; Tsan‐Piao Lin; Jeng‐Der Chung; Yu‐Pin Cheng; Shih‐Ying Hwang (Journal of Biogeography, 2006)
Aim The purpose of this paper was to study the patterns of genetic variation, demographic history, haplotype relationships and potential location of diversity centres of two closely related species, Machilus thunbergii and Machilus kusanoi . Location The phylogeography of M. thunbergii and M. kusanoi was examined by sampling 110 and 106 individuals from 25 and 16 sampling sites, respectively, across their distributional range in Taiwan. Machilus thunbergii is distributed on the Asian mainland, South Korea, southern Japan, the Ryukyus, Taiwan and the Philippines, whereas M. kusanoi is endemic to Taiwan. These two species are closely related, and both are widely distributed in Taiwan but occupy different altitudinal zones and habitats. Methods The range‐wide variation of M. thunbergii and M. kusanoi in Taiwan was studied using chloroplast DNA (cpDNA) variations. A haplotype network was constructed with the computer program tcs . Nested clade analysis was conducted with the computer program ceodis , and various parameters of genetic diversity were calculated and neutrality tested by the computer program D na SP. Population differentiation was estimated using the programs arlequin and hapstep . The contribution of the populations to gene diversity and to allelic richness was calculated using the software contrib . The level of divergence for each population from the remaining populations was calculated as the mean value of pairwise F ST for each population against the rest of the populations. Results Extremely low levels of genetic differentiation were found for both species. This result suggested that these two species probably survived in multiple relict refugia with different population sizes throughout the island during low‐temperature periods of the Pleistocene. In addition, nested clade analysis (NCA) of cpDNA haplotypes indicated that restricted gene flow with isolation‐by‐distance characterized the recolonization after the Pleistocene by Tashueshan and Shiouhluan populations of M. thunbergii in the north‐central area west of the Central Mountain Range (CMR). In contrast, NCA analysis indicated that a major diversity centre on the southern tip of the island (Kending population) and contiguous range expansion characterized the recolonization by M. kusanoi of northern areas along the east side of the CMR. The major diversity centres found for the two species examined were further supported by the results of the mean F ST for individual populations in comparison with other populations, and of the contribution of the divergence component to the total diversity. Main conclusions This research supports the multiple relict refugia hypothesis for both species investigated. Populations of M. thunbergii at Shiouhluan and Tashueshan in the north‐central area west of the CMR represent a diversity centre currently expanding its size. A diversity centre at the southern‐edge population of M. kusanoi , and a contiguous range expansion from Kending, were found. These results indicate that the M. thunbergii populations at Tashueshan and Shiouhluan and the M. kusanoi population at Kending, and even Soukar, are evolutionarily significant units for conservation programmes.

Functional polymorphisms of FGA, encoding α fibrinogen, are associated with susceptibility to venous thromboembolism in a Taiwanese population - Yu-Lin Ko; Lung-An Hsu; Tsu-Shiu Hsu; Chia-Ti Tsai; Ming-Sheng Teng; Semon Wu; Chi-Jen Chang; Ying-Shiung Lee (Human Genetics, 2006)

Adsorption-elution purification of chimeric Bacillus stearothermophilus leucine aminopeptidase II with raw-starch-binding activity - Yu-Wen Hua; Meng-Chun Chi; Huei-Fen Lo; Lih-Ying Kuo; Kuo-Lung Ku; Long-Liu Lin (World Journal of Microbiology and Biotechnology, 2005)

External sources of urban competitive advantages in China - Tao-fang Yu; Chao-lin Gu; Xiu-ying Chen (Chinese Geographical Science, 2005)

Potential refugia in Taiwan revealed by the phylogeographical study of Castanopsis carlesii Hayata (Fagaceae) - YU‐PIN CHENG; SHIH‐YING HWANG; TSAN‐PIAO LIN (Molecular Ecology, 2005)
In this study, we examined spatial patterns of chloroplast DNA (cpDNA) variation in a total of 30 populations of Castanopsis carlesii Hayata (Fagaceae), a subtropical and temperate tree species, including 201 individuals sampled throughout Taiwan. By sequencing two cpDNA fragments using universal primers (the trn L intron and the trn V‐ trn M intergenic spacer), we found a total of 1663 bp and 21 polymorphic sites. These gave rise to a total of 28 cpDNA haplotypes. The level of differentiation among the populations studied was relatively high ( G ST = 0.723). Two ancestral haplotypes are widely distributed. The Central Mountain Ridge (CMR) of Taiwan represents an insurmountable barrier to the east–west gene flow of C. carlesii . Among the populations studied, three separated populations, at Lienhuachih, Fushan and Lichia, have high nucleotide diversity. Estimates of N ST – G ST for populations on both sides of the CMR indicate that no phylogeographical structure exists. According to the genealogical tree, number of rare haplotype and population genetic divergence, this study suggests that two potential refugia existed during the last glaciation: the first refugium was located in a region to the north of Hsuehshan Range (HR) and west of the CMR; the second refugium was located in south, especially southeastern Taiwan. In fact, the second refugium happens to be the same as that reported for Quercus glauca . A ‘star‐like’ genealogy is characteristic when all haplotypes rapidly coalesce and is a general outcome of population expansion. The neutrality test and mismatch distribution also suggest demographic expansion recovering from a bottleneck.

Nucleotide Sequences and Functions of the Epstein-Barr Virus Latent Membrane Protein 1 Genes Isolated from Salivary Gland Lymphoepithelial Carcinomas - Kai Yu Jen; Masaya Higuchi; Jun Cheng; Jiang Li; Lan Yan Wu; Ying Fang Li; Han Liang Lin; Zhilong Chen; Vladimir Gurtsevitch; Masahiro Fujii; Takashi Saku (Virus Genes, 2005)

Intracellular expression of Vitreoscilla hemoglobin in Aspergillus terreus to alleviate the effect of a short break in aeration during culture - Yu-Hui Lin; Ywan-Feng Li; Min-Chang Huang; Ying-Chieh Tsai (Biotechnology Letters, 2004)

Site-Directed Mutagenesis of the Conserved Threonine, Tryptophan, and Lysine Residues in the Starch-Binding Domain of Bacillus sp. Strain TS-23 a-Amylase - Huei-Fen Lo; Wen-Ying Chiang; Meng-Chun Chi; Hui-Yu Hu; Long-Liu Lin (Current Microbiology, 2004)

Genetic Diversity and Relationship of Yunnan Native Cattle Breeds and Introduced Beef Cattle Breeds - Ying Yu; Lin-Sheng Lian; Ji-Kun Wen; Xian-Wei Shi; Fang-Xian Zhu; Long Nie; Ya-Ping Zhang (Biochemical Genetics, 2004)

Sequence Analysis of the Complete Genome of Rice Black-Streaked Dwarf Virus Isolated from Maize with Rough Dwarf Disease - Zhao-Hui Wang; Shou-Guo Fang; Jia-Ling Xu; Li-Ying Sun; Da-Wei Li; Jia-Lin Yu (Virus Genes, 2003)

Overexpression, Purification, and Characterization of the Recombinant Leucine Aminopeptidase II of Bacillus stearothermophilus - Lih-Ying Kuo; Guang-Yuh Hwang; Yu-Jing Lai; Shin-Ling Yang; Long-Liu Lin (Current Microbiology, 2003)

Noninvasive Characterization of Regional Variation in Drug Transport into Human Stratum Corneum in Vivo - Jui-Chen Tsai; Ching-Yu Lin; Hamm-Ming Sheu; Yu-Li Lo; Ying-Hsuan Huang (Pharmaceutical Research, 2003)

Cloning and expression of a new Tibetan hulless barley (Hordeum vulgare) β-1,3-glucanase gene - Zeng Yu; Xu Ying; Tang Lin; Qiang Xiao-Lin; Chen Fang (Biotechnology Letters, 2003)

Replacement of Methionine 208 in a Truncated Bacillus sp. TS-23 α-Amylase with Oxidation-Resistant Leucine Enhances Its Resistance to Hydrogen Peroxide - Long-Liu Lin; Huei-Fen Lo; Wen-Ying Chiang; Hui-Yu Hu; Wen-Hwei Hsu; Chen-Tien Chang (Current Microbiology, 2003)

RAPD markers in diversity detection and variety identification of Tibetan hulless barley - Zeng Yu; Lan Li-Qiong; Luo Huan; Bai Jie; Yang Man-Ye; Miao Chen; Cai Ying-Fan; Qiang Xiao-Lin; Chen Fang (Plant Molecular Biology Reporter, 2002)

Geochemical and Sm–Nd isotopic characteristics of metabasites from central Hainan Island, South China and their tectonic significance - Xian‐Hua Li; Hanwen Zhou; Sun‐Lin Chung; Shijiang Ding; Ying Liu; Chi‐Yu Lee; Wenchun Ge; Yeming Zhang; Renjie Zhang (Island Arc, 2002)
Major and trace elements and Sm–Nd isotopic data are presented for metabasites that are present as lenses within Paleozoic metasediments in the Chenxing and Bangxi regions, central Hainan Island, Southeast (SE) China. Most metabasites are metamorphosed cumulated gabbroic rocks tholeiitic in nature, and characterized by varying degrees of depletion in Th, Nb, Ta and light rare earth elements (LREE). Moreover, they show high positive ∈Nd(T) values of approximately +7, similar to those of mid‐ocean ridge basalts (MORB). A Sm–Nd isochron age of 333 ± 12 Ma obtained for the metabasites is interpreted as their crystallization age. The combined geochemical and Sm–Nd isotopic data suggest that the metabasites were generated by dynamic partial melting from a MORB‐like mantle source in an oceanic regime. These rocks probably represent remnants of fragmented oceanic crust of the eastern part of Paleo‐Tethys. They were obducted onto the continental crust as part of the ‘Shilu Mélange’ in earliest Mesozoic time when southern Hainan (part of the Indochina block) collided with northern Hainan (part of South China). Alternatively, they could be formed in a volcanic rifted passive margin at the sea‐floor spreading stage as part of MORB‐like seaward‐dipping reflector break‐up packages.

Lipid peroxidation and cell death mechanisms in pulmonary epithelial cells induced by peroxynitrite and nitric oxide - Yuan-Soon Ho; Hung-Bin Liou; Jen-Kun Lin; Jiiang-Huei Jeng; Min-Hsiung Pan; Yu-Ping Lin; How-Ran Guo; Sheng-Yow Ho; Ching-Chang Lee; Ying-Jan Wang (Archives of Toxicology, 2002)

Regional carrying capacity: case studies of Bohai Rim area - Yu Dan-lin; Mao Han-ying (Journal of Geographical Sciences, 2002)

Genetic variations in the cholesteryl ester transfer protein gene and high density lipoprotein cholesterol levels in Taiwanese Chinese - Lung-An Hsu; Yu-Lin Ko; Kuang-Hung Hsu; Yu-Hsien Ko; Ying-Shiung Lee (Human Genetics, 2002)

Inhibitory effect of esculetin on oxidative damage induced by t -butyl hydroperoxide in rat liver - Wea-Lung Lin; Chau-Jong Wang; Yu-Ying Tsai; Chuen-Lan Liu; Jin-Ming Hwang; Tsui-Hwa Tseng (Archives of Toxicology, 2000)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)